Future of lithium industry in Chile and the national lithium strategy: integration of solar evaporation, direct lithium extraction, and controlled reinjection - Norman Toro; Iván Salazar; Eleazar Salinas-Rodríguez; Manuel Saldana; Rossana Sepúlveda; Pía C. Hernández; Felipe M. Galleguillos-Madrid; Jonathan Castillo (Minerals Engineering, 2026)

Imaging sweetness: Rapid permeation of sucrose into rice callus cells as a component of cryoprotectant solutions - Albert Ochoa-Castillo; Gayle M. Volk; Nancy E. Levinger (Cryobiology, 2026)

La1: an evolutionarily conserved player in the Arabidopsis telomerase complex - Chinmay Phadke; Saundarya K. Mishra; Jiarui Song; Rebekah Holtsclaw; Claudia Castillo Gonzalez; Ishan Kundel; Edward M. Marcotte; Ophelia Papoulas; Dorothy E. Shippen (Plant Cell Reports, 2026)
Key message Quantitative mass spectrometry of Arabidopsis telomerase uncovered AtLa1, a homolog of ciliate and yeast proteins that promotes telomerase maturation. AtLa1 is essential for telomerase function in vivo, and in vitro it engages the same region of AtTR bound by AtNAP57, homologous to a telomerase accessory from mammals. Abstract Striking divergence is evident in the biogenesis pathways and protein complements of telomerase from mammals and single-cell organisms. However, little is known about plant telomerase. Along with catalytic subunit TERT and templating RNA TR, we previously showed Arabidopsis thaliana telomerase is also associated with AtNAP57, a dyskerin homolog essential for mammalian telomerase biogenesis. Here we employ quantitative mass spectrometry (qMS) to uncover additional Arabidopsis telomerase constituents. We report AtLa1 as a new telomerase-associated protein. RNA-IP assays confirmed AtLa1 association with AtTR, while transient RNAi-mediated knockdown of AtLa1 strongly diminished telomerase activity, supporting a functional role for AtLa1 in telomere maintenance in vivo. In vitro binding studies revealed AtLa1 contacts AtTR via the UUU-3′OH and a plant-specific P1a-P1b-P4 three-way junction (TWJ). Notably, the TWJ is also required for AtNAP57 association with AtTR. However, this protein was not detected in our qMS experiment using overexpressed AtTERT and AtTR, perhaps because the purification scheme enriched for RNP assembly intermediates. La-related proteins serve as RNA chaperones and are associated with a wide variety of telomerase complexes. Therefore, we postulate that AtNAP57 and AtLa1 compete for AtTR or bind sequentially during telomerase biogenesis. Further exploration of Arabidopsis telomerase may offer novel insights into telomerase evolution and mechanisms of biogenesis.

Deep Phylogenomic Structure and Microendemism in Baja California Ammotrechidae (Arachnida: Solifugae) Support a Model of Distributed Diversification - Matthew R. Graham; Carlos E. Santibáñez‐López; R. Ryan Jones; Joshua A. Idjadi; Athenea M. Acosta; Fadia Sara Ceccarelli; Jaír R. Castillo; Diana Laura Batista‐Perales; Jack O. Brookhart; Paula E. Cushing (Journal of Biogeography, 2026)
Aim To assess phylogeographic structure, phylogenetic diversity and historical diversification processes in ammotrechid camel spiders from the Baja California Peninsula. Location Baja California Sur, Mexico. Time Period Miocene to Pleistocene. Major Taxa Studied Ammotrechid camel spiders (Solifugae: Ammotrechidae). Methods We conducted the first phylogeographic analysis of Baja California Sur ammotrechid camel spiders using mitochondrial COI sequences and genome‐wide RADseq data. Phylogenomic analyses, divergence dating, species accumulation curves and tests of admixture (F 3 statistics) were used to evaluate lineage structure, timing of diversification and patterns of connectivity. Results We uncovered deep phylogenomic structure and extensive cryptic diversity, identifying at least 16 putative lineages, many restricted to single localities. Divergence dating indicates Miocene origins with subsequent Plio–Pleistocene diversification. Although several lineages exhibit north–south structure, divergence times and spatial patterns do not support diversification driven by discrete transpeninsular seaway vicariance at major southern breaks (e.g., La Paz/Loreto). Instead, patterns support a model of distributed diversification shaped by tectonic segmentation, habitat heterogeneity, and climatic oscillation. Limited admixture among a subset of closely related lineages, suggested by incongruent tree topologies and F 3 statistics, indicates episodic secondary contact rather than long‐term connectivity. Species accumulation curves did not approach an asymptote, suggesting that much of the region's solifuge diversity remains undocumented. Main Conclusions Ammotrechid camel spiders preserve fine‐scale genomic signatures of landscape history in Baja California Sur and reveal previously undocumented levels of endemism and diversification. These results highlight Solifugae as promising but underused systems for geogenomic studies of desert biogeography.

Mercury binding to selenoproteins and age-related depletion of bioavailable selenium in long-finned pilot whales - Nunnapus Laitip; M. Estela del Castillo Busto; Zuzana Gajdosechova; Heidi Goenaga-Infante; Andrea Raab; Christian Ward-Deitrich; Andrew Brownlow; Joerg Feldmann (Science of The Total Environment, 2026)

Methoxyacetic acid exposure in rats induces N-butyrylglycinuria consistent with beta-oxidation impairment - Samuele Sala; Janonna Kadyrov; Andres Bernal; Andres M. Castillo; Preechaya Naraprasertkul; Nadia Paesalasakul; Proud Bekanan; Issariya Dhitsuwon; Thanaporn Kulthawatsiri; Reika Masuda; Manthan Sharma; Jutarop Phetcharaburanin; et al. (Archives of Toxicology, 2026)

Confirmed Outbreaks of Streptococcosis Caused by Streptococcus agalactiae Serotype Ia in Nile Tilapia Culture From Campeche, Mexico - R. A. Avila‐Castillo; R. E. del Rio‐Rodriguez; S. A. Soto‐Rodriguez; J. Navarro‐Flores; A. D. Cu‐Escamilla; F. I. Marrujo‐Lopez; K. G. Aguilar‐Rendon; M. I. Gomez‐Solano (Journal of Fish Diseases, 2026)
Streptococcus agalactiae was confirmed as the etiologic agent of streptococcosis in Nile tilapia ( Oreochromis niloticus ) from Campeche, Mexico, during a cross‐sectional investigation of eight semi‐intensive farms (2021–2022) that yielded virulent strains in a challenge assay. Standard bacteriology, histopathology, API‐20 Strep phenotyping, one‐step PCR, and real‐time PCR confirmed S. agalactiae in five farms (62.5%). Gross and histological lesions were characterised by mid‐axial and peduncular muscle abscesses, extensive myonecrosis, granuloma formation, polyserositis, and occasional suppurative meningitis. Experimental infections fulfilled Koch's postulates. Juveniles of O. niloticus (20 g) infected with strain ASG‐2290 at 10 6 CFU/mL produced 53% mortality at 96 h. Whole‐genome sequencing of the strains ASG‐2290 and ASG‐2292 identified them as S. agalactiae Ia, marking the first report of this serotype isolated from farmed tilapia in Mexico. Frequent interstate fry movements are likely to be a risk factor for pathogen dissemination. These findings document the geographic expansion of pathogenic S. agalactiae into the Yucatan Peninsula, underscoring the need for strengthened surveillance, biosecurity, and diagnostic capacity to mitigate economic losses in Mexican tilapia aquaculture. Considering that tilapia aquaculture is carried out all year‐round in the Yucatan Peninsula, the implications of these findings are of major concern.

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

Ensuring adaptability and applicability of long-term contaminant monitoring initiatives: A discussion of NOAA’s National Mussel Watch Program current practices and future approaches - N. A. Castillo; L. M. Swam-Jaramillo; M. M. Rider; A. Morozova; K. L. Kimbrough; E. D. Davenport; M. A. Edwards; F. Arzayus; D. A. Apeti (Environmental Monitoring and Assessment, 2026)

Continent-wide stock structure and connectivity of silver trevally (Pseudocaranx georgianus) based on population genomics and otolith shape and chemistry - Zoriana H.T. Lam; John Stewart; Jonathan Sandoval-Castillo; Patrick Reis-Santos; Rhiannon A. Van Eck; Bronwyn M. Gillanders; Peter Ritchie; Maren Wellenreuther; Charlie Huveneers; David V. Fairclough; Ashley M. Fowler; Julian Hughes; et al. (Fisheries Research, 2026)

Ancient and recent soils as indicators of the genesis and evolution of Salada de Chiprana from middle Pleistocene to present (Ebro Basin, NE Spain) - M. Tierra; C. Castañeda; F.J. Gracia; R. Rodríguez-Ochoa; J.R. Olarieta; A. Medialdea; O. Castillo (CATENA, 2026)

Revisiting Strategies for Bacterial Enumeration: The Case for Viable but Nonculturable (VBNC) Cells in Supplement Products - T. O. Kirby; J. R. Townsend; E. D. Walts; A. Kiefer; J. Zhu; M. Cormier; D. Pathak; C. Wong; A. Castillo; J. Ochoa-Repáraz; R. Jäger; R. H. Lai; et al. (Probiotics and Antimicrobial Proteins, 2026)

Zinc deficiency and sarcopenia define a metabolic frailty phenotype predicting hepatic encephalopathy and early mortality in cirrhosis - Osvely Méndez-Guerrero; Anaisa Carranza-Carrasco; Rodrigo Guerrero-Guerrero; Lilia Castillo-Martínez; Fabiola M. Del Razo-Olvera; Liliana Juárez-Martínez; Rodrigo Otero-Otero; Alma Estanes-Hernández; Patricia Clark; Carlos A. Aguilar-Salinas; Aldo Torre; Graciela E. Castro-Narro; et al. (Metabolic Brain Disease, 2026)

LA-COMET group: In vivo application of the comet assay in animal and plant models, including wild species - Gisela L. Poletta; Patricia Mussali-Galante; J. Alfredo Castillo-Ipiña; Guillermo Espinosa-Reyes; Ana Rosa Flores-Márquez; Donaji J. González-Mille; César A. Ilizaliturri-Hernández; Celeste Ruiz de Arcaute; Efraín Tovar-Sánchez; Juliana da Silva; Deidamia Franco; Ana Leticia García; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Bioactive molecules from Agave salmiana bagasse: Study of their antioxidant, prebiotic potential, and cytotoxicity - Isabel Márquez-Rangel; Mario Cruz; Héctor A. Ruiz; Rosa M. Rodríguez-Jasso; Araceli Loredo-Treviño; Guillermo Castillo-Olvera; Ruth Belmares (Food Research International, 2026)

Formulation and evaluation of a functional beverage from Ilex guayusa Loes. (Aquifoliaceae): Chemical analysis, antioxidant activity, and sensory acceptance - Luis G. Sequeda-Castañeda; Laura D. Bermeo-Pulido; Yineth Piñeros-Castro; Geison M. Costa; Yuri M. Castillo-Quiroga (Food and Humanity, 2026)

Carpobrotus taxa benefit more from clonal integration in their non-native than native ranges - Marta Pérez-Diz; Hana Skálová; Susan Canavan; María Loreto Castillo; Paula Gervazoni; Luís González; Petr Pyšek; Jonatan Rodríguez; Kateřina Štajerová; Giuseppe Brundu; Carla M. D’Antonio; Tom Dudley; et al. (Biological Invasions, 2026)
Understanding physiological integration in invasive clonal plants is relevant to invasion biology because resource transfer across ramets may allow alien plants to buffer spatial heterogeneity in their introduced areas. However, experimental evidence across native and non-native ranges is limited. Here, we tested whether physiological integration provides greater performance benefits to Carpobrotus taxa in non-native than native ranges. We grew clonal fragments under controlled conditions from eleven populations representing different genetic clusters across their native and non-native ranges. Connected recipient ramets showed higher growth than severed ones, with increased ramet length, node number, Branching and Vigor Indices, while connected donor ramets showed reduced growth, indicating resource redistribution within the clone. Plants from non-native ranges exhibited overall higher growth-related traits and chlorophyll content, suggesting enhanced growth and stress tolerance across genetic backgrounds. These results indicate that physiological integration allows Carpobrotus taxa to overcome environmental heterogeneity by reallocating resources among ramets, promoting clonal growth and expansion, and potentially increasing competitive ability in non-native ranges. Our findings provide experimental evidence across multiple populations that physiological integration can promote the ecological success of clonal invaders.

Vaccine strategies for cancer prevention in Lynch syndrome: the potential of dendritic cell-based therapy - Romy N. Kuipers; Mark A. J. Gorris; Cristina Bayó; Tom Hofland; Daniel Benítez Ribas; Georgina Flórez Grau; Nicoline Hoogerbrugge; Joaquin Castillo; Francesc Balaguer; Tanya M. Bisseling; Gerty Schreibelt; I. Jolanda M. de Vries (Familial Cancer, 2026)
Cancer vaccines offer a promising strategy for cancer prevention, particularly in hereditary cancer syndromes such as Lynch syndrome (LS). LS is characterized by a high lifetime risk of developing various malignancies due to defects in DNA mismatch repair, leading to an accumulation of mutations, particularly frameshift insertion/deletions (indels) within microsatellite loci. These indels create shared tumour-specific neoantigens, which are unique to LS and can be recognized by the immune system and trigger cancer cell killing. Importantly, these neoantigens are also present in precancerous lesions, making LS an ideal target for immune-interception strategies aimed at prevention. Over the years, a variety of vaccine designs targeting different antigens along with a range of delivery platforms have been explored for different types of tumours, each with its own advantages and limitations. In this review, we provide an overview of the key antigens and delivery platforms used in cancer preventive vaccine development for LS, evaluate their limited clinical outcomes to date, and explore the future directions of preventive vaccine immunotherapy. A particular focus is placed on the promising potential of dendritic cell vaccination therapy as a future approach in this field.

Devonian metavolcanic rocks in the Rio Puelo section, Patagonian Andes of Chile: possible implications for the eastern limit of Chaitenia and the origin of the Liquiñe Ofqui Fault Zone - F. Hervé; C.M. Fanning; P. Quezada; P. Castillo; K. Deckart; R.J. Pankhurst; C.W. Rapela; C. Palape; M. Zúñiga; M. Calderón (Journal of South American Earth Sciences, 2026)

A subnational social vulnerability index for use in drought decision support systems - Md Sariful Islam; Yusuke Kuwayama; Dara Entekhabi; Katlyn M. Turner; Catherine Lu; Felipe Munoz Castillo; Zolana Joao; Vangiliya Filipe Pereira; Osvaldo Porto; Luciano Lupedia; Ivandro Rodrigues; Danielle Wood (Environmental Science & Policy, 2026)

Effect of stinging nettle powder (Urtica dioica) supplementation on productive and physiological performance of laying hens - Magdy Sayed Hassan Hassan; Inas Ibrahim Ismail; Ahmed Mohamed Dief Youssef; Ahmed M. Hussein; Nahla A. Elrazik; Ibrahim Abd El hamed Fathy; EIham Salah Mohamed Ahmed; Waleed Sobhy El Saqa; José del Carmen Rodríguez-Castillo; Mona M. M. Y. Elghandour (Tropical Animal Health and Production, 2026)

Cytotoxic Edema and Intra-parenchymal Hemorrhage: A Mediated Pathway to Mortality and Functional Outcome in Cerebral Venous Sinus Thrombosis- A sub-analysis of the CLOT-VENUS Registry - Nashwa Abdelhakim; Milagros Galecio-Castillo; Piyush Kalakoti; Leonardo Cruz-Criollo; Aaron Rodriguez-Calienes; Anderson Brito; Jorge Cespedes; Amir Shaban; Anish Venkatesan; Vanessa Cano Nigenda; Andres Alberto Mercado Pompa; Nicholas M. Mohr; et al. (Translational Stroke Research, 2026)
Cytotoxic edema (CE) is a radiographic marker of early tissue injury in cerebral venous thrombosis (CVT) associated with poor outcomes, yet its mechanistic pathway remains unclear. We investigated whether intraparenchymal hemorrhage (IPH) mediates the association between CE and outcomes. We conducted a retrospective cohort study using the multicenter CLOT-VENUS registry, including acute CVT patients treated at two Comprehensive Stroke Centers in the USA and Mexico (2004–2024). CE was defined as hyperintensities around IPH or venous infarct with DWI restricted diffusion and corresponding low ADC, confirming true restricted diffusion. IPH was defined as hemorrhagic transformation of venous infarction or intracerebral hemorrhage on GRE MRI and/or NCCT. Mediation analyses assessed whether IPH mediated CE associations with in-hospital mortality and functional outcomes. Among 394 patients (mean age 42.7 years; 65.5% female), 128 (32.5%) demonstrated CE and 111(30.2%) IPH. CE was associated with in-hospital mortality (aOR 2.63, 95% CI 1.01–7.12) and poor 6-month mRS (aOR 1.71, 95% CI 1.06–2.74). CE was associated with IPH, which in turn was associated with mortality (aOR 8.73, 95% CI 2.93–30.45) and poor mRS (aOR 1.96, 95% CI 1.18–3.25). Adjustment for IPH rendered the CE-outcome associations non-significant. IPH accounted for 76.8% of CE’s effect on mortality and 83.8% on 6-month mRS. Our findings suggest that IPH likely mediates the effect of CE on outcomes in CVT. Although the temporal sequence could not be confirmed, the results underscore the value of early CE detection for timely intervention.

Plant-based production of virus-like particles from hepatitis C virus - Laura M. López-Castillo; Rafael Gonzalez-Castro; Lino Sánchez-Segura; Brisia A. Aguilar-Barragán; Miguel A. Gomez Lim (Planta, 2026)
Main conclusion Virus-like particles (VLP) from hepatitis C virus were successfully produced in Nicotiana benthamiana plants for the first time, by co-expressing three viral proteins (Core, E1 and E2) in a polycistron-like arrangement. Abstract Hepatitis C virus (HCV) remains a global health challenge, underscoring the need for a preventive vaccine. Virus-like particles (VLP) offer a safe alternative, as they resemble native virions without infectious genomes. We expressed the HCV structural proteins Core, E1, and E2 in Nicotiana benthamiana using binary and deconstructed viral vector systems. Western blot confirmed expression, with the binary system achieving higher yields. Purified proteins assembled into spherical VLP (40–60 nm) were confirmed by electron microscopy. These findings demonstrate for the first time the feasibility of producing complete HCV-VLP in plants, supporting their potential as a scalable platform for vaccine development.

Estuarine structure and connectivity influence seasonal and spatial shifts in the food web structure of fish assemblages - Edgar Abraham Aragón-Flores; Rocío Rodiles-Hernández; Miriam Soria-Barreto; Matteo Cazzanelli; Carmen G. Montaña; María M. Castillo (Regional Studies in Marine Science, 2026)

Strengthening national genebanks through genomics and regional collaboration: Lessons from Latin America and the Caribbean - M. Carvajal-Yepes; C. Petroli; M. Correa; F. Breseghello; G. Tapia; E. Salazar; A. Chassaigne; M. Ferreyra; P.H. Reyes-Herrera; M. Guzmán; A. Mendoza; R. Vidal; et al. (Global Food Security, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Low-dose tamoxifen ameliorates ovariectomy-induced metabolic and immune dysfunction - Heather E. McClurg; Amanda Ferraro; Gina Pham; Itzel Morales-Hernandez; Estefania Valencia-Rincon; Kevin D. Pham; Willard M. Freeman; Jacquelyn A. Gorman; Marisol Castillo-Castrejon (GeroScience, 2026)
The decline in estrogen following menopause is a major driver of metabolic and immune dysfunction in aging females. While hormone replacement therapy improves many of these outcomes, its clinical use remains limited due to concerns regarding estrogen-sensitive malignancies. Tissue-selective estrogen complexes (TSECs), which combine estrogens with selective estrogen receptor modulators (SERMs) such as tamoxifen (TAM), represent a promising strategy to preserve the metabolic and immunological benefits of estrogen while reducing oncogenic risk. However, the systemic effects of TAM under conditions of estrogen deficiency remain incompletely defined. In this study, we investigated the metabolic and immunomodulatory actions of low-dose TAM, alone or in combination with 17β-estradiol (E2), in adult ovariectomized (OVX) female mice. OVX resulted in increased adiposity, hepatic steatosis, glucose intolerance, insulin resistance, immunoglobulin G3 (IgG3) concentration, and systemic inflammation, along with decreased immunoglobulin G1 (IgG1) concentration. E2, TAM, and E2 + TAM each attenuated OVX-induced adipose expansion, adipocyte hypertrophy, and proinflammatory cytokine production. TAM improved insulin sensitivity but did not fully restore glucose tolerance. Transcriptomic analysis of visceral adipose tissue-resident B cells revealed that E2 and E2 + TAM modulate overlapping yet distinct immune-regulatory networks, including suppression of pro-inflammatory signaling, regulation of immune checkpoints, and genes linked to adipose homeostasis. Low-dose TAM emerges as a modulator of estrogen receptor signaling that attenuates multiple features of OVX-induced metabolic and inflammatory dysfunction, though its limited effect on glycemic control highlights the need for tissue-specific evaluation of SERM-based interventions. These findings provide mechanistic insight into endocrine–immune–metabolic interactions and inform strategies to reduce aging-related disease risk in postmenopausal women. Graphical Abstract Created in BioRender ( https://BioRender.com/7ouhlqq ), Castillo M. (2025)

Using front face fluorescence for rapid estimation of furosine concentration in heat treated milk: a kinetic study - C. González-Gallardo; N. Ayala; F. Ali; A. Zamora; J. Saldo; M. Castillo (International Dairy Journal, 2026)

Functional analysis of wssv025 gene in the pathogenicity of white spot syndrome virus in Penaeus monodon - Shanel G. Manito; Cong-Yan Chen; Brandon Rafael de Jesús Castillo-Corea; Mary Nia M. Santos; Casiano H. Choresca; Fiona L. Pedroso; Christopher Marlowe Caipang; Han-Ching Wang; Fernand F. Fagutao (Fish & Shellfish Immunology, 2026)

Sex matters: female black corals experience higher stress under different current velocities - L. Palacios-Castillo; S. Navarro-Mayoral; M. Godefroid; C. García-Herrera; F. Tuya; R. Haroun; F. Otero-Ferrer (Coral Reefs, 2026)
Black coral forests play a vital role in mesophotic and deep-water environments, providing habitat and refuge for numerous organisms. Their presence and distribution are influenced by hydrodynamic conditions. Yet, insight into the effect of current velocity on the survival and overall condition of black corals, and how this may differ between sexes during the reproductive period, is lacking. Here, we investigated how the current velocity affected male and female nubbins of Antipathella wollastoni , throughout a 5-week experiment, under three treatments: no (0 cm s −1 ), low (mean ± SE = 5.3 cm s −1 ± 0.27) and high current (10 cm s −1 ± 0.42). We studied both the nubbin state ( i.e. mortality, tissue necrosis and propagule production) and their physiology ( i.e. total antioxidant capacity, TAC). We found higher tissue necrosis and mortality in the no-current treatment. Responses were significantly sex-conditioned across all treatments. All male nubbins survived the experiment and exhibited minimal tissue necrosis (mean ± SE = 4.72% ± 0.77), whereas 33.3% of female nubbins died and showed significantly higher tissue necrosis (37.05% ± 8.57). Propagule release was up to fourfold higher under high current compared to low, whereas nubbins in the no-current treatment produced almost none, likely due to the rapid onset of necrosis preventing the use of this escape response. The findings emphasize the importance of current velocities to rear black corals under controlled conditions, especially given the increased vulnerability of female nubbins during the reproductive period.

Simultaneous consumption of Liolaemus lizards by the raptor Geranoaetus polyosoma in south-central patagonia - Candela Victorel; Martín C. Castillo; Mauro I. Bonavita; Mauro N. Tammone; Laura M. Casalins; Laura Mangini Mas; Valeria S. Ojeda; Débora L. Moreno Azócar; Marcelo F. Bonino; Félix B. Cruz (acta ethologica, 2026)

Fermentation of rice milling by-products can completely replace soybean meal in the diet of Oreochromis niloticus fingerlings - Mark Henry F. De Leon; Dinah Grace D. Bienes; Mary Jessa Bell B. Pagapulan; Emelyn Joy G. Mameloco; Vyenge Erre D. Gayosa; Fredson H. Huervana; Carmelo S. del Castillo; Rex Ferdinand M. Traifalgar (Frontiers in Marine Science, 2026)
The expansion and intensification of aquaculture have been widely adopted to support large-scale production, creating a reliance on high-protein feed ingredients such as soybean meal (SBM) and fish meal (FM). These ingredients, however, are costly and unsustainable, emphasizing the need for alternative plant-based protein sources for aquafeeds. This study assessed the nutritional and feed value of fermented rice bran meal (FRBM) as a substitute for SBM in the diet of tilapia ( Oreochromis niloticus ) fingerlings. Five diets were formulated with FRBM replacing SBM at 0%, 25%, 50%, 75%, and 100%, and were fed to fingerlings over a 60-day period. Results showed that FRBM could fully replace SBM, with growth-promoting effects particularly observed at 25% replacement. Survival, percentage weight gain, feed conversion ratio (FCR), and specific growth rate (SGR) did not differ significantly among the treatments with varying FRBM levels. No significant differences in carcass composition (protein, lipid, and ash) were observed among tilapia fed with diets containing FRBM replacement. The apparent protein and dry matter digestibility coefficients of FRBM are 91.52% and 66.67%, respectively. Histological examination also revealed no intestinal abnormalities, even at the highest level of FRBM inclusion. Overall, the findings suggest that solid-state fermented rice bran can fully replace soybean meal in the diet of O. niloticus . In addition, its use presents a practical option to help meet the growing protein requirements in aquafeeds and to promote the sustainable expansion of tilapia aquaculture.

Reliable methodologies to determine microplastics in mussels: Enhanced digestion protocols, transference to gold-coated filters and determination via laser-based transflectance infrared spectrometry - Adrián López-Rosales; José M. Andrade; Paula García-Tejedor; M. Estela del Castillo-Busto; Elba Iglesias-Cambón; Soledad Muniategui-Lorenzo (Marine Pollution Bulletin, 2026)

Microbial consortia in mine water bioremediation: principles, design and practical applications - A. Matu; A. Valverde; E. Cason; A. Gomez-Arias; M. Maleke; J. Castillo (Water Research, 2026)

Functional characterization of splice variants in hereditary breast and ovarian cancer susceptibility genes - Laura Rosado-Jiménez; Younes Mestre-Terkemani; Ángeles García-Aliaga; María D. Sarabia-Meseguer; Miguel Marín-Vera; José A. Macías-Cerrolaza; Pilar Sánchez-Henarejos; María R. García-Hernández; Marta Zafra-Poves; Beatriz C. Álvarez-Abril; Carmen B. López-Sánchez; María P. Moya-Martínez; et al. (Familial Cancer, 2025)

Changes to soil phosphorus cycling parameters after long-term treated wastewater irrigation in agroforestry lands of a humid region - Benjamin Castillo; John M. Regan (Journal of Environmental Management, 2025)

Philippine functional foods: A new frontier in noncommunicable diseases prevention - Myra O. Villareal; Lotis E. Mopera; Gladys C. Completo; Ruel C. Nacario; Marissa V. Romero; Katherine Ann T. Castillo-Israel; Rona Camille M. Lizardo-Agustin; Marianne Joy G. Laya; Roi Miguel M. Obdosantos; Christel Leo O. Romano; Jocelyn E. Serrano; Samuel C. Bobiles; et al. (Food and Humanity, 2025)

Repeated Clozapine Administration Causes Extensive Changes to the Expression of Coding and Non-coding RNAs, Including miR-124, in the Mouse Frontal Cortex - Rabha Mussa Younis; Dalia Y. Al Saeedy; Mikhail G. Dozmorov; Fay M. Jahr; Shravani Malay; Sina Mahdiani; Bashir Idris; Joel Castillo; Patrick M. Beardsley; Joseph L. McClay (Molecular Neurobiology, 2025)
Clozapine is arguably the most effective antipsychotic drug for the treatment of schizophrenia, but the mechanisms underlying its efficacy are poorly understood. Therefore, we perform deep RNA sequencing to test for differential transcription and exon use resulting from clozapine’s effects in the mouse frontal cortex, and integrate our findings with known schizophrenia risk genes. We used a dose (4 mg/kg/day, i.p.) and duration (21 days) to approximate clinical exposure, followed by a 24-h washout to determine persistent changes resulting from biological remodeling. We observed significant (FDR < 0.05) differential expression of both mRNAs and long noncoding RNAs (lncRNAs), which were enriched in RNA processing and splicing pathways. Among the most significant lncRNAs, showing 2.3-fold upregulation, was the microRNA 124 host gene ( Mir124a-1hg ), a major source of miR-124, one of the most abundant microRNAs in the brain. Quantitative PCR analysis of the mature microRNAs miR-124-3p and miR-124-5p revealed a significant dose-dependent upregulation of miR-124-3p following 21-day repeated clozapine administration. RNA splicing was also profoundly impacted by clozapine, as revealed by differential exon use analysis, with mouse orthologs of 50 schizophrenia risk genes from the Psychiatric Genomics Consortium among the genes affected. These genes were enriched in “apical dendrite” and “distal axon” ontologies, supporting prior evidence that clozapine may target cortical pyramidal neuron deficits implicated in schizophrenia. Overall, this study demonstrates the profound effect of clozapine on cortical gene expression, affecting abundance of splicing of coding and non-coding transcripts. Future studies are needed to fully characterize our findings as potential preclinical markers of clozapine response.

Effects of domesticated-to-wild gene flow on the genetic structure and diversity of wild papaya (Carica papaya L.) in its Mesoamerican diversity area - Mauricio Heredia-Pech; Jaime Martínez-Castillo; Daniela A. Martínez-Natarén; Pedro Ruiz-Gil; Mónica I. Jiménez-Rojas; Matilde M. Ortiz-García; Mariana Chávez-Pesqueira (Genetica, 2025)

Consideration in vitro of photosynthetically active radiation as a relevant parameter associated with cyanobacteria in a tropical monomictic aquatic system - David Chicalote-Castillo; Pedro Ramírez-García; Víctor M. Luna-Pabello (Aquatic Ecology, 2025)
Studies performed in Valle de Bravo (VB) reservoir in Mexico record the presence of cyanobacteria proliferation and microcystin LR (MC-LR), both from 1998 to 2022, related mainly to two environmental factors; first, nitrates (NO 3 ) and second, temperature. We statistically analyzed data from nine selected works in VB and found that these parameters do not converge seasonally during stratification and mixing. We propose that cyanobacteria, being photoautotrophic organisms, their proliferation and toxin-producing capacity are mainly determined by the amount of photosynthetically active radiation (PAR) rather than NO 3 . We conducted experimental tests to evaluate the toxic wild cyanobacterium, Microcystis aeruginosa , producer of microcystin LR (MC-LR), exposed to 100 µmol photons m −2 s −1 of PAR and three fractions at different descending concentrations of NO 3 . The results of the analyses on data from nine studies showed that cyanobacteria did not proliferate due to the seasonal availability of NO 3 but rather due to temperature. In vitro, we observed that increased PAR had an effect on the growth of M. aeruginosa . The presence of MC-LR was driven by the inverse relationship between PAR and NO 3 . Therefore, we conclude that adding PAR monitoring to studies of tropical monomictic systems would contribute to expanding our understanding of NO 3 and temperature-related effects on the proliferation of cyanobacteria and their toxins.

A New Neotropical Species of Gnathostoma (Nematoda: Gnathostomatidae) from the Northern Four-Eyed Opossum Philander vossi (Marsupialia) - M. Á. Mosqueda-Cabrera; E. Sánchez-Miranda; L. D. Castillo-Loeza; G. Torres-Carrera; L. García-Prieto (Acta Parasitologica, 2025)
Purpose This work provides a detailed morphological description of a previously identified but unnamed lineage inside Gnathostoma spp. from Mexico. Methods Specimens of the four-eyed opossum Philader vossi were collected in Tlacotalpan, Veracruz, Mexico. Specimens were examined morphologically using both light microscopy and scanning electron microscopy. Additionally, we generate DNA sequences for the following loci: mitochondrial cox 1 and nuclear 5.8S rRNA and ITS-2 and 28S rDNA. Results The new species, Gnathostoma mexicanum n. sp., differs from G. turgidum Stossich, 1902, the common gnathostomid species infecting Didelphis spp. from the Americas, in its smaller body size, fewer teeth on the cuticular spines at anterior half of body, as well as site of infection (pyloric region vs. stomach layers). Host specificity further distinguishes the two species. Additionally, molecular data show that the new species clearly diverges from its congeners. Conclusions This work represents the fourth Gnathostoma species described for Mexican mammals and the eight recorded in the Americas.

Admixture Increases Genetic Diversity and Adaptive Potential in Australasian Killer Whales - Isabella M. Reeves; John A. Totterdell; Jonathan Sandoval‐Castillo; Emma L. Betty; Karen A. Stockin; Ramari Oliphant Stewart; Muriel Johnstone; Andrew D. Foote (Molecular Ecology, 2025)
Admixture is the exchange of genetic variation between differentiated demes, resulting in ancestry within a population coalescing in multiple ancestral source populations. Low‐latitude killer whales ( Orcinus orca ) populations typically have higher genetic diversity than those in more densely populated, high productivity and high‐latitude regions. This has been hypothesized to be due to episodic admixture between populations with distinct genetic backgrounds. We test this hypothesis by estimating variation in local ancestry of whole genome sequences from three genetically differentiated, low‐latitude killer whale populations and comparing them to global genetic variation. We find ‘Antarctic‐like’ ancestry tracts in the genomes of southwestern Australia (SWA) population including recent (within the last 2–4 generations) admixture. Admixed individuals had, on average, shorter and fewer runs of homozygosity than unadmixed individuals and increased effective population size ( N e ). Thus, connectivity between demes results in the maintenance of N e of relatively small demes at a level comparable to the sum of N e across demes. A subset of the admixed regions was inferred to be evolving under selection in the SWA population, suggesting that this admixed variation may be contributing to the population's adaptive potential. This study provides important and rare empirical evidence that small populations can maintain genetic diversity due to sporadic admixture between different genetic backgrounds and that admixed ancestry can promote the long‐term stability of N e .

Three Non-Invasive Tests Reveal Anxiety-like Responses During Food Anticipation in Rainbow Trout - André Barany; Miguel Gómez-Boronat; Lisbeth Herrera-Castillo; María J. Delgado; Nuria de Pedro; Ana M. Larrán; Esther Isorna (Fishes, 2025)
Anxiety-like behavior in fish is commonly assessed using non-invasive behavioral paradigms such as the Light/Dark preference, Novel Tank, and Open Field tests. In this study, we validated these three assays in rainbow trout (Oncorhynchus mykiss), a species of commercial relevance, to characterize their anxiety-related responses. To explore behavioral changes associated with feeding anticipation and satiety, we implemented a feeding schedule consisting of two daily meals and conducted behavioral tests at specific times before and after feeding. Trout exhibited clear patterns of scototaxis, geotaxis, and thigmotaxis, consistent with anxiety-like behavior described in other teleosts. Our results showed a significant increase in anxiety-like responses before feeding, coinciding with food anticipatory activity observed prior to expected feeding schedules, which diminished after food intake, as evidenced by each test individually. Moreover, multivariate analysis combining parameters from all three tests improved discrimination between anxious and relaxed fish. The behavioral states before and after feeding resembled anxiety-like and anxiolytic conditions reported in other species, supporting that food anticipatory activity reflects an anxious state in rainbow trout as well. These findings endorse using a multi-test behavioral battery to assess anxiety-like states and provide a framework for studying neurobiological mechanisms of emotional regulation related to feeding in teleosts.

Recovery of strategic elements from mining tailings at La Cienega, Peru, through geochemical and mineralogical assessment: a focus on circular economy policy - Marco A. Cotrina-Teatino; Jairo J. Marquina-Araujo; Jose N. Mamani-Quispe; Jorge Chira-Fernandez; Cesar De la Cruz-Poma; Aldo R. Castillo-Chung; Solio M. Arango-Retamozo; Joe A. González-Vasquez; Salomon M. Ortiz-Quintanilla (Resources Policy, 2025)

Extreme Precipitation Events Associated with Summer Rains in the Western Slope of the Peruvian Andes Using a Numerical Modeling and Weather Radar Data: Case Studies - Aldo S. Moya-Álvarez; Yamina Silva; Elver Villalobos-Puma; Miguel Saavedra-Huanca; Carlos Del Castillo; Shailendra Kumar; Jairo M. Valdivia-Prado (Pure and Applied Geophysics, 2025)

Strategic potential assessment of lanthanum and scandium through geochemical-lithological analysis with unsupervised machine learning in southern Ecuador - Marco A. Cotrina-Teatino; Jairo J. Marquina-Araujo; Jose N. Mamani-Quispe; José A. Guartán; Aldo R. Castillo-Chung; Solio M. Arango-Retamozo; Joe A. González-Vasquez; Salomon M. Ortiz-Quintanilla (Resources Policy, 2025)

Nutrition Assessment in Cyclic Vomiting Syndrome: Exploring the Prevalence of Avoidant/Restrictive Food Intake Disorder, Disordered Eating, and Metabolic Dysregulation - L. Forsthoefel; G. Vanhouwe; O. Khan; K. Heitman; K. Goheen; E. Holley; P. Madril; J. Kennel; R. Jimenez-Castillo; S. Arumugam; M. Vyas; P. Goday; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Microbial diversity and biogeochemical potential related to C and N coupling in the oxygen minimum zone in a warming scenario - Patricia M. Valdespino-Castillo; Andrea Bautista-García; Rocío J. Alcántara-Hernández; Mariel Barjau-Aguilar; Fabio Favoretto; Fermín S. Castillo-Sandoval; Luz Ma. López-Gómez; Andrea P. Guzmán-Arias; Alex González; Nancy Calisto-Ulloa; Hiram Rosales-Nanduca; Anidia Blanco-Jarvio; et al. (Journal of Marine Systems, 2025)

Geochemical and mineralogical characterization of critical elements in gold tailings from the La Cienega, Peru, and assessment of their reuse potential - Marco A. Cotrina-Teatino; Jairo J. Marquina-Araujo; Jose N. Mamani-Quispe; Jorge E. Chira-Fernandez; Aldo R. Castillo-Chung; Solio M. Arango-Retamozo; Joe A. González-Vasquez; Salomon M. Ortiz-Quintanilla (Journal of Environmental Chemical Engineering, 2025)

Long-Term Treatment with Alcaligenes faecalis A12C Improves Host Resistance to Pathogens in Septic Rats: Possible Contribution of Curdlan-Like Immune Trainer - C. J. Martel-Benítez; R. Alayón-Afonso; D. Padilla Castillo; F. J. Chamizo-López; M. Isabel García-Laorden; A. Espinosa de los Monteros y Zayas; J. C. Rivero-Vera; P. Nogueira Salgueiro; F. Real; A. Bordes-Benítez; A. Martel Quintana; C. Almeida Peña; et al. (Probiotics and Antimicrobial Proteins, 2025)
Curdlan, a β-1,3/1,6-glucan found in Alcaligenes faecalis ( A. faecalis ) wall, activates innate and humoral immunity. The aim of this study is to evaluate whether pretreated rats with A. faecalis A12C could prevent sepsis disturbances and identify the immunomodulatory mechanisms involved. Experiments occurred in two stages: a survival study with 16 rats randomly divided into septic (SC) ( n = 8) and septic pretreated (SA) ( n = 8) groups and 45 rats divided into four groups: healthy (AGUSAN) ( n = 9), septic (AGUIC) ( n = 13), septic pretreated (AGUIA) ( n = 14), and healthy pretreated (AGUSTO) ( n = 9). Sepsis was induced by cecal ligation and puncture after 30 days of A. faecalis A12C pretreatment or without. SA group had a higher survival rate of 58% vs. 16% for SC group ( P < 0.05). Overall, AGUIA showed better status than AGUIC ( P < 0.01). Higher monocytosis was found in AGUIA and AGUSTO vs. AGUIC and AGUSAN, respectively ( P < 0.05). A gradual increase in curdlan fecal concentration was observed in AGUIA during pretreatment. Fecal concentrations of Escherichia coli significantly decreased in AGUIA and AGUSTO. Bacterial load in urine, peritoneal lavage fluid (PLF), and bronchoalveolar lavage fluid (BALF) decreased ( P < 0.05) in AGUIA vs. AGUIC. Finally, lower inflammation was observed in serum, BALF, and PLF, with reduced IL-6, IL-10, IL-1β, and TNF-α, along with less damage in lungs and peritoneum in AGUIA vs. AGUIC. These findings suggest the connection between curdlan—produced by A. faecalis A12C—with the immune system and the reduction in severity of experimental sepsis.

Cardiovascular risk of gender-affirming estrogen therapy in a transgender rat model - D. S. Escudero; V. R. Martínez; Y. Pirosanto; G. A. Colareda; M. Pis Diez; J. M. Lofeudo; O. Castillo; J. O. Vélez Rueda; E. L. Portiansky; N. G. Pérez; R. G. Díaz (Journal of Molecular Medicine, 2025)

Adaptive responses to thinning: Growth and sensitivity to hydric and thermal stress in four widely planted pine species - Àngela Manrique-Alba; Santiago Beguería; J. Julio Camarero; Antonio J. Molina; Gonzalo G. Barberá; Juan A. Blanco; Antonio M. Cachinero-Vivar; Víctor M. Castillo; Antonio D. del Campo; Álvaro Hernández; J. Bosco Imbert; María N. Jiménez; et al. (Agricultural and Forest Meteorology, 2025)

Safety and pharmacodynamics of intranasal recombinant human interferon alpha-2b as antiviral prophylaxis: A phase I-II clinical trial (OLIVO study) - Francisco Hernández-Bernal; Dania Vázquez-Blomquist; Joel M. Quintana-Guerra; Lídice Josué-Díaz; Klaudia Urrutia-Pérez; Karen Urrutia-Pérez; José L. Rodríguez-Reinoso; Jorge C. Castillo-Miranda; Maritza Pacheco-Rodríguez; Iris Valdés-Prado; Marel Alonso-Valdés; Hugo Nodarse-Cuní; et al. (Next Research, 2025)

Chitosan-based materials for food preservation: Enhancing shelf life and safety through sustainable nanoparticles and films - Tarsila Tuesta; Angie Castillo-Barzola; Henry Linares; Gustavo Ruiz-Pacco; Angélica M. Baena-Moncada; A.C. Valderrama-Negrón (Food Chemistry, 2025)

Hydrological seasonality is a major driver of ecosystem metabolism in tropical nonwadeable rivers - María M. Castillo; Amber J. Ulseth; Aarón Jarquín‐Sánchez; Arturo Álvarez‐Merino; Krista A. Capps (Limnology and Oceanography, 2025)
Studies of annual patterns of ecosystem metabolism in rivers have primarily been conducted in temperate ecosystems, and little is known about metabolic regimes of tropical rivers. We estimated ecosystem metabolism in four nonwadeable rivers in southern México that varied in size and the extent of human disturbance. The smaller rivers with limited human disturbance showed reduced gross primary production (GPP; 1.0 and 1.7 g O 2 m −2 d −1 ), ecosystem respiration (ER; − 1.9 g O 2 m −2 d −1 ), and net ecosystem production (NEP) approaching autotrophy (− 0. 8 and − 0.3 g O 2 m −2 d −1 ) relative to rivers draining larger, more disturbed catchments (GPP, 1.2 and 2.7 g O 2 m −2 d −1 ; ER, − 5.7 and − 6.9 g O 2 m −2 d −1 ; NEP, − 3.8 and − 3.7 g O 2 m −2 d −1 ). In all rivers, GPP and ER varied seasonally with discharge. The smaller rivers exhibited a distinct pattern of greater and sustained GPP during periods of low discharge, a seasonal metabolic regime we describe as “flow decline.” In general, process–discharge relationships exhibited thresholds, with an initial decline in GPP and ER, with increasing discharge and an increase in ER at higher flows. Relative to larger and more disturbed watersheds, smaller rivers showed a more constrained metabolic fingerprint. Annual NEP (− 1033 and − 641 g C m −2 yr −1 ) in the larger rivers was more negative than the global average, supporting evidence from other studies that tropical rivers are greater contributors to CO 2 emissions than temperate ecosystems. Our study indicates that hydrological seasonality is a major driver of metabolism in tropical rivers.

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Fault interactions and subsurface deformation in the Mexicali Valley: Implications for seismic hazard assessment at the México-USA border - Cristian A. Gallegos-Castillo; Mario González-Escobar; Jaime A. Reyes-López; Joann M. Stock; Sergio M. Arregui-Ojeda; Carlos Simón Reyes-Martínez; Edgar A. Mastache-Román (Tectonophysics, 2025)

Source apportionment of PM10 particles in the urban atmosphere using PMF and LPO-XGBoost - Ying Liu; Bowen Jin; Xun Zhang; Xiansheng Liu; Tao Wang; Vy Ngoc Thuy Dinh; Jean-Luc Jaffrezo; Gaëlle Uzu; Pamela Dominutti; Sophie Darfeuil; Olivier Favez; Sébastien Conil; et al. (Environmental Research, 2025)

Productivity and nutritional quality of pastures in a silvopastoral system under two harvest intervals in southeastern Mexico - Benito B. Dzib-Castillo; Fernando Casanova-Lugo; Dixan Pozo-Leyva; Ricardo L. D. Costa; Laura Macario-González; Flavia M. A. Gimenes; Luis A. Lara-Pérez; Alfonso J. Chay-Canul (Agroforestry Systems, 2025)

Chronic arsenic exposure of ovarian surface and fallopian tube cultures induces giant and/or multinucleated cells with phagocytosis-like properties and an inflammatory phenotype - Cristina M. Andrade-Feraud; Arlet M. Acanda de la Rocha; Noah E. Berlow; Santiago Duque; Alexander Velazco; Diego Castillo; Baylee Holcomb; Ebony R. Coats; Yasmin R. Ghurani; Catherine M. Lucey; Brandon Pearson; Tomás R. Guilarte; et al. (Toxicology and Applied Pharmacology, 2025)

Canine eosinophilic pulmonary granulomatosis: Clinical-pathological diagnosis and physiopathology theories - L.X. Bravo-Coello; E. Carrillo-Castillo; A. Cervantes-Arias; M. Juárez-Ramírez; G. Valero-Elizondo (Journal of Comparative Pathology, 2025)

A study on the dynamic response of the double pantograph interaction with rigid catenary - M. Simarro; S. Postigo; P. Reyes; R.J. Luque; P.V. Baćić; J.J. Castillo (Engineering Structures, 2025)

Are leaf anatomical traits strong predictors of litter decomposability? Evidence from upper Andean tropical species along a forest successional gradient - Dennis Castillo-Figueroa; Juan M. Posada (Oecologia, 2025)
Litter decomposability has been linked to "soft" traits of green leaves, but relationships with "hard" traits associated with leaf anatomy remain unexplored. Examining anatomical traits within the leaf economic spectrum may enhance our understanding of litter decomposability. In this study, we analyzed the relationships between leaf anatomical traits and decomposability at both species and community levels along a successional gradient of upper Andean tropical forests in Colombia. We conducted a reciprocal translocation field experiment with 15 upper Andean species in 14 permanent plots around Bogotá, collecting 2520 litterbags at four times (3, 6, 12, 18 months). Using a multiple regression model based on foliar traits, we estimated decomposability for the remaining 48 species that compose the plant community (63 species in total) in the studied successional gradient. We measured several leaf anatomical traits in all 63 species and calculated community-weighted means and functional diversity indices with the most effective anatomical predictors of decomposability. We found that thicker cuticles, larger vascular bundles, higher spongy mesophyll proportion, and lower palisade mesophyll proportion are related to low decomposability. Plant communities with thicker protective structures slow down decay rates, while large palisade tissues with cylindrical cells increase litter breakdown. Decomposability did not change along succession due to the balance between high functional evenness in secondary forests and high functional richness in mature forests. Despite potential circularity and interdependence between functional diversity metrics, our study provides novel insights into the anatomical basis of decomposability and community dynamics in successional gradients of upper Andean tropical forests.

Unraveling spatio-temporal patterns of taxonomic, functional, and phylogenetic β-diversity of temperate ant communities after habitat simplification - G. Pérez-Toledo; M. Cuautle; C. Castillo-Guevara; J. G. Miguelena (Biodiversity and Conservation, 2025)

Parthenogenesis in the neotropical katydid Conocephalus ictus - Tzitzi M. Placier-Gallardo; Hugo J. Amaro-Lozada; Raúl Cueva del Castillo (Journal of Insect Physiology, 2025)

Lack of cold temperatures is driving recent high-summer warming in the southern Rocky Mountains - M. C. A. Torbenson; E. Martinez del Castillo; F. Reinig; D. W. Stahle; K. E. King; J. T. Maxwell; G. L. Harley; E. Ziaco; J. Esper (International Journal of Biometeorology, 2025)
We present a 483-year-long tree-ring chronology from a high-elevation Engelmann spruce stand in central Colorado. Over 800,000 density measurements produce a maximum latewood density (MXD) record, which together with tree-ring widths, is used to assess the climatic influences on radial tree growth. Variability in MXD is strongly related to local and regional August maximum temperatures (T max ) for 127 years of overlapping instrumental climate data. A single-predictor reconstruction based on the MXD record explains > 50% of the variance in regional August T max is presented and considered robust for the period 1662–2021. The estimates of past temperature variability display phases of continuous cold conditions that are beyond the range of the instrumental record, including the 1830s. Our results further indicate that August T max have been higher since the early 1990s than for any other 30-year period in the past 350 years. This recent increase occurs on top of multi-centennial warming, and appears to be driven mainly by less frequent cold summers rather than an increase in warm extremes.

Cytomegalovirus Infection Affects the Differentiation and Determines the Functionality of a Human Progenitor Neural Cell Line - H. M. González-Sánchez; E. I. Rubio Hernández; A. S. Silva-Ramírez; A. Miranda-López; A. E. Monsiváis-Urenda; M. Comas-García; D. E. Noyola; V. M. Rodríguez; C. G. Castillo (Current Microbiology, 2025)

Rewilding shows differential fitness of sympatric Physella acuta (Draparnaud, 1805) snail lineages - Kevin A. McQuirk; Juliana M. DeCore; Maria G. Castillo; Coen M. Adema (Aquatic Ecology, 2025)

Latitudinal propagation and solar wind drivers of Pc5 pulsations during the June 2015 geomagnetic storm - J. A. Lazzús; I. Salfate; M. N. Castillo; J. Lorca-Castillo; C. Olivares-Salazar; A. Rivera-Zepeda (Acta Geodaetica et Geophysica, 2025)

Arbuscular mycorrhizal fungi and edaphic factors modulate flowering and fruiting of secondary vegetation species in a temperate forest - Yasmin Vázquez-Santos; Silvia Castillo-Argüero; Noé M. Montaño; Francisco Javier Espinosa-García; Silvia Margarita Carrillo-Saucedo; Yuriana Martínez-Orea; Ernesto V. Vega-Peña (Brazilian Journal of Botany, 2025)
Arbuscular mycorrhizal (AM) fungi enhance plant flowering and fruiting by improving nutrient and water uptake. The aim of this study was to evaluate how AM fungal colonization percentage and edaphic factors, modulate flowering and fruiting in secondary vegetation (SV) species with different biological traits, in a temperate forest. We conducted the research in four sites at two elevation intervals in a temperate forest in Mexico, focusing on three SV species. We recorded flower, fruit and AM fungal colonization percentages during the rainy and the dry season. Soil was collected from the rhizosphere of each SV species to determine organic matter (OM), pH, relative soil moisture (RSM), available phosphorus (Ava-P) and nitrogen (Ava-N). The AM fungal colonization, flower and fruit percentages showed interspecific and temporal variations. Structural equation models showed that flowering was positively influenced by RSM in Acaena elongata and negatively influenced by AN in Solanum pubigerum . Fruiting was positively influenced by AM fungal colonization and negatively by AP in A. elongata , with a relevant indirect effect of OM. In S. pubigerum , the effect of AM fungal colonization was slightly positive, while AN and pH had a greater effect on fruiting. While in Ageratina glabrata the effect of AM fungal colonization on fructification was not evident. The study highlights the critical role of AM fungal colonization and soil properties such as OM, pH and N in flower and fruit production, which depend on the biological traits of the host plant species.

Simultaneous electricity generation and low-energy-intensive water desalination using a hydraulic wind turbine - Helber Antonio Esquivel-Puentes; Andrea Vacca; Leonardo P. Chamorro; Jose Garcia-Bravo; David M. Warsinger; Luciano Castillo (Desalination, 2025)

Ecophysiological and biochemical responses to cold and heat waves of native Spartina maritima, alien S. densiflora and their reciprocal hybrids - Rosario Álvarez; Salvador A. Fernandez-Gonzalez; Adrián Perera-Bonaño; Alfonso De Cires; Jesús M. Castillo; Blanca Gallego-Tévar (Planta, 2025)
Main conclusion Spartina hybrids outperform parental species, showing transgressive acclimation to extreme climates. Native S. maritima demonstrates high seasonal adaptability and invasive S. densiflora low physiological impact, suggesting resilience under climate change. Abstract Extreme climatic events, such as cold and heat waves, are becoming more frequent, intense, and prolonged due to climate change. Simultaneously, invasive alien plant species are altering the composition of plant communities. Both climate change and the introduction of alien species pose significant threats to biodiversity. We studied the responses of 25 biochemical and physiological functional traits for native Spartina maritima , alien invasive S. densiflora and their reciprocal hybrids to changing environmental conditions during a cold snap in winter and a heat wave in summer in Guadiana Marshes (Southwest Iberian Peninsula). These four closely related taxa responded differently to seasonal environmental fluctuations. Both hybrid taxa, particularly S. maritima × densiflora , exhibited transgressive responses, allowing them to display a wider range of acclimation responses to air temperature compared to their parental species. Native S. maritima also demonstrated a relatively high acclimation capacity to seasonal meteorological changes. In contrast, alien S. densiflora presented few acclimation responses to seasonal environmental changes, responding primarily to sediment salinity rather than to air temperature. Even so, all four studied Spartina taxa appear to be well-adapted to the occurrence of cold and heat waves in the Gulf of Cadiz. These findings underscore the complexity of plant acclimation strategies in response to extreme climatic events and highlight the potential for hybrid taxa to face the future dynamics of salt marshes under climate change.

Using a vibrating microtome to prepare Mentha × piperita shoot tip sections for live-tissue microscopy experiments - Heidi D. Kreckel; Albert Ochoa-Castillo; Stephanie Villanueva; Gayle M. Volk; Nancy E. Levinger (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Structural and functional dynamics of coralline algal systems under warming scenarios: Insights into vulnerability, and resilience - Andrea Bautista-García; Patricia M. Valdespino-Castillo; Teresa Pi-Puig; Fabio Favoretto; Martín Merino-Ibarra; Javier A. Ceja-Navarro; Silvia Espinosa-Matías; Javier Tadeo León; Anidia Blanco-Jarvio (Aquatic Botany, 2025)

Safety Outcomes of Antiplatelet Therapy During Endovascular Treatment of Tandem Lesions in Acute Ischemic Stroke Patients - Mudassir Farooqui; Afshin A. Divani; Milagros Galecio-Castillo; Ameer E. Hassan; Mouhammad A. Jumaa; Marc Ribo; Michael Abraham; Nils Petersen; Johanna Fifi; Waldo R. Guerrero; Amer M. Malik; James E. Siegler; et al. (Translational Stroke Research, 2025)

Six decades of global coral bleaching monitoring: a review of methods and call for enhanced standardization and coordination - Andrea Rivera-Sosa; Aarón Israel Muñiz-Castillo; Ben Charo; Gregory P. Asner; Chris M. Roelfsema; Simon D. Donner; Brianna D. Bambic; Ana Gabriela Bonelli; Morgan Pomeroy; Derek Manzello; Paulina Martin; Helen E. Fox (Frontiers in Marine Science, 2025)
Coral bleaching poses a severe threat to the health and survival of global coral reef ecosystems, with recent events surpassing historical heat stress records. To address this crisis, improved long-term monitoring, communication, and coordination are urgently required to enhance conservation, management, and policy responses. This study reviews global coral bleaching survey methodologies and datasets spanning 1963 to 2022, identifying key challenges in methodological standardization, including database duplication and inconsistencies in naming and reporting bleaching metrics. These issues hinder comparative analyses and contribute to discrepancies in global bleaching impact assessments. We developed a typology of twenty-nine coral bleaching methods used across various scales, encompassing remote sensing tools, underwater surveys, and specimen collection. Analysis of 77,370 observations from three major datasets revealed that 9.36% of entries lacked methodological descriptions. Among recorded methods, belt transects (42%), line and point intercept transects (33%), and random surveys (17%) were the most widely applied. Practitioner surveys underscored the dominance of in situ transect and visual methods, highlighting the growing adoption of photo quadrats—an emerging yet underrepresented technique in existing datasets. To enhance global coral bleaching assessments, we propose a standardized framework that ensures open access and accessible data that aligns with decision-makers’ needs for efficient data aggregation and interoperability to better understand temporal and spatial bleaching events. A globally coordinated coalition should unify protocols, improve data-sharing capabilities, and empower regional networks through targeted training, incentives, and open communication channels. Strengthening field capacity in coral taxonomy and standardized survey methodologies, alongside integrating advanced tools, will improve data quality and comparability. Additionally, creating precise geolocated datasets will bridge on-the-ground observations with advanced remote sensing systems, refining the accuracy of satellite-based early warning tools. Establishing interoperable online platforms will further streamline data integration and accessibility, providing a robust foundation to support global responses to coral bleaching and foster impactful conservation initiatives.

Drivers of soil fauna communities along a successional gradient in upper andean tropical forests - Camilo Castillo-Avila; Dennis Castillo-Figueroa; Juan M. Posada (Soil Biology and Biochemistry, 2025)

Unraveling the lab-scaling up production of activated carbon from plastic-enriched waste - Ledicia Pereira; Gabriel Blázquez; Ventura Castillo; Francisco Miguel González-Pernas; María González-Lucas; M. Ángeles Martín-Lara; Mónica Calero; Rafael R. Solís (Journal of Cleaner Production, 2025)

Characterization of Surface and Bottom Longline Artisanal Shark Fisheries in the Northern Gulf of Tehuantepec, Mexico - Cristina Celaya-Castillo; Emilio I. Romero-Berny; Felipe Galván-Magaña; Jesús M. López-Vila; Wilfredo A. Matamoros (Thalassas: An International Journal of Marine Sciences, 2025)

Basin Style Variation Along a Transform Fault: Southern Colorado River Delta, Baja California, México - Mario González-Escobar; Carlos Simón Reyes-Martínez; Cristian A. Gallegos-Castillo; Sergio M. Arregui-Ojeda; Edgar A. Mastache-Román (Pure and Applied Geophysics, 2025)

How Old Is the Presence of the Canary Pine Forests in the Canary Islands? - C. A. Góis‐Marques; E. Martín‐González; J. M. Postigo‐Mijarra; M. C. Velasco‐Flores; C. Castillo Ruiz; M. Menezes de Sequeira (Journal of Biogeography, 2025)
Aim The Neogene fossil record of Pinus canariensis C.Sm ex DC. suggests a wider past distribution in Europe, but due to extirpation by past climatic events, today this taxon is restricted to the Canary Islands. Remarkably, the putative oldest P. canariensis fossil for the Canary Islands, found in Gran Canaria is 13.3–13.0 Ma. This palaeobiogeographical information has been cited as proof of the deep‐time presence of conifers, the genus Pinus L., P. canariensis and the pine forest ecosystems in the Canary Islands, but also to justify the long‐term evolution of P. canariensis within an active insular volcanic environment. Here we present a re‐evaluation of the oldest Pinus fossil from the Canary Island. Location Gran Canaria, Canary Islands, Spain. Taxon Pinus canariensis C.Sm ex DC. Methods We compiled a citation record for the mentions of the ‘bark fossil’ and conducted a review of the specimen. We compared it with extant P. canariensis and with pyroclasts. Results The analysis of the specimen demonstrates that it lacks morphological or anatomical characters to identify as a bark or even as a plant fossil. The specimen is best interpreted as a lapilli‐sized tube pumice, highly altered by mineral deposition promoted by the percolating hydrothermal water. Main Conclusions The oldest reliable Pinus fossils from the Canary Islands are 3.9–3.1 Ma and ca. 9 to 10 Ma younger than previously claimed. When did Pinus arrive at the Canary Islands is unknown, but this biogeographical question can be approached via focused volcano‐stratigraphical and palaeobotanical research in this Archipelago.

Effect of melanization of entomopathogenic nematodes on the potential of Steinernema feltiae and Heterorhabditis bacteriophora for the control of Aedes albopictus and Aedes aegypti - Uvaldo M. Velázquez-Pablos; Alfredo Castillo-Vera; Juan Cisneros; Francisco Solis-Santoyo (BioControl, 2025)

Unveiling Macroecological Patterns of Elasmobranchs in the Eastern Pacific Ocean - Andrés F. Navia; Joanna Alfaro‐Shigueto; Jose Ágreda‐Arango; Elisa Areano; Cristopher Avalos‐Castillo; Joseph J. Bizzarro; Carlos Bustamante; Adriana Cevallos; Francisco J. Concha; Víctor H. Cruz‐Escalona; David A. Ebert; Mario Espinoza; et al. (Journal of Biogeography, 2025)
Aim To examine the species richness, distribution and macroecological patterns of elasmobranch assemblages across a broad latitudinal gradient in the Eastern Pacific Ocean (EPO). Location The study area encompasses the Pacific coast of the American continent, spanning from 65°N to 60°S, and extending from the coastline to approximately 1000 km offshore, encompassing the oceanic archipelagos. Taxon Elasmobranchs. Methods Utilising the established distribution ranges of 190 elasmobranch species (comprising 89 sharks and 101 rays), we assessed the richness and spatial distribution of these species across the EPO. Subsequently, three macroecological patterns were scrutinised: Rapoport's rule, the Mid Domain Effect with its association to Mean Sea Surface Temperature, and the correlation between body size and latitudinal distribution. Results The analysis of species richness along latitudinal gradients unveiled a bimodal pattern, reaching peaks between 30° to 20°N and 10°N to 5°S. A decline in species richness was observed from tropical to polar regions. Contrary to Rapoport's Rule, Stevens' and midpoint methods demonstrated higher geographic range values at lower latitudes, diminishing towards higher latitudes. Additionally, the mid‐domain effect model exhibited a robust correlation with the mean sea surface temperature. Exploring the interspecific relationship between body size and extent of occurrence, it was found that 29 out of 190 species are more susceptible to extinction. Main Conclusion Marine elasmobranchs of the EPO defy conventional latitudinal richness patterns and deviate from Rapoport's rule. Furthermore, our findings indicate a robust correlation between observed richness and both sea surface temperature and environmental heterogeneity. The proportion of species vulnerable to human or stochastic impacts potentially leading to extirpation in relation to their geographic range was low across the majority of examined provinces.

Shortfalls in the protection of Important Shark and Ray Areas undermine shark conservation efforts in the Central and South American Pacific - Théophile L. Mouton; Adriana Gonzalez-Pestana; Christoph A. Rohner; Ryan Charles; Emiliano García-Rodríguez; Peter M. Kyne; Amanda Batlle-Morera; Giuseppe Notarbartolo di Sciara; Asia O. Armstrong; Enzo Acuña; Joanna Alfaro-Shigueto; Randall Arauz; et al. (Marine Policy, 2025)

Delineating distinct sediment pollution signatures from diverse sources in a heavily contaminated estuary near an area of high cancer and cardiovascular mortality - Manuel Contreras-Llanes; Vanessa Santos-Sánchez; Juan Alguacil; Jesús M. Castillo (Science of The Total Environment, 2024)

A holistic simulation model of solid-set sprinkler irrigation systems for precision irrigation - M. Morcillo; J. F. Ortega; R. Ballesteros; A. del Castillo; M. A. Moreno (Precision Agriculture, 2024)

Metal (loid) Exposure and Overweight and Obesity in 6–12-Year-Old Spanish Children - Inmaculada Salcedo-Bellido; Helga Castillo Bueno; Pablo Olmedo; Fernando Gil; Francisco M. Ocaña-Peinado; Lourdes Rodrigo; Ana Rivas (Exposure and Health, 2024)
Epidemiological studies focusing on metal(oid) exposure and excess body weight among children show inconsistent results and the influence of metal(loid) mixtures has been little studied. We aimed to explore the effect of 10 metal(loid)s, individually and in combinations, on overweight and obesity among children aged 6–12. Urinary levels of these metal(oid)s from 92 controls and 51 cases with overweight and obesity were analyzed. Metal(loid) levels were log-transformed and categorized into tertiles according to the control group cutoff points. Two logistic regression models and weighted quantile sum regressions (WQS) were run: model 1 adjusting for age, sex, creatinine, energy intake and physical activity and model 2 additionally adjusting for maternal education, rice and fish consumption. In the single metal(oid) exposure model, there was a trend of significant negative association for urinary cobalt (Co), where children in the third tertile had lower odds of present overweight and obesity than those in the first (Odds Ratio, OR = 0.43; 95% Confidence Interval, CI = 0.20–0.93). Urinary chromium (Cr) levels were borderline-significant negatively associated with overweight and obesity (ORa = 1.70; 95% CI = 0.97–2.98). Molybdemun, Cr and Co had a major contribution to the inverse association between metal(loid) mixture and overweight and obesity as well as lead, cadmium and total arsenic in the positive relationship. Our findings in this explorative study suggested an inverse association of high urinary Co levels with overweight and obesity. Moreover, metal(loid) mixture exposure may have influence on overweight and obesity with an important contribution of Co in the potential negative effect.

Correction: DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew Dewoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)

DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew DeWoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)
Genetic diversity is essential for maintaining healthy populations and ecosystems. Several approaches have recently been developed to evaluate population genetic trends without necessarily collecting new genetic data. Such “genetic diversity indicators” enable rapid, large-scale evaluation across dozens to thousands of species. Empirical genetic studies, when available, provide detailed information that is important for management, such as estimates of gene flow, inbreeding, genetic erosion and adaptation. In this article, we argue that the development and advancement of genetic diversity indicators is a complementary approach to genetic studies in conservation biology, but not a substitute. Genetic diversity indicators and empirical genetic data can provide different information for conserving genetic diversity. Genetic diversity indicators enable affordable tracking, reporting, prioritization and communication, although, being proxies, do not provide comprehensive evaluation of the genetic status of a species. Conversely, genetic methods offer detailed analysis of the genetic status of a given species or population, although they remain challenging to implement for most species globally, given current capacity and resourcing. We conclude that indicators and genetic studies are both important for genetic conservation actions and recommend they be used in combination for conserving and monitoring genetic diversity.

Genomic Vulnerability to Climate Change of an Australian Migratory Freshwater Fish, the Golden Perch ( Macquaria ambigua ) - Emily J. Booth; Chris J. Brauer; Jonathan Sandoval‐Castillo; Katherine Harrisson; Meaghan L. Rourke; Catherine R.M. Attard; Dean M. Gilligan; Zeb Tonkin; Jason D. Thiem; Peter J. Unmack; Brenton Zampatti; Luciano B. Beheregaray (Molecular Ecology, 2024)
Genomic vulnerability is a measure of how much evolutionary change is required for a population to maintain optimal genotype‐environment associations under projected climates. Aquatic species, and in particular migratory ectotherms, are largely underrepresented in studies of genomic vulnerability. Such species might be well equipped for tracking suitable habitat and spreading diversity that could promote adaptation to future climates. We characterised range‐wide genomic diversity and genomic vulnerability in the migratory and fisheries‐important golden perch ( Macquaria ambigua ) from Australia's expansive Murray–Darling Basin (MDB). The MDB has a steep hydroclimatic gradient and is one of the world's most variable regions in terms of climate and streamflow. Golden perch are threatened by fragmentation and obstruction of waterways, alteration of flow regimes, and a progressively hotter and drying climate. We gathered a genomic dataset of 1049 individuals from 186 MDB localities. Despite high range‐wide gene flow, golden perch in the warmer, northern catchments had higher predicted vulnerability than those in the cooler, southern catchments. A new cross‐validation approach showed that these predictions were insensitive to the exclusion of individual catchments. The results raise concern for populations at warm range edges, which may already be close to their thermal limits. However, a population with functional variants beneficial for climate adaptation found in the most arid and hydrologically variable catchment was predicted to be less vulnerable. Native fish management plans, such as captive breeding and stocking, should consider spatial variation in genomic vulnerability to improve conservation outcomes under climate change, even for dispersive species with high connectivity.

Interactive impact of residual pyrethroid compounds used in the Chilean salmon farming industry and coastal acidification conditions on the feeding performance of farmed mussels in northern Patagonia - Adonis Conejeros; Valeska A. San Martin; Nicole Castillo; L. Antonio Cuevas; Karen Garcés; Ricardo O. Barra; Victor M. Aguilera; Cristian A. Vargas (Marine Environmental Research, 2024)

PM10-bound trace elements in pan-European urban atmosphere - Xiansheng Liu; Xun Zhang; Tao Wang; Bowen Jin; Lijie Wu; Rosa Lara; Marta Monge; Cristina Reche; Jean-Luc Jaffrezo; Gaelle Uzu; Pamela Dominutti; Sophie Darfeuil; et al. (Environmental Research, 2024)

Impact of coagulation characteristics on the aggregation of microplastics in upper-ocean turbulence - F. Pizzi; M. Rahmani; C. Romera-Castillo; F. Peters; J. Grau; F. Capuano; L. Jofre (Advances in Water Resources, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Superhydrophobic coatings reduce human bacterial foodborne pathogen attachment to woods used in fresh produce harvest and postharvest packing - Zachariah Vice; William de Florio; Joseph Masabni; Luis Cisneros-Zevallos; Alejandro Castillo; Chris R. Kerth; Mustafa Akbulut; Thomas M. Taylor (Food Microbiology, 2024)

Recruitment niche segregation of halophytes along the tidal gradient - Adolfo F. Muñoz-Rodríguez; María D. Infante-Izquierdo; Alejandro Polo-Ávila; Virgilio Hermoso-López; Francisco J.J. Nieva; Blanca Gallego-Tévar; Jesús M. Castillo (Estuarine, Coastal and Shelf Science, 2024)

Biodiversity of octopuses in the Americas - Roberto González-Gómez; Otilio Avendaño; Irene de los Angeles Barriga-Sosa; Penélope Bastos; Claudia Caamal-Monsreal; Gabriela Castillo-Estrada; Celso Cedillo-Robles; Adam Daw; Mariana Díaz-Santana-Iturrios; Gabriela Galindo-Cortes; Jürgen Guerrero-Kommritz; Manuel Haimovici; et al. (Marine Biology, 2024)

Exploring epipelic diatom species composition across wetlands conductivity gradients in southern Spain - David Fernández-Moreno; Cristina Delgado; Lorena González-Paz; Saúl Blanco; Pedro M. Sánchez-Castillo; Carmen Pérez-Martínez (Hydrobiologia, 2024)
The objective of this study was to explore the environmental factors having the greatest influence on the distribution and abundance of epipelic diatom species in different wetlands in southern Spain. We previously defined four groups of conductivity categories: fresh (< 0.8 mS cm −1 ), oligosaline (< 8 mS cm −1 ), mesosaline (8–30 mS cm −1 ) and eusaline (> 30 mS cm −1 ). A dbRDA analysis performed on a subset of 36 of the 53 wetlands, using a total of 25 environmental variables, showed that five environmental variables (conductivity, pH, wetland area, silicates, and total suspended solids) were the best explanatory variables for the diatom assemblage, with conductivity being the main explanatory variable. Nonmetric multidimensional scaling (nMDS) analysis performed on the set of 53 wetlands revealed significant differences in diatom composition among the four conductivity groups. The key species in the eusaline group were Tryblionella pararostrata , Halamphora sp.1 and Cocconeis euglypta , whereas in the mesosaline and oligosaline group, these were Navicula veneta , Tryblionella hungarica and Nitzschia inconspicua . Finally, in the fresh group dominated Achnanthidium minutissimum , Navicula veneta and Gomphonema exilissimum . This study on epipelic diatoms can therefore contribute to the knowledge of these organisms in a European region with a high diversity of wetland typologies.

Does the diversity of vegetation and diatoms correlate with soil and water factors in a tropical cloud forest’s complex land use/land cover scenario? - Gabriela Vázquez; José G. García-Franco; Gonzalo Castillo-Campos; M. Luisa Martínez; Klaus Mehltreter; Adolfo Campos; Mario E. Favila (Environmental Monitoring and Assessment, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

P26-01 Hexagonal boron nitride (hBN) and hBN-reinforced thermoplastic polyurethane composite: an in vitro hazard characterization using human skin and lung cells - M. Carlin; J. Kaur; D.Z. Ciobanu; Z. Song; M. Olsson; T. Totu; G. Gupta; G. Peng; V. Jehová González; I.J. Janica; V. Fuster Pozo; S. Chortarea; et al. (Toxicology Letters, 2024)

P18-09 Quantitative analysis of micro and nanoplastics in biological tissues: implications for environmental and human health - M. Garcia; A. Nihart; R. Liu; E. El Hayek; E. Castillo; B. Bleske; E. Barrozo; M.A. Suter; J. Scott; K. Forsythe; N. Adolfi; D. Gallego Umana; et al. (Toxicology Letters, 2024)

Adsorption of amine surfactants onto kaolinite: A multiscale investigation - J. Lainé; Y. Foucaud; J.W. Hounfodji; P. Pelée de Saint-Maurice; A. Bonilla-Petriciolet; D.I. Mendoza-Castillo; H. Turrer; M. Badawi (Minerals Engineering, 2024)

Diversity and structure of prokaryotic assemblages in a thermally stratified tropical lake - Jesús Torres-Huesca; Jazmín Santillán; Yislem Beltrán; Rafael A. López-Martínez; Miroslav Macek; Luisa I. Falcón; Martín Merino-Ibarra; Patricia M. Valdespino-Castillo; Jesús T. Martínez-Díaz; Javier Alcocer; Rocío J. Alcántara-Hernández (Limnologica, 2024)

Identifying pathways of pharmaceutical exposure in a mesoconsumer marine fish - N.A. Castillo; W.R. James; R.O. Santos; R. Rezek; D. Cerveny; R.E. Boucek; A.J. Adams; S. Trabelsi; A. Distrubell; M. Sandquist; J. Fick; T. Brodin; et al. (Journal of Hazardous Materials, 2024)

Genetic and phenotypic differentiation in functional traits of Iris pseudacorus L. in native and introduced Mediterranean climate ranges - B. Gallego-Tévar; B. J. Grewell; J. F. Gaskin; J. M. Castillo (Biological Invasions, 2024)
Intraspecific variation in functional traits between native and introduced plant species may underlie resilience and invasiveness of introduced species. We explored if observed phenotypic variation of Iris pseudacorus L. between populations in the native vs. introduced ranges results from genetic differentiation and/or phenotypic plasticity. Seeds were collected from populations along estuarine stress gradients within populations in both Guadalquivir Estuary (Andalusia, Spain) and San Francisco Bay-Delta Estuary (California, USA). Genetic analysis was performed on leaf tissue from plants in each seed donor population. Germinants (n = 48: 6 plants × 4 populations × 2 ranges) were grown for 12 months in a common garden experiment (CGE). We then evaluated 25 traits including growth, biomass allocation, morphological and biochemical responses. Geographic range explained relative intraspecific trait variation segregating native from introduced phenotypes. Native plants had lower specific leaf area (− 34%) and carbohydrate concentrations in rhizomes (− 63%) than introduced plants, providing evidence of genetic differentiation. Higher genetic diversity and 27% higher phenotypic variation (CGE) of native vs. introduced plants indicated longer-term adaptive processes in the native range. Genetic distance of introduced populations (field) increased along with their phenotypic distance (CGE), suggesting rapid genetic differentiation. Phenotypic plasticity also explained some observed inter-range differences under field conditions not expressed by plants in the CGE. Management of the introduced I. pseudacorus populations should be established urgently since they represent novel genotypes with key functional traits that can support invasiveness through increased competitive ability and physiological stress tolerances to sea level rise.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Exploring proteasome inhibition using atomic weighted vector indices and machine learning approaches - Yoan Martínez-López; Juan A. Castillo-Garit; Gerardo M. Casanola-Martin; Bakhtiyor Rasulev; Ansel Y. Rodríguez-Gonzalez; Oscar Martínez-Santiago; Stephen J. Barigye (Molecular Diversity, 2024)

Genetic (co)variation for resistance to white spot syndrome virus, acute hepatopancreatic necrosis, and overall pond survival in Litopenaeus vannamei - Reyes López-Ordaz; Alejandra Caballero-Zamora; José M. Yáñez; Leobardo Montoya-Rodríguez; Bruno Gómez-Gil; Sonia A. Soto Rodríguez; Alfonso Martínez Ortega; Juan C. Quintana-Casares; Héctor Castillo-Juárez; Gabriel R. Campos-Montes (Aquaculture International, 2024)

Influence of human emotions on conservation attitudes toward relevant wildlife species in El Triunfo Biosphere Reserve, Mexico - Nathalia M. Castillo-Huitrón; Eduardo J. Naranjo; Dídac Santos-Fita; Mateo Peñaherrera-Aguirre; Pavol Prokop; Rodrigo Cisneros; Silvia Vaca Gallegos; Zuzana Ježová (Biodiversity and Conservation, 2024)

Multinational evaluation of genetic diversity indicators for the Kunming‐Montreal Global Biodiversity Framework - Alicia Mastretta‐Yanes; Jessica M. da Silva; Catherine E. Grueber; Luis Castillo‐Reina; Viktoria Köppä; Brenna R. Forester; W. Chris Funk; Myriam Heuertz; Fumiko Ishihama; Rebecca Jordan; Joachim Mergeay; Ivan Paz‐Vinas; et al. (Ecology Letters, 2024)
Under the recently adopted Kunming‐Montreal Global Biodiversity Framework, 196 Parties committed to reporting the status of genetic diversity for all species. To facilitate reporting, three genetic diversity indicators were developed, two of which focus on processes contributing to genetic diversity conservation: maintaining genetically distinct populations and ensuring populations are large enough to maintain genetic diversity. The major advantage of these indicators is that they can be estimated with or without DNA‐based data. However, demonstrating their feasibility requires addressing the methodological challenges of using data gathered from diverse sources, across diverse taxonomic groups, and for countries of varying socio‐economic status and biodiversity levels. Here, we assess the genetic indicators for 919 taxa, representing 5271 populations across nine countries, including megadiverse countries and developing economies. Eighty‐three percent of the taxa assessed had data available to calculate at least one indicator. Our results show that although the majority of species maintain most populations, 58% of species have populations too small to maintain genetic diversity. Moreover, genetic indicator values suggest that IUCN Red List status and other initiatives fail to assess genetic status, highlighting the critical importance of genetic indicators.

Terrestrial and Martian space weather: A complex systems approach - Abraham Chian; Rodrigo Miranda; Cesar Bertucci; Xóchitl Blanco-Cano; Joe Borovsky; Sergio Dasso; Ezequiel Echer; Adriane Franco; Kirolosse M. Girgis; J. Américo González-Esparza; Tohru Hada; Hiroshi Hasegawa; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Habitat characterization and decline of Critically Endangered Onobrychis conferta subsp. conferta - Anis Sakhraoui; Hela Belhaj Ltaeif; Jesús M. Castillo; Slim Rouz (Journal for Nature Conservation, 2024)

Conversion of char from pyrolysis of plastic wastes into alternative activated carbons for heavy metal removal - Ledicia Pereira; Ventura Castillo; Mónica Calero; Gabriel Blázquez; Rafael R. Solís; M. Ángeles Martín-Lara (Environmental Research, 2024)

What if there is no further south to go: Assessing the vulnerability of Nacella species to climate change - Paola B. Reyna; Santiago Castillo; M. Carla de Aranzamendi (Estuarine, Coastal and Shelf Science, 2024)

Habitat of two threatened short-tailed whip-scorpions (Arachnida: Schizomida) in the tropical Andes of Northern South America - Dennis Castillo-Figueroa; Camilo Castillo-Avila; Jairo A. Moreno-González; Juan M. Posada (Journal of Insect Conservation, 2024)
Aim Schizomids are one of the less-known arachnid groups in terms of their natural history and ecology. However, due to their remarkable short-range endemic distribution, they may be vulnerable to climate change and habitat loss. In Colombia, although the national IUCN red list of threatened invertebrates has categorized species of schizomids as vulnerable (VU), this assessment was based on expert criteria. Therefore, information about the ecology of schizomids is critical for a more accurate reassessment of their conservation status. In this study, we describe the habitat of two species of Surazomus in endangered Andean tropical forests of Colombia after a sampling effort of 15.12 m 2 (n = 168 soil samples) and the collection of 6999 soil fauna individuals from the samples. We analyzed soil fauna communities associated with schizomids as well as different forest and environmental variables from permanent plots installed a decade ago in the Sabana de Bogotá region. Detailed information on climate, plant communities, and forest structure was obtained from these plots. Thus, we provide the first comprehensive habitat description of schizomids including both above- and belowground compartments. We found that each species lives in specific habitats with different soil fauna communities, suggesting a potential association between geographical fidelity and habitat conditions. This result could indicate that schizomids are highly sensitive to dramatic environmental changes, such as those experienced in the Andean region of Colombia. Implications for insect conservation Our study is valuable for the future reassessment of the conservation status of schizomids in the country, particularly considering that the previous categorization was based on expert criteria. Since habitat conditions and soil fauna communities are species-specific, schizomids could be disproportionately vulnerable to climate change and human disturbances in the Colombian Andes.

Predicting plant–pollinator interactions: concepts, methods, and challenges - Guadalupe Peralta; Paul J. CaraDonna; Demetra Rakosy; Jochen Fründ; María P. Pascual Tudanca; Carsten F. Dormann; Laura A. Burkle; Christopher N. Kaiser-Bunbury; Tiffany M. Knight; Julian Resasco; Rachael Winfree; Nico Blüthgen; et al. (Trends in Ecology & Evolution, 2024)

Sedimentological evolution of the Quibas site: High-resolution glacial/interglacial dynamics in a terrestrial pre-Jaramillo to post-Jaramillo sequence from southern Iberian Peninsula - Casto Laborda-López; David M. Martín-Perea; Elia Del Castillo; M. Asunción Alías Linares; Claudia Iannicelli; Shubham Pal; Xabier Arroyo; Jordi Agustí; Pedro Piñero (Quaternary International, 2024)

Evaluation of sub-chronic toxicity of melamine via systematic or oral delivery in adult zebrafish based on behavioral endpoints - Hsiu-Chao Chen; Wen-Wei Feng; Gilbert Audira; Kevin Adi Kurnia; San-Ho Hung; Agnes L. Castillo; Marri Jmelou M. Roldan; Chung-Der Hsiao; Chih-Hsin Hung (NeuroToxicology, 2024)

Insights into using plastic waste to produce activated carbons for wastewater treatment applications: A review - Ledicia Pereira; Ventura Castillo; Mónica Calero; Gabriel Blázquez; Rafael R. Solís; M. Ángeles Martín-Lara (Journal of Water Process Engineering, 2024)

Potential strategic allocation of nuptial gift proteins of the neotropical katydid Conocephalus ictus (Orthoptera Tettigoniidae) - Raúl Cueva del Castillo; Anahi Elias-Quevedo; Josefina Vázquez Medrano; Anabel Ruíz-Flores; César M. Flores-Ortiz (Journal of Insect Physiology, 2024)

Regional assessment of the historical trends of mercury in sediment cores from Wider Caribbean coastal environments - Yoelvis Bolaños-Alvarez; Ana Carolina Ruiz-Fernández; Joan-Albert Sanchez-Cabeza; Misael Díaz Asencio; Luisa F. Espinosa; Juan Pablo Parra; Jesús Garay; Ramón Delanoy; Nicolás Solares; Katia Montenegro; Alexis Peña; Fabiola López; et al. (Science of The Total Environment, 2024)

Promoting the circular economy: Valorization of a residue from industrial char to activated carbon with potential environmental applications as adsorbents - Ledicia Pereira; Ventura Castillo; Mónica Calero; Sergio González-Egido; M. Ángeles Martín-Lara; Rafael R. Solís (Journal of Environmental Management, 2024)

Disseminated cutaneous non-epitheliotropic B-cell lymphoma associated with a fracture site in a cat - M. Saravia-Castro; A. Reyes-Matute; A. Cervantes-Arias; D.d.J. Ruiz-Castillo (Journal of Comparative Pathology, 2024)

Efficient removal of triclosan from water through activated carbon adsorption and photodegradation processes - Nahum Andrés Medellín-Castillo; Lázaro Adrián González-Fernández; Raúl Ocampo-Pérez; Roberto Leyva-Ramos; Guilherme Luiz-Dotto; Rogelio Flores-Ramírez; Amado Enrique Navarro-Frómeta; Miguel Mauricio Aguilera-Flores; Francisco Carrasco-Marín; Héctor Hernández-Mendoza; Samuel Aguirre-Contreras; Manuel Sánchez-Polo; et al. (Environmental Research, 2024)

Precipitation in Northwestern Mexico: daily extreme events - José P. Vega-Camarena; Luis Brito-Castillo; Luis M. Farfán (Theoretical and Applied Climatology, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

The power of on-farm data for improved agronomy - Ignacio Macedo; Cameron M. Pittelkow; José A. Terra; Jesús Castillo; Alvaro Roel (Global Food Security, 2024)

Monitoring of Chemical Species in Soils, Waters and Plants Near the Active Copper Mine Tailing Dam Ovejeria (Central Chile) - Y. Tapia; A. García; E. Acuña; O. Salazar; M. Casanova; F. Najera; C. Kremer; B. Castillo; A. Joven; O. Diaz; R. Pastene; M. Antilen; et al. (Water, Air, & Soil Pollution, 2024)

PHB production by Bacillus megaterium strain MNSH1-9K-1 using low-cost media - Andrea M. Rivas-Castillo; Alejandro Valdez-Calderón; Arturo F. Angeles-Padilla; César B. Figueroa-Ocampo; Sandra Carrillo-Ibarra; Maribel Quezada-Cruz; Arian Espinosa-Roa; Brandon D. Pérez-García; Norma G. Rojas-Avelizapa (Brazilian Journal of Microbiology, 2024)

Assessing the impact of land use change on different components of plant diversity in a tropical montane cloud forest of Mexico - Gonzalo Castillo-Campos; José G. García-Franco; M. Luisa Martínez; Gabriela Vázquez; Jesús J. Pale-Pale; Mirna R. Zamudio Pérez; Octavio Pérez-Maqueo (Biodiversity and Conservation, 2024)

The critical period for yield and grain protein determination in quinoa (Chenopodium quinoa Willd.) - Santiago C. Vásquez; Alejandro del Pozo; Dalma Castillo; Iván Matus; Luz Gómez-Pando; Diego Zamudio-Ayala; Cesar M. Mignone; H. Daniel Bertero; Daniel F. Calderini (Field Crops Research, 2024)

Exploring the potential of microbial fuel cell-assisted biodegradation of nonylphenol - E. De la Peña; C. Castillo-Zacarías; R. G. Araújo; M. Rostro-Alanis; R. Parra-Saldivar; J. Rodriguez-Rodriguez (International Journal of Environmental Science and Technology, 2024)

Efficacy of a mirid predator and an eulophid parasitoid to the tomato potato psyllid Bactericera cockerelli control on pepper plants - Alejandro O. Guzmán-Pedraza; Ana Mabel Martínez; Ángel Rebollar-Alviter; Luis J. Palma-Castillo; Sinue I. Morales-Alonso; Juan M. Chavarrieta-Yáñez; José I. Figueroa; Samuel Pineda (BioControl, 2024)

Hg and Se in Muscle and Liver of Blue Shark (Prionace glauca) from the Entrance of the Gulf of California: An Insight to the Potential Risk to Human Health - M. E. Rechimont; J. Ruelas-Inzunza; F. Amezcua; F. Paéz-Osuna; J. L. Castillo-Géniz (Archives of Environmental Contamination and Toxicology, 2024)

Predictive models for grape downy mildew (Plasmopara viticola) as a decision support system in Mediterranean conditions - M. Puelles; J. Arbizu-Milagro; F.J. Castillo-Ruiz; J.M. Peña (Crop Protection, 2024)

Intra-urban variability of long-term exposure to PM2.5 and NO2 in five cities in Colombia - Laura A. Rodriguez-Villamizar; Yurley Rojas; Sara Grisales; Sonia C. Mangones; Jhon J. Cáceres; Dayana M. Agudelo-Castañeda; Víctor Herrera; Diana Marín; Juan G. Piñeros Jiménez; Luis C. Belalcázar-Ceron; Oscar Alberto Rojas-Sánchez; Jonathan Ochoa Villegas; et al. (Environmental Science and Pollution Research, 2023)
Rapidly urbanizing cities in Latin America experience high levels of air pollution which are known risk factors for population health. However, the estimates of long-term exposure to air pollution are scarce in the region. We developed intraurban land use regression (LUR) models to map long-term exposure to fine particulate matter (PM 2.5 ) and nitrogen dioxide (NO 2 ) in the five largest cities in Colombia. We conducted air pollution measurement campaigns using gravimetric PM 2.5 and passive NO 2 sensors for 2 weeks during both the dry and rainy seasons in 2021 in the cities of Barranquilla, Bucaramanga, Bogotá, Cali, and Medellín, and combined these data with geospatial and meteorological variables. Annual models were developed using multivariable spatial regression models. The city annual PM 2.5 mean concentrations measured ranged between 12.32 and 15.99 µg/m 3 while NO 2 concentrations ranged between 24.92 and 49.15 µg/m 3 . The PM 2.5 annual models explained 82% of the variance ( R 2 ) in Medellín, 77% in Bucaramanga, 73% in Barranquilla, 70% in Cali, and 44% in Bogotá. The NO 2 models explained 65% of the variance in Bucaramanga, 57% in Medellín, 44% in Cali, 40% in Bogotá, and 30% in Barranquilla. Most of the predictor variables included in the models were a combination of specific land use characteristics and roadway variables. Cross-validation suggests that PM 2.5 outperformed NO 2 models. The developed models can be used as exposure estimate in epidemiological studies, as input in hybrid models to improve personal exposure assessment, and for policy evaluation.

Leaching tests reveal fast aluminum fluoride release from ashfall accumulated in La Palma (Canary Islands, Spain) after the 2021 Tajogaite eruption - J. Sánchez-España; M. Pilar Mata; J. Vegas; G. Lozano; J. Mediato; J. Martínez Martínez; I. Galindo; N. Sánchez; B. del Moral; B. Ordóñez; A. de Vergara; A. Nieto; et al. (Journal of Volcanology and Geothermal Research, 2023)

Zero-G Lab: A multi-purpose facility for emulating space operations - Miguel Olivares-Mendez; Mohatashem Reyaz Makhdoomi; Barış Can Yalçın; Zhanna Bokal; Vivek Muralidharan; Miguel Ortiz Del Castillo; Vincent Gaudilliere; Leo Pauly; Olivia Borgue; Mohammadamin Alandihallaj; Jan Thoemel; Ernest Skrzypczyk; et al. (Journal of Space Safety Engineering, 2023)

Assessing earlywood-latewood proportion influence on tree-ring stable isotopes - M.C.A. Torbenson; U. Büntgen; P. Römer; O. Urban; M. Trnka; A. Ač; F. Reinig; M. Rybníček; T. Kolář; T. Arosio; E. Martinez del Castillo; E. Koňasová; et al. (Dendrochronologia, 2023)

Tracking the permeation of PVS2 components in living Mentha x Piperita SHOOT TIPS USING OPTICAL MICROSCOPIES - Heidi D. Kreckel; Albert Ochoa Castillo; Remi Bonnart; Gayle M. Volk; Dominik Stich; Nancy E. Levinger (Cryobiology, 2023)

Decoupling of short-lived radiogenic and helium isotopes in the Marquesas hotspot - M.-T. Herret; B.J. Peters; D. Kim; P.R. Castillo; A. Mundl-Petermeier (Chemical Geology, 2023)

Influence of Krill Meal on the Performance of Post-Smolt Atlantic Salmon That Are Fed Plant-Based and Animal-Based Fishmeal and Fish Oil-Free Diets - Frederick T. Barrows; Kelly B. Campbell; T. Gibson Gaylord; Rodrigo C. M. Sanchez; Sergio A. Castillo; Ewen McLean (Fishes, 2023)
The purpose of this study was to determine the influence of krill meal (KM) inclusion at various levels (0%, 2.5%, 5%) in plant-based and animal-based feeds, that were fishmeal (FM) and fish oil (FO) free, on Atlantic salmon growth. A FM/FO feed containing 0% KM was the control. Using a 2 × 3 factorial approach, diets were randomly assigned to one of 28 0.5 m3 flow-through tanks (n = 4 tanks per diet) initially stocked with 60 fish (148.4 ± 12.9 g; 23.6 ± 0.8 cm; condition factor (K) = 1.16 ± 0.08) each. Salmon were fed for 90 days using automatic feeders ad libitum. On day 45, stocking densities were reduced to 45 fish per tank by the random removal of 15 individuals to remove any potential of density affecting growth through the trial end. Water temperature, oxygen saturation, pH, and salinity throughout the trial were 11.8 °C, 103.5%, 7.38, and 32.0 g L−1, respectively. Fish fed plant-based feed without KM were lighter (p 0.05) to the control and 5% KM plant-based groups, with KM increasing feed intake (p

Overview of the tectonic and seismicity in Continental Borderland (offshore) Baja California, México - Mario González Escobar; Cristian A. Gallegos-Castillo; Sergio M. Arregui-Ojeda; Edgar A. Mastache-Román; Carlos S. Reyes-Martínez; Young Ho Aladro-Chio (Journal of South American Earth Sciences, 2023)

Five-year airborne pollen calendar for a Sonoran Desert city and the relationships with meteorological variability - C. I. Ortega-Rosas; O. G. Gutiérrez-Ruacho; L. Brito-Castillo; M. C. Calderón-Ezquerro; C. Guerrero-Guerra; V. Amaya-García (International Journal of Biometeorology, 2023)

Multiple dimensions of extreme weather events and their impacts on biodiversity - Juan David González-Trujillo; Rosa M. Román-Cuesta; Aarón Israel Muñiz-Castillo; Cibele H. Amaral; Miguel B. Araújo (Climatic Change, 2023)
Climate change is a multidimensional phenomenon. As such, no single metric can capture all trajectories of change and associated impacts. While numerous metrics exist to measure climate change, they tend to focus on central tendencies and neglect the multidimensionality of extreme weather events (EWEs). EWEs differ in their frequency, duration, and intensity, and can be described for temperature, precipitation, and wind speed, while considering different thresholds defining “extremeness.” We review existing EWE metrics and outline a framework for classifying and interpreting them in light of their foreseeable impacts on biodiversity. Using an example drawn from the Caribbean and Central America, we show that metrics reflect unequal spatial patterns of exposure across the region. Based on available evidence, we discuss how such patterns relate to threats to biological populations, empirically demonstrating how ecologically informed metrics can help relate EWEs to biological processes such as mangrove recovery. Unveiling the complexity of EWE trajectories affecting biodiversity is only possible through mobilisation of a plethora of climate change metrics. The proposed framework represents a step forward over assessments using single dimensions or averages of highly variable time series.

Influence of synoptic meteorology on airborne allergenic pollen and spores in an urban environment in Northeastern Iberian Peninsula - Marta Alarcón; Raül Rodríguez-Solà; M. Carmen Casas-Castillo; Francisco Molero; Pedro Salvador; Cristina Periago; Jordina Belmonte (Science of The Total Environment, 2023)

Diet Quality Outcomes of a Cooperative Extension Diabetes Prevention Program - Hannah K. Wilson; Isaura M. Castillo-Hernandez; Ellen M. Evans; Ewan R. Williams; Alison C. Berg (Journal of Nutrition Education and Behavior, 2023)

Salinity effects on the microbiome of a Neotropical water strider - Anakena M. Castillo; Karina A. Chavarria; Kristin Saltonstall; Carlos F. Arias; Luis C. Mejía; Luis F. De León (Hydrobiologia, 2023)

Higher alpha and gamma, but not beta diversity in tropical than in Mediterranean temporary ponds: A multi‐taxon spatiotemporal approach - Ángel Gálvez; Andreu Castillo‐Escrivà; Anne Magurran; Iván Alambiaga; Fabián Bonilla; Antonio Camacho; Eduardo M. García‐Roger; Sanda Iepure; Javier Miralles‐Lorenzo; Juan S. Monrós; Carla Olmo; Antonio Picazo; et al. (Limnology and Oceanography, 2023)
The latitudinal diversity gradient predicts that tropical regions should have higher alpha, beta, and gamma diversity than temperate areas. However, only a few studies have assessed the temporal variability of the different components of diversity across climatic regions. In this study, we compare, using a spatial and temporal approach, the diversity of multiple taxa inhabiting tropical and Mediterranean temporary ponds. We sampled the biological communities of each set of ponds on three occasions during the same hydrological year. Under a spatial framework, we analyzed, alpha, beta, and gamma diversities. With a temporal approach, we compared the coefficients of variation in alpha diversity for each local community, and temporal beta diversity. Differences between regions and sampling periods were tested using generalized linear mixed models. We found higher gamma and alpha diversity in the tropical ponds, as expected given the latitudinal differences between them. However, phytoplankton and microinvertebrates from the Mediterranean region, matched or even exceeded tropical alpha diversity on some occasions. Spatial beta diversity did not differ between regions, and it showed lower values at the middle or the end of the hydroperiod in bacteria, micro‐ and macroinvertebrates and amphibians. Thus, processes homogenizing and heterogenising pond metacommunities must be balanced in both studied regions. Temporal variation in alpha and beta diversity was similar for ponds in both regions, except for macroinvertebrates and amphibians, suggesting differential effects on community variation observable only in animals with longer life‐spans, at our temporal scale of analysis.

Deep convection, lightning activity and population impact over northwest Mexico: Coastal hotspots from 2009 to 2018 - Luis M. Farfán; Luis Brito‐Castillo; María Z. Flores López; Jorge Cortés‐Ramos (International Journal of Climatology, 2023)
Northwest Mexico (NWM) is an extensive region with a humid and unstable environment leading to atmospheric convection during the North American monsoon. Occasionally, extreme events are associated with severe weather, including deep convection, heavy rainfall and frequent lightning. Based on the period from July through September 2009–2018, the present study investigates general characteristics of convection. Geostationary satellites were used to document three‐dimensional cloud cover structures over the mainland, Gulf of California (GOC) and Baja California Peninsula (BCP). The convection developed over the Sierra Madre Occidental (SMO) mountains with a distinct cloud top structure over the southern GOC. In contrast, reduced cloud cover was observed over the peninsula and eastern Pacific Ocean. An active (2014) and inactive (2010) season are examined in more detail; the former had a more favourable environmental setting to support above‐normal convection and rainfall with respect to the 10‐year average. A regional‐scale analysis of lightning was computed with data from a ground‐based sensor network, including date, time and location of more than 16 million records. Major findings include: (1) lightning enhancement occurred in conjunction with deep convection, west of the SMO from the afternoon through the evening, while the gulf entrance became a well‐defined hotspot close to the mainland coastal plains overnight; (2) most lightning‐related deaths were in specific areas near the coastal plains or within isolated regions of the SMO foothills; (3) high exposure is expected in areas with considerable lightning and population located within 100 km from the gulf coastline. These findings are valuable for monitoring monsoon thunderstorms and for improving the ability to provide timely warnings of severe weather.

P06-19: Observations on the Behavior of the P-glycoprotein (ABCB1) Membrane Transporter in the Presence of ATP, Active and Inactive Substances - L. Mora Lagares; Y. Perez-Castillo; M. Novič (Toxicology Letters, 2023)

The effect of chronic disturbance on the woody plant diversity in a tropical dry forest of Central Mexico - Ofelia Sotelo-Caro; Susana Valencia-Díaz; Dulce M. Infante-Mata; Gonzalo Castillo-Campos; Alejandro Flores-Palacios (Flora, 2023)

Gill microbiomes accurately predict the geographic origin of bonefish (Albula vulpes) when combined with machine learning models - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Shimana M. Bose; Addiel U. Perez; Juan J. Schmitter-Soto; Sahar Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

3D printing to modulate the texture of starch-based food - Y. Bugarin-Castillo; P. Rando; M. Clabaux; G. Moulin; M. Ramaioli (Journal of Food Engineering, 2023)

Morphology of buried volcanic bodies in a sedimentary basin of the Pacific Continental Shelf (Gulf of California, Mexico) - Mario González-Escobar; Abril C. Sánchez-Barra; Cristian A. Gallegos-Castillo; Sergio M. Arregui Ojeda; Edgar A. Mastache-Román (Journal of Volcanology and Geothermal Research, 2023)

Understanding the landscape evolution of El Mogote barrier spit, Baja California Sur, Mexico, using OSL dating, satellite images and a multivariate analysis - A. Valoix; E. Muñoz-Salinas; M. Castillo; D. Sanderson; A. Cresswell (Journal of South American Earth Sciences, 2023)

Growth performance and lipid profiles of some tropical microalgae: An assessment of their potential as biofuel source - Chona Estudillo-del Castillo; Enrique M. Ligot; Leonora P. Nudo (Biocatalysis and Agricultural Biotechnology, 2023)

Valorizing industrial side streams through microalgae cultivation: A roadmap for process scale-up - Sandra Beatriz Castillo Castañeda; Rafael Emilio Altamirano Torres; Miguel Ángel Domínguez Vizcaíno; Elda M. Melchor-Martínez; Mariel Araceli Oyervides-Muñoz; Juan Eduardo Sosa Hernandez; Roberto Parra-Saldívar; Thomas Bisgaard; Omid Tavakoli; Irini Angelidaki; Solange I. Mussatto; Eduardo Krebs Kleingesinds; et al. (Algal Research, 2023)

Spatio‐temporal patterns of ichthyoplankton in southern Chilean Patagonia: β‐diversity and associated environmental factors - Mauricio F. Landaeta; Lissette D. Paredes; Manuel I. Castillo; M. Teresa González (Fisheries Oceanography, 2023)
Fjords play an important role in biological productivity worldwide but are vulnerable to climate/anthropogenic effects. Chilean Patagonia (41°S–55°S) is one of the largest fjord ecosystems in the world, characterized by a complex geography with highly heterogeneous hydrographic conditions and a permanent input from oceanic water mass, both of which influence the ichthyoplankton distributional patterns. In this study, we analysed the distributional patterns of ichthyoplankton and its diversity during austral spring from 1996, 2009 and 2019 in the southern Chilean fjords (47°S–54°S). The area shows important latitudinal gradients of sea surface temperature (from 15°C to 5°C), fjord‐ocean variability in salinity (from 23 to 33) and water column temperature (3°C to 9°C). Spatial (but not temporal) variations in the composition and abundance of ichthyoplankton were recorded, caused mainly by differences in the abundance of larval Sprattus fuegensis , Maurolicus australis and Sebastes oculatus . Richness was higher on continental shelf and the lowest nearby fjord's head and ice fields. At the spatial scale, β‐diversity showed an increased species replacement (turnover) across areas, suggesting an important role of environmental conditions (e.g., salinity and water stratification) on the larval fish structure in this region. Ordination analysis indicates that changes in salinity and temperature, caused by ice melting, is the main environmental factor influencing the abundance of larval Thysanopsetta naresi (1996), Cataetyx messieri (2009) and Bathylagichthys parini (2019). Finally, this study highlights the importance of the conservation and protection of the Chilean Patagonia and monitoring ichthyoplankton communities, which are vital biomarkers of ecosystem health.

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

The dynamics of arsenic and copper in solid and aqueous phases in reactive confluences receiving acid drainage: The role of turbidity and particle size - J.A. Díaz; D. Castillo; R. Oyarzún; A. Briso; M. Montecinos; P. Pastén (Environmental Pollution, 2023)

Effects of Atlanticists policies and visions: The legacy of colonialism in conservation - Leticia M. Ochoa-Ochoa; Rafa Devillamagallón; Guillermo Castillo-Ramírez; Liliana Cordero-Marines (Biological Conservation, 2023)

Prioritization of areas for groundwater monitoring using analytic hierarchy process method in Geographic Information Systems: a case of Mexico - J. M. Esquivel-Martínez; J. L. Expósito-Castillo; M. V. Esteller-Alberich; M. A. Gómez-Albores; C. M. Medina-Rivas; C. R. Fonseca-Ortiz (International Journal of Environmental Science and Technology, 2023)

ENSO Impact on Summer Precipitation and Moisture Fluxes over the Mexican Altiplano - José P. Vega-Camarena; Luis Brito-Castillo; Luis F. Pineda-Martínez; Luis M. Farfán (Journal of Marine Science and Engineering, 2023)
In the warm season, El Niño/Southern Oscillation (ENSO) causes periods with more rain in Northern Mexico during its positive phase, while less rainfall is recorded in the southern regions during the negative phase. This research study evaluates the variability of summer (July–September) precipitation and moisture fluxes under different ENSO scenarios in the Mexican Altiplano and coast of the state of Nayarit. The catchment of Rio San Pedro-Mezquital (SPM-RB) connects both regions. Using the Oceanic Niño Index (ONI), the years that signal change from El Niño to La Niña (1998), neutral conditions (2005), and strong (moderate) La Niña (1999) were selected to get an insight of ENSO impact on summer precipitation. For anomalies in the Altiplano, two additional contrasting years were analyzed—2006 (mostly dry) and 2010 (wet)—to determine moisture sources. Summer rainfall conditions in 1998 and 1999 had an opposite behavior between coastal Nayarit (wet) and the Altiplano (dry), while in 2005, rainfall deficits were observed in both regions. The moisture fluxes showed large divergence areas over central Mexico and the Southeastern United States in years of intense drought (1998 and 1999) caused by two high-pressure cells at middle levels of the troposphere (500 hPa). The moisture transport mechanisms into the Altiplano were related to atmospheric circulation at the upper level (200 hPa). The variations of the moisture fluxes from 2006 to 2010 are less strong at middle levels. The Eastern Pacific moisture convergence along the western coast of Mexico favors above-average rainfall anomalies in the coastal region but below-average anomalies in the Altiplano.

The removal of dissolved organic matter by marine sponges is a function of its composition and concentration: An in situ seasonal study of four Mediterranean species - M. Ribes; G. Yahel; C. Romera-Castillo; R. Mallenco; T.M. Morganti; R. Coma (Science of The Total Environment, 2023)

Biodiversity and assemblages of molluscs (Gastropoda and Bivalvia) from coastal and deep-sea soft-bottoms off Mauritania - Sidi M. Mohamed Moctar; Ana Ramos; Sara Castillo; Fran Ramil (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Phylogeographic origin authentication of Araucaria araucana (Mol.) K Koch seedlings through the application of spectroscopy techniques in different infrared ranges and chemometric methods - Macarena Rojas-Rioseco; Rosario del P. Castillo; Jorge González-Campos; Roberto Ipinza; M. I. Sanhueza; Rodrigo Hasbún (New Forests, 2023)

Volatile Organic Compounds Released by Oxyrrhis marina Grazing on Isochrysis galbana - Charel Wohl; Queralt Güell-Bujons; Yaiza M. Castillo; Albert Calbet; Rafel Simó (Oceans, 2023)
A range of volatile organic compounds (VOCs) have been found to be released during zooplankton grazing on microalgae cultivated for commercial purposes. However, production of grazing-derived VOCs from environmentally relevant species and their potential contribution to oceanic emissions to the atmosphere remains largely unexplored. Here, we aimed to qualitatively explore the suite of VOCs produced due to grazing using laboratory cultures of the marine microalga Isochrysis galbana and the herbivorous heterotrophic dinoflagellate Oxyrrhis marina with and without antibiotic treatment. The VOCs were measured using a Vocus proton-transfer-reaction time-of-flight mass spectrometer, coupled to a segmented flow coil equilibrator. We found alternative increases of dimethyl sulfide by up to 0.2 nmol dm−3 and methanethiol by up to 10 pmol dm−3 depending on the presence or absence of bacteria regulated by antibiotic treatment. Additionally, toluene and xylene increased by about 30 pmol dm−3 and 10 pmol dm−3, respectively during grazing only, supporting a biological source for these compounds. Overall, our results highlight that VOCs beyond dimethyl sulfide are released due to grazing, and prompt further quantification of this source in budgets and process-based understanding of VOC cycling in the surface ocean.

Non-destructive methods to assess pesticide exposure in free-living bats - Natalia Sandoval-Herrera; Jesusa Paz Castillo; Ma. Enrica Angela Ching; L. Gerardo Herrera M.; Paul A. Faure; Kenneth Welch (Science of The Total Environment, 2023)

Cross-sectional associations of persistent organic pollutants measured in adipose tissue and metabolic syndrome in clinically diagnosed middle-aged adults - Iris Reina-Pérez; Francisco Artacho-Cordón; Vicente Mustieles; Daniel Castellano-Castillo; Fernando Cardona; Inmaculada Jiménez-Díaz; Jose A. López-Medina; Juan Alcaide; Luis Ocaña-Wilhelmi; Luz M. Iribarne-Durán; Juan P. Arrebola; Nicolás Olea; et al. (Environmental Research, 2023)

Microalgae, a current option for the bioremediation of pharmaceuticals: a review - Manuel Aaaron Gayosso-Morales; Andrea M. Rivas-Castillo; Isaac Lucas-Gómez; Abelardo López-Fernández; Alejandro Valdez Calderón; Eduardo Fernández-Martínez; Jaime Ortega Bernal; Brenda Karen González-Pérez (Folia Microbiologica, 2023)

Associations between early introduction to complementary foods, subsequent cereal-added bottle feeding and daily macronutrient intake among infants - Jigna M. Dharod; Marlen Hernandez; Jeffrey D. Labban; Maureen M. Black; Alice Ammerman; Christina Frazier; Nichole Raynor; Isa Ramos-Castillo (Appetite, 2023)

Aerosolized aqueous dust extracts collected near a drying lake trigger acute neutrophilic pulmonary inflammation reminiscent of microbial innate immune ligands - Trevor A. Biddle; Keziyah Yisrael; Ryan Drover; Qi Li; Mia R. Maltz; Talyssa M. Topacio; Jasmine Yu; Diana Del Castillo; Daniel Gonzales; Hannah L. Freund; Mark P. Swenson; Malia L. Shapiro; et al. (Science of The Total Environment, 2023)

Lactoferrin gene polymorphisms associated with clinical mastitis in Honduran Holstein inheritance cows - M. Moncada-Laínez; P. A. Valladares-Medina; R. Castillo; X. F. De la Rosa-Reyna; A. M. Sifuentes-Rincón; V. R. Moreno-Medina; A. L. Lara-Rivera; G. M. Parra-Bracamonte (Molecular Biology Reports, 2023)

Using recreational tournament records to construct a 53-year time series of the Florida Keys recreational Bonefish fishery - Ross E. Boucek; Jennifer S. Rehage; Nicholas A. Castillo; Elijah Dwoskin; Steven M. Lombardo; Rolando Santos; Carl Navarre; Michael Larkin; Aaron J. Adams (Environmental Biology of Fishes, 2023)

A review of estimation methods for natural mortality and their performance in the context of fishery stock assessment - Mark N. Maunder; Owen S. Hamel; Hui-Hua Lee; Kevin R. Piner; Jason M. Cope; André E. Punt; James N. Ianelli; Claudio Castillo-Jordán; Maia S. Kapur; Richard D. Methot (Fisheries Research, 2023)

Refuelling infrastructure requirements for renewable hydrogen road fuel through the energy transition - John M. Low; R. Stuart Haszeldine; Julien Mouli-Castillo (Energy Policy, 2023)

Seed Viability, Spikelet Dispersal, Seed Banks and Seed Storage Requirements for Native and Invasive Cordgrasses (Genus Spartina) in Southwest Iberian Peninsula - M. Dolores Infante-Izquierdo; Ruth Romero-Martín; Jesús M. Castillo; Brenda J. Grewell; Jesús J. Soriano; F. Javier J. Nieva; Adolfo F. Muñoz-Rodríguez (Wetlands, 2023)
Seed banks play an important role in determining the spatial and temporal distribution of halophytes in salt marshes. We tested the ability of native Spartina maritima and invasive S. densiflora spikelets to disperse by flotation on water with different salinity concentrations, and the longevity of spikelet viability relative to environmental conditions including dry or wet storage at low or moderate temperatures, and aqueous salinity concentrations from fresh to sea water. We quantified pre-dispersal seed production and pre- and post-dispersal focal Spartina spp. presence in seed banks along intertidal gradients within salt marshes at the Gulf of Cádiz (Southwest Iberian Peninsula). Spartina densiflora spikelets, especially from middle and high elevation marshes, showed greater ability than S. maritima to remain afloat, which suggests this species could be dispersed over longer distances. Wet-stored Spartina seeds were able to maintain viability for months, while seeds under dry storage rapidly lost viability. This decline was most significant for S. maritima , and for seeds stored at moderate temperatures. Storage of spikelets under wet and cold conditions optimized spikelet viability. Native S. maritima did not establish transient or persistent seed banks, while invasive S. densiflora established transient seed banks mainly at higher marsh elevations. Our results on the dynamics of seed dispersal and seed banks and seedling recruitment provide fundamental knowledge that can be applied for conservation of native S. maritima , management of invasive S. densiflor a, and ecological restoration of tidal salt marshes.

Nitrogen and phosphorus budget in an intensive irrigation area and effects on littoral water and groundwater (Yaqui Valley, Northwestern Mexico) - B. R. Almazán; M. V. Esteller; S. E. Garrido-Hoyos; J. L. Expósito-Castillo; C. Díaz-Delgado; J. C. García-Colín (Environmental Monitoring and Assessment, 2023)

Time trends, irregularity and multifractal structure on the monthly rainfall regime at Barcelona, NE Spain, years 1786–2019 - Xavier Lana; M. Carmen Casas‐Castillo; Raül Rodríguez‐Solà; Marc Prohom; Carina Serra; Maria Dolors Martínez; Ricard Kirchner (International Journal of Climatology, 2023)
A long and complete series of monthly rainfall amounts corresponding to Barcelona city (Catalonia, NE Spain), exceeding two centuries (years 1786–2019), is analysed in detail. The obtained results of periodicity (annual scale), time trends (monthly, seasonal and annual scales), statistical distribution (seasonal and annual scale) and fractal/multifractal structures and self‐similarity at monthly scale depict the complex structure of this pluviometric regime, which is characterized by moderate increasing and decreasing trends on rain amounts, varying from +0.08 mm·year −1 (February) to −0.07 mm·year −1 (September) and quite evident changes on the pluviometric trends at annual and seasonal scales when the rainfall data are analysed for segments of 50 years from 1800 up to 2019. A good example could be the relevant change on the annual scale time trend, from +0.77 mm·year −1 (years 1800–1850) to −0.17 mm·year −1 (years 1950–2019). Clear evidences of decreasing pluviometry for spring, summer and autumn for the last segment (1950–2019) in comparison with the other three segments, including years 1800–1950, are also detected. Additionally, increasing rainfall patterns complexity, expected difficulties on monthly rainfall forecasting and the increasing irregularity of monthly amounts is also detected by interpreting fractal and multifractal results. Irregularity increases on the monthly rainfall series and on the rainfall regime complexity derived from multifractal parameters, could be associated with the very notable increase of CO 2 emissions into the atmosphere, globally varying from 51.1 × 10 6 metric tonnes (year 1820) to 36.6 × 10 9 metric tonnes (year 2019) and the tropospheric concentration increasing from 280.8 ppm (year 1850) to 397.5 ppm (year 2014), being the probable relationship between tropospheric concentrations and changes on rainfall patterns the objective of future researches.

Inconsistent response of taxonomic groups to space and environment in mediterranean and tropical pond metacommunities - Ángel Gálvez; Pedro R. Peres‐Neto; Andreu Castillo‐Escrivà; Fabián Bonilla; Antonio Camacho; Eduardo M. García‐Roger; Sanda Iepure; Javier Miralles‐Lorenzo; Juan S. Monrós; Carla Olmo; Antonio Picazo; Carmen Rojo; et al. (Ecology, 2023)
The metacommunity concept provides a theoretical framework that aims at explaining organism distributions by a combination of environmental filtering, dispersal, and drift. However, few works have attempted a multitaxon approach and even fewer have compared two distant biogeographical regions using the same methodology. We tested the expectation that temperate (mediterranean‐climate) pond metacommunities would be more influenced by environmental and spatial processes than tropical ones, because of stronger environmental gradients and a greater isolation of waterbodies. However, the pattern should be different among groups of organisms depending on their dispersal abilities. We surveyed 30 tropical and 32 mediterranean temporary ponds from Costa Rica and Spain, respectively, and obtained data on 49 environmental variables. We characterized the biological communities of bacteria and archaea (from the water column and the sediments), phytoplankton, zooplankton, benthic invertebrates, amphibians and birds, and estimated the relative role of space and environment on metacommunity organization for each group and region, by means of variation partitioning using generalized additive models. Purely environmental effects were important in both tropical and mediterranean ponds, but stronger in the latter, probably due to their larger limnological heterogeneity. Spatially correlated environment and pure spatial effects were greater in the tropics, related to higher climatic heterogeneity and dispersal processes (e.g., restriction, surplus) acting at different scales. The variability between taxonomic groups in the contribution of spatial and environmental factors to metacommunity variation was very wide, but higher in active, compared with passive, dispersers. Higher environmental effects were observed in mediterranean passive dispersers, and higher spatial effects in tropical passive dispersers. The unexplained variation was larger in the tropical setting, suggesting a higher role for stochastic processes, unmeasured environmental factors, or biotic interactions in the tropics, although this difference affected some actively dispersing groups (insects and birds) more than passive dispersers. These results, despite our limitations in comparing only two regions, provide support, for a wide variety of aquatic organisms, for the classic view of stronger abiotic niche constraints in temperate areas compared with the tropics. The heterogeneous response of taxonomic groups between regions also points to a stronger influence of regional context than organism adaptations on metacommunity organization.

Integrated evidence‐based extent of occurrence for North American bison ( Bison bison ) since 1500 CE and before - Jeff M. Martin; Rachel A. Short; Glenn E. Plumb; Lauren Markewicz; Dirk H. Van Vuren; Bradly Wehus‐Tow; Erik Otárola‐Castillo; Matthew E. Hill (Ecology, 2023)
Following the near extinction of bison ( Bison bison ) from its historic range across North America in the late 19th century, novel bison conservation efforts in the early 20th century catalyzed a popular widespread conservation movement to protect and restore bison among other species and places. Since Allen's initial delineation (1876) of the historic distribution of North American bison, subsequent attempts have been hampered by knowledge gaps about bison distribution and abundance prior to and following colonial arrival and settlement. For the first time, we applied a multidisciplinary approach to assemble a comprehensive, integrated geographic database and meta‐analysis of bison occurrence over the last 200,000 years, with particular emphasis on the 450 years before present. We combined paleontology, archaeology, and historical ecology data for our database, which totaled 6438 observations. We derived the observations from existing online databases, published literature, and first‐hand exploration journal entries. To illustrate the conservative maximum historical extent of occurrence of bison, we created a concave hull using observations occurring over the last 450 years ( n = 3379 observations), which is the broadly accepted historical benchmark at 1500 CE covering 59% of the North American continent. Although this distribution represents a historic extent of occurrence—merely delineating the maximum margins of the near‐continental distribution—it does not replace a density‐based approach reconstructing potential historical range distributions, which identifies core and marginal ranges. However, we envision the observations contained in this database will contribute to further research in the increasingly evidence‐based disciplines of bison ecology, evolution, rewilding, management, and conservation. There are no copyright or proprietary restrictions on these data, and this data paper should be cited when the data are reused.

Effect of the Trans‐Volcanic Axis on meridional propagation of summer precipitation in western Mexico - Luis Brito‐Castillo; Luis M. Farfán; Geimond Jarumi Antemate‐Velasco (International Journal of Climatology, 2022)
The Trans‐Volcanic Axis (TVA)—comprising ridges and terrain elevations above 1,900 m—strongly affects meridional propagation of summer precipitation in western Mexico. This barrier modifies atmospheric moisture content and changes the annual precipitation cycle configuration, which distinguishes it from the precipitation cycle on both sides of the TVA. Using upper‐air observations and rainfall records, this study demonstrates that the TVA is the region where the North American monsoon (NAM) and the mid‐summer drought (MSD) influence intersections regarding precipitation. This region affects both northward extent of double precipitation maxima with the MSD and the southward extent of the NAM single precipitation peak. This study proposes that the forcing mechanism that controls the annual precipitation cycle in the TVA region relies on latent heat loss via ground cooling by reducing air temperature below dewpoint temperature in the 700–500 hPa layer, consistent with local terrain elevations. The orographic effect increases specific humidity in the atmospheric column—sufficiently large to enhance local precipitation accumulation—resulting in a mid‐summer drought intensity decline but not enough to yield a single peak in precipitation. Consequently, the TVA becomes an uncategorized region that does not display the NAM nor the characteristic features of the MSD.

Assessing Conservation Easement Landowners Adoption of Thinning - Ana Gutierrez-Castillo; Shaun M Tanger; Jerrod Penn; Michael A Blazier (Forest Science, 2022)
The Natural Resources Conservation Service has overseen several conservation easement programs in the Lower Mississippi Alluvial Valley (LMAV), which have the primary objective to protect, restore, and enhance wetlands functions and to protect conservation values, such as wildlife habitat. Promotion of thinning in forests reaching or past canopy closure improves habitat conditions in forests under conservation easement. This study explicitly explores determinants that influence easement landowner voluntary adoption of thinning and characterizes landowners who are unwilling to thin in terms of management concerns, objective interference, and other reasons. The willingness-to-thin models demonstrated that membership in conservation organizations, different income expectations from thinning, and investment objectives positively influence landowners’ willingness to thin, whereas being an original easement grantor decreases the likelihood to thin such that subsequent landowners who will inherit or purchase the easement will be more willing to conduct thinning. Study results also indicated that landowners who had recreation as an ownership objective are less likely to adopt thinning, having important long-term implications for managing the forest in the easements. Findings from this study could be used to improve efforts to design and conduct educational interventions that promote forest health and wildlife habitat needs in the LMAV easements.

Seasonal and Spatial Variability of PM2.5 Concentration, and Associated Metal(loid) Content in the Toluca Valley, Mexico - Ana Larissa Barbosa-Sánchez; Ciro Márquez-Herrera; Rodolfo Sosa-Echeverria; Raúl Venancio Díaz-Godoy; María Eugenia Gutiérrez-Castillo; Consuelo Escamilla-Núñez; Ana M. Rule; Martha Patricia Sierra-Vargas; Octavio Gamaliel Aztatzi-Aguilar (Bulletin of Environmental Contamination and Toxicology, 2022)

Lupeol acetate isolated from Chrysophyllum cainito L. fruit as a template for the synthesis of N -alkyl-arylsulfonamide derivatives and their synergistic effects with metronidazole against Trichomonas vaginalis - Angel D. Herrera-España; Julio A. Aguiar-Pech; M. Elizbeth Alvarez-Sánchez; Victor E. Arana-Argáez; Cynthia K. Palomar-Gómez; Armin G. Jiménez-Ross; David Cáceres-Castillo; Rubén M. Carballo; Julio C. Torres-Romero (Natural Product Research, 2022)

Structure and activity of microbial communities in response to environmental, operational, and design factors in constructed wetlands - M. Verduzo Garibay; A. Fernández del Castillo; J. de Anda; C. Senés-Guerrero; M. S. Gradilla-Hernández (International Journal of Environmental Science and Technology, 2022)

Title: Present status and management of coastal lagoons in the Sabana–Camagüey Archipelago I: environmental baseline at lagoons of Cayo Sabinal - R. González-De; Zayas; M. Merino-Ibarra; J. A. Lestayo González; F. S Castillo – Sandoval (Thalassas: An International Journal of Marine Sciences, 2022)

Metaomics unveils the contribution of Alteromonas bacteria to carbon cycling in marine oxygen minimum zones - Carlos Henríquez-Castillo; Alvaro M. Plominsky; Salvador Ramírez-Flandes; Anthony D. Bertagnolli; Frank J. Stewart; Osvaldo Ulloa (Frontiers in Marine Science, 2022)
Gammaproteobacteria of the genus Alteromonas are prominent members of pelagic marine microbial communities, playing critical roles in the aerobic degradation of particulate organic matter. Comparative genomic studies of these microorganisms have mainly focused on the metabolic and genomic plasticity of strains isolated primarily from oxygenated environments. In this study, we show that Alteromonas significantly contribute to marine microbial communities from suboxic waters ([O 2 ] < 5 uM) in both the free-living (FL) and particle-attached (PA) fractions, but considerably decrease in abundance in the anoxic waters. The highest proportion of Alteromonas transcripts was found within the secondary fluorescence maximum (SFM) of Oxygen Minimum Zones (OMZs). This metatranscriptomic information suggests an in situ coupling of Alteromonas iron (Fe) and carbon metabolisms, and a relevant role of the glyoxylate cycle across the different layers of the OMZs. This study demonstrates that Alteromonas is an abundant and active member of the OMZ microbial communities, with a potentially significant impact on the carbon cycling in these ecosystems. These results provide valuable environmental evidence to support previous culture-based studies assessing the physiology and ecology of these ubiquitous marine heterotrophs under low-oxygen conditions.

Spatio-temporal analysis of the extent of an extreme heat event - Ana C. Cebrián; Jesús Asín; Alan E. Gelfand; Erin M. Schliep; Jorge Castillo-Mateo; María A. Beamonte; Jesús Abaurrea (Stochastic Environmental Research and Risk Assessment, 2022)
Evidence of global warming induced from the increasing concentration of greenhouse gases in the atmosphere suggests more frequent warm days and heat waves. The concept of an extreme heat event (EHE), defined locally based on exceedance of a suitable local threshold, enables us to capture the notion of a period of persistent extremely high temperatures. Modeling for extreme heat events is customarily implemented using time series of temperatures collected at a set of locations. Since spatial dependence is anticipated in the occurrence of EHE’s, a joint model for the time series, incorporating spatial dependence is needed. Recent work by Schliep et al. (J R Stat Soc Ser A Stat Soc 184(3):1070–1092, 2021) develops a space-time model based on a point-referenced collection of temperature time series that enables the prediction of both the incidence and characteristics of EHE’s occurring at any location in a study region. The contribution here is to introduce a formal definition of the notion of the spatial extent of an extreme heat event and then to employ output from the Schliep et al. (J R Stat Soc Ser A Stat Soc 184(3):1070–1092, 2021) modeling work to illustrate the notion. For a specified region and a given day, the definition takes the form of a block average of indicator functions over the region. Our risk assessment examines extents for the Comunidad Autónoma de Aragón in northeastern Spain. We calculate daily, seasonal and decadal averages of the extents for two subregions in this comunidad. We generalize our definition to capture extents of persistence of extreme heat and make comparisons across decades to reveal evidence of increasing extent over time.

Contrasting Effects of Nitrogen and Labile Carbon Addition on N2O Emissions from Andosols in Costa Rica and Chile Under Controlled Conditions - C. Chinchilla-Soto; M. A. Alfaro; F. Bertsch; A. G. Perez-Castillo (Journal of Soil Science and Plant Nutrition, 2022)

Molecular detection of Coxiella-like endosymbionts and absence of Coxiella burnetii in Amblyomma mixtum from Veracruz, Mexico - Estefanía Grostieta; Héctor M. Zazueta-Islas; Timoteo Cruz-Valdez; Gerardo G. Ballados-González; Lucía Álvarez-Castillo; Sandra M. García-Esparza; Anabel Cruz-Romero; Dora Romero-Salas; Mariel Aguilar-Domínguez; Ingeborg Becker; Sokani Sánchez-Montes (Experimental and Applied Acarology, 2022)

Aridification‐driven evolution of a migratory fish revealed by niche modelling and coalescence simulations - Emily J. Booth; Jonathan Sandoval‐Castillo; Catherine R. M. Attard; Dean M. Gilligan; Peter J. Unmack; Luciano B. Beheregaray (Journal of Biogeography, 2022)
Aim Major knowledge gaps exist regarding the evolution of arid zone organisms. For freshwater species with high dispersal potential, little is known if historical aridification influenced connectivity across drainage divides and impacted on their divergence and diversification. We tested the hypothesis that the historical aridification of Australia promoted the isolation and influenced the demographic histories and evolutionary divergence of a migratory group of freshwater obligates. Location Central and eastern Australia; Murray–Darling Basin (MDB), Lake Eyre Basin (LEB), Fitzroy Basin (FIT). Taxon Three lineages of golden perch ( Macquaria ambigua ), a widespread fishery resource from inland Australia. Methods We obtained genome‐wide data for golden perch sampled throughout their range. Phylogenetic relationships were reconstructed using maximum likelihood. Species distribution modelling was used to predict contemporary and past distributions for the three lineages and to develop hypotheses regarding their biogeographic and demographic histories. Hypotheses were independently tested using coalescent simulations in fastsimcoal and DIYABC with the genomic dataset. Results We found evidence for three reciprocally monophyletic lineages that have experienced little to nil genetic connectivity since divergence. Coalescent models suggest that the coastal (FIT) and inland (MDB and LEB) lineages diverged ~103 thousand years ago (ka), followed by the split of MDB and LEB lineages ~58 ka. These timings agree with reductions of large freshwater environments in Australia during the late Pleistocene. Species distribution models show an extreme decrease in habitat during the Last Glacial Maximum ~21 ka, consistent with inferred demographic contractions in coalescent tests. Main conclusions We reveal that aridification of Australia during the late Pleistocene has driven and reinforced the divergence of a migratory freshwater obligate. Our findings are important for informing the conservation management of aquatic organisms under climate change. This work further demonstrates the value of using species distribution modelling to formulate diversification hypotheses and to improve interpretation of coalescent analyses.

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

A quality control procedure for long-term series of daily precipitation data in a semiarid environment - Javier Estévez; Alba Llabrés-Brustenga; M. Carmen Casas-Castillo; Amanda Penélope García-Marín; Ricard Kirchner; Raül Rodríguez-Solà (Theoretical and Applied Climatology, 2022)
The availability of quality precipitation records in the current climate situation is of great importance in the scientific-technical field but also for the public institutions that manage the meteorological networks. This work has implemented a comprehensive spatial quality control procedure in the semiarid region of Andalusia (Southern Spain), using precipitation time series from 1947 stations from three meteorological networks: Spanish Meteorological Agency (AEMET), Agroclimatic Information Network of Andalusia (RIA), and Phytosanitary Information Alert Network (RAIF). The method consists of three consecutive steps: basic, absolute, and relative quality control processes. The latter step compares data from neighboring stations taking into account their proximity, height difference, and correlation, leading to a complete evaluation of each daily value. Finally, the quality of each year at each station can be declared as acceptable, good, or excellent. The automatic weather station networks RIA and RAIF gave absolute quality index $$Q$$ Q above 85% for almost 87% of their stations, while only 57% of AEMET network reached this percentage. However, one of the longest AEMET datasets, San Fernando-Cádiz, obtained, except for 1 year, $$Q$$ Q values over 90% in all available years for more than a century of measurements, since 1870 until 2000. From a total of more than 15 million daily records, almost 82% was flagged as correct. Despite the limitations of Andalusia region (low density of stations and its structural water deficit), the complete quality control procedure has been satisfactorily applied. Finally, related to the number of outliers, no temporal trend was found across the region. Graphical abstract

Different exercise training modalities similarly improve heart rate variability in sedentary middle-aged adults: the FIT-AGEING randomized controlled trial - Ginés Navarro-Lomas; Manuel Dote-Montero; Juan M. A. Alcantara; Abel Plaza-Florido; Manuel J. Castillo; Francisco J. Amaro-Gahete (European Journal of Applied Physiology, 2022)
Purpose This study aimed to investigate the influence of different exercise training modalities on heart rate variability (HRV) in sedentary middle-aged adults; and to study whether changes in health-related outcomes (i.e., body composition and cardiometabolic risk) are associated with those hypothetical HRV changes in sedentary middle-aged adults. Methods A total of 66 middle-aged adults (53.6 ± 4.4 years old; 50% women) were enrolled in the FIT-AGEING study. We conducted a 12-week randomized controlled trial. The participants were randomly assigned to 4 groups: (a) a control group (no exercise); (b) a physical activity recommendation from the World Health Organization group (PAR); (c) a high-intensity interval training group (HIIT); and (d) a high-intensity interval training group adding whole-body electromyostimulation (HIIT + EMS). Results All exercise training modalities induced changes in HRV parameters (all P ≤ 0.001) without statistical differences between them (all P > 0.05). We found associations between changes in body composition and cardiometabolic risk and exercise-related changes in HRV. Conclusion Our results suggest that different exercise interventions (i.e., PAR, HIIT and HIIT + EMS) induced an enhancement of HRV in sedentary middle-aged adults. Our findings support the notion that exercise-related changes in HRV are associated with changes in body composition and cardiometabolic risk after the intervention program Clinical trial registry NCT03334357 (ClinicalTrials.gov). November 7, 2017 retrospectively registered.

How candidate genes respond to aluminum toxicity in Citrus x limonia Osbeck? - Carolina M. S. Silva; Alexander Banguela-Castillo; Douglas S. Domingues; Gustavo Habermann (Theoretical and Experimental Plant Physiology, 2022)

DNA barcoding of Glossogobius species (Teleostei: Gobiidae) from major lakes in the Philippines reveals the presence of cryptic species and species complexes - Onaya P. Abdulmalik-Labe; Nicole Mae R. Picart; Mirriam Esther M. Francisco; Raisa Mikaelle G. Castillo; Jonas P. Quilang (Conservation Genetics Resources, 2022)

Evolution and dynamics of the open-vent eruption at Arenal volcano (Costa Rica, 1968–2010): what we learned and perspectives - Mauricio M. Mora; Philippe Lesage; Waldo Taylor-Castillo; Sylvie Vergniolle; Loïc Fourel; Gerardo J. Soto (Bulletin of Volcanology, 2022)
On 29 July 1968, there was a violent reactivation of Arenal volcano. The resulting westward-directed lateral blast eruption left two villages destroyed and 78 people dead. The activity continued as a long-lasting, open-vent eruption that evolved into seven recognisable phases reflecting changes in magma supply, explosive activity and cone evolution, and ended in October 2010. Here, we review this activity, the geophysical approaches applied to understanding it and the open questions resulting from these insights. The eruptive dynamics were characterised by almost constant lava effusion, degassing, strombolian and vulcanian explosions and infrequent pyroclastic density currents. In this study, the total rock dense equivalent volume of lava and tephra erupted is calculated at 757 ± 77 Mm 3 , while the volume of the lava flow field is 527 ± 58 Mm 3 . Typical seismic activity included harmonic and spasmodic tremors, long-period events and explosion signals with frequent audible “booms”. The decline of the eruptive activity started in 2000, with a decrease in the number and size of explosive events, a shift from long to short lava flows along with the collapse of lava flow fronts and the subsequent formation of downward-rolling lava block aprons, the frequent growth of dome-like structures on the summit and a gradual decrease in seismic energy. Multiple geological and geophysical studies during this 42-year-long period of open-vent activity at Arenal resulted in many advances in understanding the dynamics of andesitic blocky lava flows, the origin and diversity of pyroclastic density currents and seismic sources, as well as the role of site effects and rough topography in modifying the seismic wavefield. The acoustic measurements presented here include two types of events: typical explosions and small pressure transients. Features of the latter type are not usually observed at volcanoes with intermediate to evolved magma composition. Explosions have different waveforms and larger gas volumes than pressure transients, both types being associated with active and passive degassing, respectively. This body of data, results and knowledge can inform on the type of activity, and associated geophysical signals, of open-vent systems that are active for decades.

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Correction to: A study on correlations between precipitation ETCCDI and airborne pollen/fungal spore parameters in the NE Iberian Peninsula - R. Rodríguez-Solà; M. C. Casas-Castillo; J. J. Ho Zhang; R. Kirchner; M. Alarcón; C. Periago; C. De Linares; J. Belmonte (International Journal of Biometeorology, 2022)

A study on correlations between precipitation ETCCDI and airborne pollen/fungal spore parameters in the NE Iberian Peninsula - R. Rodríguez-Solà; M. C. Casas-Castillo; J. J. Ho Zhang; R. Kirchner; M. Alarcón; C. Periago; C. De Linares; J. Belmonte (International Journal of Biometeorology, 2022)

Assessing the impact of an invasive plant in a Protected Natural Area: Island of Cozumel, Mexico - Gonzalo Castillo-Campos; M. Luisa Martínez; José G. García-Franco; Gabriela Vázquez; Octavio Pérez-Maqueo; Jesús Pale-Pale (Biological Invasions, 2022)

Seascape genomics of coastal bottlenose dolphins along strong gradients of temperature and salinity - Eleanor A. L. Pratt; Luciano B. Beheregaray; Kerstin Bilgmann; Nikki Zanardo; Fernando Diaz‐Aguirre; Chris Brauer; Jonathan Sandoval‐Castillo; Luciana M. Möller (Molecular Ecology, 2022)
Heterogeneous seascapes and strong environmental gradients in coastal waters are expected to influence adaptive divergence, particularly in species with large population sizes where selection is expected to be highly efficient. However, these influences might also extend to species characterized by strong social structure, natal philopatry and small home ranges. We implemented a seascape genomic study to test this hypothesis in Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) distributed along the environmentally heterogeneous coast of southern Australia. The data sets included oceanographic and environmental variables thought to be good predictors of local adaptation in dolphins and 8081 filtered single nucleotide polymorphisms (SNPs) genotyped for individuals sampled from seven different bioregions. From a neutral perspective, population structure and connectivity of the dolphins were generally influenced by habitat type and social structuring. Genotype‐environment association analysis identified 241 candidate adaptive loci and revealed that sea surface temperature and salinity gradients influenced adaptive divergence in these animals at both large‐ (1000 km) and fine‐scales (

The genetic diversity of wild grapes in Mexico - Karla G. Huerta-Acosta; Summaira Riaz; Omar Franco-Mora; Juan G. Cruz-Castillo; M. Andrew Walker (Genetic Resources and Crop Evolution, 2022)
This is the first report evaluating the genetic diversity of Mexican grape species utilizing DNA-based markers to understand the distribution of grape species, and patterns of hybridization. The study utilized accessions maintained in three collections in Mexico, one in the USA and recently collected germplasm. Fifteen SSR markers were used to develop a fingerprint database to identify unique germplasm. Two different clustering analyses without prior population assignment, were used to identify groups that were verified by a Discriminant Analysis of Principal Components and a Principal Coordinate Analysis. Genetic diversity estimates were made across and within groups to validate the results obtained from the clustering analyses. Multiple clustering analyses and diversity parameters supported six genetic groups representing different geographic regions. The Northeastern group was the most diverse with a geographic range extending to Eastern and Central Mexico, while the Coahuila group was the least diverse. Vitis arizonica Engelm. and Vitis cinerea Engelm. ex Millardet were the most abundant species with many hybrid forms. We provide evidence that wild grape species in Mexico follow the physical barriers of mountain ranges like the Sierra Madre Oriental with an east–west divide and the Trans-Mexican Volcanic Belt as a corridor for gene flow among different grape species. Additional collections are required to fully understand the extent of hybridization and to clarify hybrid zones.

Genomics outperforms genetics to manage mistakes in fisheries stocking of threatened species - Catherine R. M. Attard; Jonathan Sandoval-Castillo; Dean M. Gilligan; Peter J. Unmack; Leanne K. Faulks; Luciano B. Beheregaray (Biodiversity and Conservation, 2022)
Hatchery production and fisheries stocking is a widespread and high profile management practice because it allows recreational fisheries to continue in threatened species. Human-mediated transfer of fish across the geographic boundaries of intraspecies lineages or closely related species can cause introgression and occasionally outbreeding depression. Hybridization can be difficult to detect due to limited morphological differences among close lineages and the relatively low power of traditional genetic datasets. Here we showcase the use of genomic techniques to detect admixture of the economically important and threatened golden perch ( Macquaria ambigua ) in the Murray-Darling Basin, southeast Australia. We detected admixture through a genome-wide dataset of 6,862 single nucleotide polymorphisms (SNPs) across 174 Murray-Darling sourced fish and 15 fish from each of two neighbouring basins: the Lake Eyre and Fitzroy basins. Individuals with partial ancestry from both neighboring basins were detected using genomics throughout the Murray-Darling, suggesting the release of individuals and introgression into the Murray-Darling Basin. Importantly, a traditional microsatellite dataset was unreliable for identifying admixed individuals. The SNP-detected admixed individuals were also found in Murray-Darling impoundments, where fish are solely sourced from government-managed hatcheries, suggesting that some broodstock in hatcheries might have non-endemic ancestry. Stocking programs for golden perch release over one million fingerlings each year, and so could impact the genetic variation in the wild. We advocate for using genomics to check the ancestry of broodstock and for increasing collaboration between managers and academics—as done here—to better integrate the power of genomics into biodiversity management and conservation.

Diatom Species that Characterize Saline Ponds (Southern Spain) with the Description of a New Navicula Species - David Fernández-Moreno; Pedro M. Sánchez-Castillo; Cristina Delgado; Salomé F. P. Almeida (Wetlands, 2022)

Population genomic structure of killer whales ( Orcinus orca ) in Australian and New Zealand waters - Isabella M. Reeves; John A. Totterdell; Andrea Barceló; Jonathan Sandoval‐Castillo; Kimberley C. Batley; Karen A. Stockin; Emma L. Betty; David M. Donnelly; Rebecca Wellard; Luciano B. Beheregaray; Luciana M. Möller (Marine Mammal Science, 2022)
Population genomic data sets have enhanced power to detect cryptic and complex population structure and generate valuable information for the conservation and management of wildlife species. Globally, killer whales ( Orcinus orca ) are considered to have a complex population structure due to their ability to specialize in a variety of ecological niches. In the Australasian region, they are found year round in New Zealand waters and are sighted in all Australian waters, with seasonal aggregations in the northwest (NWA) and southwest (SWA). Regionally, there is some knowledge regarding killer whale abundance, diet, acoustics, and social structure, but limited information about their population structure. Here, we present a population structure assessment of Australasian killer whales using 17,491 high quality genome‐wide single nucleotide polymorphisms (SNPs), combined with sequences of the mitochondrial DNA control region. The results indicate a minimum of three populations: New Zealand, NWA, and SWA. These populations present moderate levels of genomic diversity, negligible levels of inbreeding, small effective population sizes, and low contemporary migration rates among them. Mitochondrial DNA analysis elucidated five closely related haplotypes, suggestive of matrilineal societies, consistent with killer whales elsewhere. This information will assist conservation management of killer whales in the Australasian region.

Pharmacokinetic and pharmacodynamic properties of aerosolized (“vaped”) THC in adolescent male and female rats - C. M. Ruiz; A. Torrens; V. Lallai; E. Castillo; L. Manca; M. X. Martinez; D. N. Justeson; C. D. Fowler; D. Piomelli; S. V. Mahler (Psychopharmacology, 2021)

Whole genomes reveal multiple candidate genes and pathways involved in the immune response of dolphins to a highly infectious virus - Kimberley C. Batley; Jonathan Sandoval‐Castillo; Catherine M. Kemper; Nikki Zanardo; Ikuko Tomo; Luciano B. Beheregaray; Luciana M. Möller (Molecular Ecology, 2021)
Wildlife species are challenged by various infectious diseases that act as important demographic drivers of populations and have become a great conservation concern particularly under growing environmental changes. The new era of whole genome sequencing provides new opportunities and avenues to explore the role of genetic variants in the plasticity of immune responses, particularly in non‐model systems. Cetacean morbillivirus (CeMV) has emerged as a major viral threat to cetacean populations worldwide, contributing to the death of thousands of individuals of multiple dolphin and whale species. To understand the genomic basis of immune responses to CeMV, we generated and analysed whole genomes of 53 Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) exposed to Australia's largest known CeMV‐related mortality event that killed at least 50 dolphins from three different species. The genomic data set consisted of 10,168,981 SNPs anchored onto 23 chromosome‐length scaffolds and 77 short scaffolds. Whole genome analysis indicated that levels of inbreeding in the dolphin population did not influence the outcome of an individual. Allele frequency estimates between survivors and nonsurvivors of the outbreak revealed 15,769 candidate SNPs, of which 689 were annotated to 295 protein coding genes. These included 50 genes with functions related to innate and adaptive immune responses, and cytokine signalling pathways and genes thought to be involved in immune responses to other morbilliviruses. Our study characterised genomic regions and pathways that may contribute to CeMV immune responses in dolphins. This represents a stride towards clarifying the complex interactions of the cetacean immune system and emphasises the value of whole genome data sets in understanding genetic elements that are essential for species conservation, including disease susceptibility and adaptation.

Rainfall regime trends at annual and monthly scales in Catalonia (NE Spain) and indications of CO2 emissions effects - Xavier Lana; M. Carmen Casas-Castillo; Raül Rodríguez-Solà; Carina Serra; M. Dolors Martínez; Ricard Kirchner (Theoretical and Applied Climatology, 2021)
The pluviometric regime in the Western Mediterranean and concretely in Catalonia (NE Spain) is characterised by irregular amounts at monthly and annual scales, sometimes with copious short episodes causing floods and, conversely, sometimes with long dry spells exceeding 1 month length, depending on the chosen threshold level to define the dry episode. Taking advantage of a dense network of rain gauges, most of them with records length of 50–60 years and some others exceeding 85 years, the evolution of these monthly and annual amounts is quantified by means of their time trends, statistical significance and several irregularity parameters. In agreement with the evolution of the CO 2 emissions into the atmosphere and the increasing concentration, in parts per million (ppm), of this greenhouse gas, different time trends at annual scale have been detected up to approximately years 1960–1970 in comparison with the interval 1960–1970 to nowadays. Consequently, besides the greenhouse effects on the temperature regime, the influence on the pluviometric regime could not be negligible. Graphical abstract

Probiotic Properties of Alcaligenes faecalis Isolated from Argyrosomus regius in Experimental Peritonitis (Rat Model) - A. I. Gutiérrez-Falcón; A. M. Ramos-Nuez; A. Espinosa de los Monteros y Zayas; D. F. Padilla Castillo; M. Isabel García-Laorden; F. J. Chamizo-López; F. Real Valcárcel; F. Artilles Campelo; A. Bordes Benítez; P. Nogueira Salgueiro; C. Domínguez Cabrera; J. C. Rivero-Vera; et al. (Probiotics and Antimicrobial Proteins, 2021)
A strain of Alcaligenes faecalis A12C ( A. faecalis A12C) isolated from Argyrosomus regius is a probiotic in fish. Previous experiments showed that A. faecalis A12C had inhibitory effects on the growth of multidrug-resistant bacteria. We aimed to confirm whether A. faecalis A12C is safe and has adequate intestinal colonization in experimental rats, and evaluate its efficacy in an animal model of peritonitis . We used 30 male rats, randomly divided into 6 groups ( n = 5): three groups (HA7, HA15, HA30) received A. faecalis A12C in drinking water (6 × 10 8 CFU/mL) for 7 days, and three control groups received drinking water only. All groups were evaluated at 7, 15, and 30 days. Survival after A. faecalis A12C administration was 100% in all groups. Mild eosinophilia (1.5%, p < 0.01) and increased aspartate aminotransferase (86 IU/L, p < 0.05) were observed in HA7, followed by progressive normalization. No histological signs of organ injury were found. We observed significant E. coli decline in faeces, parallel to an increase in A. faecalis A12C at 7 days. E. coli had a tendency to recover initial values, while A. faecalis A12C disappeared from the intestinal microbiota at 30 days. To evaluate its efficacy against peritonitis, we studied two additional groups of animals: IA group pretreated with A. faecalis A12C before E. coli intra-abdominal inoculation, and IC group inoculated with no A. faecalis A12C. We found an increase in C-reactive protein, alanine aminotransferase, urea, and eosinophils in IC animals when compared with IA. Peritonitis was more evident in IC than in IA animals. Our findings suggest that A. faecalis A12C altered clinically relevant parameters in sepsis and was associated with a lesser spread of infection.

Salinity and inundation effects on Iris pseudacorus: implications for tidal wetland invasion with sea level rise - Brenda J. Grewell; Blanca Gallego-Tévar; Morgane B. Gillard; Caryn J. Futrell; Rebecca Reicholf; Jesús M. Castillo (Plant and Soil, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Addressing the challenges of climate-driven community-led resettlement and site expansion: knowledge sharing, storytelling, healing, and collaborative coalition building - Julie Maldonado; Itzel Flores Castillo Wang; Fred Eningowuk; Lesley Iaukea; Aranzazu Lascurain; Heather Lazrus; Chief Albert Naquin; JR Naquin; Kukuya Margarita Nogueras-Vidal; Kristina Peterson; Isabel Rivera-Collazo; M. Kalani Souza; et al. (Journal of Environmental Studies and Sciences, 2021)
Presently coastal areas globally are becoming unviable, with people no longer able to maintain livelihoods and settlements due to, for example, increasing floods, storm surges, coastal erosion, and sea level rise, yet there exist significant policy obstacles and practical and regulatory challenges to community-led and community-wide responses. For many receiving support only at the individual level for relocation or other adaptive responses, individual and community harm is perpetuated through the loss of culture and identity incurred through forced assimilation policies. Often, challenges dealt to frontline communities are founded on centuries of injustices. Can these challenges of both norms and policies be addressed? Can we develop socially, culturally, environmentally, and economically just sustainable adaptation processes that supports community responses, maintenance and evolution of traditions, and rejuvenates regenerative life-supporting ecosystems? This article brings together Indigenous community leaders, knowledge-holders, and allied collaborators from Louisiana, Hawai‘i, Alaska, Borikén/Puerto Rico, and the Marshall Islands, to share their stories and lived experiences of the relocation and other adaptive challenges in their homelands and territories, the obstacles posed by the state or regional governments in community adaptation efforts, ideas for transforming the research paradigm from expecting communities to answer scientific questions to having scientists address community priorities, and the healing processes that communities are employing. The contributors are connected through the Rising Voices Center for Indigenous and Earth Sciences, which brings together Indigenous, tribal, and community leaders, atmospheric, social, biological, and ecological scientists, students, educators, and other experts, and facilitates intercultural, relational-based approaches for understanding and adapting to extreme weather and climate events, climate variability, and climate change.

Resource availability and heterogeneity shape the self‐organisation of regular spatial patterning - Jessica A. Castillo Vardaro; Juan A. Bonachela; Christopher C. M. Baker; Malin L. Pinsky; Daniel F. Doak; Robert M. Pringle; Corina E. Tarnita (Ecology Letters, 2021)
Explaining large‐scale ordered patterns and their effects on ecosystem functioning is a fundamental and controversial challenge in ecology. Here, we coupled empirical and theoretical approaches to explore how competition and spatial heterogeneity govern the regularity of colony dispersion in fungus‐farming termites. Individuals from different colonies fought fiercely, and inter‐nest distances were greater when nests were large and resources scarce—as expected if competition is strong, large colonies require more resources and foraging area scales with resource availability. Building these principles into a model of inter‐colony competition showed that highly ordered patterns emerged under high resource availability and low resource heterogeneity. Analysis of this dynamical model provided novel insights into the mechanisms that modulate pattern regularity and the emergent effects of these patterns on system‐wide productivity. Our results show how environmental context shapes pattern formation by social‐insect ecosystem engineers, which offers one explanation for the marked variability observed across ecosystems.

Exposure duration modulates the response of Caribbean corals to global change stressors - Hannah E. Aichelman; Colleen B. Bove; Karl D. Castillo; Jessica M. Boulton; Alyssa C. Knowlton; Olivia C. Nieves; Justin B. Ries; Sarah W. Davies (Limnology and Oceanography, 2021)
Global change, including rising temperatures and acidification, threatens corals globally. Although bleaching events reveal fine‐scale patterns of resilience, traits enabling persistence under global change remain elusive. We conducted a 95‐d controlled‐laboratory experiment investigating how duration of exposure to warming (~28, 31°C), acidification ( p CO 2 ~ 343 [present day], ~663 [end of century], ~3109 [extreme] μ atm), and their combination influences physiology of reef‐building corals ( Siderastrea siderea , Pseudodiploria strigosa ) from two reef zones on the Belize Mesoamerican Barrier Reef System. Every 30 d, net calcification rate, host protein and carbohydrate, chlorophyll a , and symbiont density were quantified for the same coral individual to characterize acclimation potential under global change. Coral physiologies of the two species were differentially affected by stressors and exposure duration was found to modulate these responses. Siderastrea siderea exhibited resistance to end of century p CO 2 and temperature stress, but calcification was negatively affected by extreme p CO 2 . However, S. siderea calcification rates remained positive after 95 d of extreme p CO 2 conditions, suggesting acclimation. In contrast, P. strigosa was more negatively influenced by elevated temperatures, which reduced most physiological parameters. An exception was nearshore P. strigosa , which maintained calcification rates under elevated temperature, suggesting local adaptation to the warmer environment of their natal reef zone. This work highlights how tracking coral physiology across various exposure durations can capture acclimatory responses to global change stressors.

Assisted phytoremediation of lead contaminated soil using Atriplex halimus and its effect on some soil physical properties - E. Acuña; B. Castillo; M. Queupuan; M. Casanova; Y. Tapia (International Journal of Environmental Science and Technology, 2021)

Extreme freezing in the Sonoran Desert, Mexico: Intense and short‐duration events - Jorge Cortés‐Ramos; Luis M. Farfán; Luis Brito‐Castillo (International Journal of Climatology, 2021)
Freezing temperatures are responsible for population and ecosystem damage, and their spatial extent, frequency, and duration may change in a warming world. Few studies are available concerning the analysis of extreme freezing in Mexico, and none have evaluated the probability of occurrence. This study identified the characteristics of past and recent events by applying the statistical crossing theory method to calculate the cumulative density function (CDF) of the minimum temperature ( T min ) values throughout the Sonoran Desert, including the Baja California Peninsula. Based on observations, spatial and temporal freezing evolution has been described during the period from 1970 to 2010, for which T min is less than 0°C and less than the fifth percentile of the monthly T min . Since 1970, a quasi‐homogeneous decrease has been observed in the number of freezing days. Extreme freezing was less frequent and severe during the early 1990s, which continued during the early 21st century when intense and persistent short events exhibited return periods above 20 years. After the 1990s, longer recurrence intervals for extreme T min , which overlapped with the increase in T min , implied a change in stationarity. This study found that cold‐season warming lead to less‐frequent severe freezing and a probability of change. These results represent a quantitative benchmark for current and upcoming validations of climate change scenarios.

Seasonal dynamics of natural Ostreococcus viral infection at the single cell level using VirusFISH - Yaiza M. Castillo; Irene Forn; Sheree Yau; Xosé Anxelu G. Morán; Laura Alonso‐Sáez; Néstor Arandia‐Gorostidi; Dolors Vaqué; Marta Sebastián (Environmental Microbiology, 2021)
Summary Ostreococcus is a cosmopolitan marine genus of phytoplankton found in mesotrophic and oligotrophic waters, and the smallest free‐living eukaryotes known to date, with a cell diameter close to 1 μm. Ostreococcus has been extensively studied as a model system to investigate viral–host dynamics in culture, yet the impact of viruses in naturally occurring populations is largely unknown. Here, we used Virus Fluorescence in situ Hybridization (VirusFISH) to visualize and quantify viral‐host dynamics in natural populations of Ostreococcus during a seasonal cycle in the central Cantabrian Sea (Southern Bay of Biscay). Ostreococcus were predominantly found during summer and autumn at surface and 50 m depth, in coastal, mid‐shelf and shelf waters, representing up to 21% of the picoeukaryotic communities. Viral infection was only detected in surface waters, and its impact was variable but highest from May to July and November to December, when up to half of the population was infected. Metatranscriptomic data available from the mid‐shelf station unveiled that the Ostreococcus population was dominated by the species O. lucimarinus . This work represents a proof of concept that the VirusFISH technique can be used to quantify the impact of viruses on targeted populations of key microbes from complex natural communities.

Freshwater pearl culture in Mexico: historic context, present status and future perspectives - Pedro E. Saucedo; Héctor Acosta‐Salmón; Douglas McLaurin‐Moreno; Alfonso Castillo‐Domínguez; Carolina E. Melgar‐Valdés; José M. Mazón‐Suástegui (Reviews in Aquaculture, 2021)
We revise the historic context of freshwater pearl culture in Asia, updating the present situation and perspectives of this activity in Mexico, and, possibly, in some Latin American countries. The review is based on the results of ten years of research conducted in southeast Mexico (state of Tabasco) to firstly determine the demography of freshwater mussel stocks and, based on this information, identify a target species with a higher potential for pearl farming: the fatmucket mussel Psoronaias crocodilorum . The main advances relative to the seeding technique for keshi pearl production and composite technique for half‐pearl (mabe) production are detailed and placed under perspective with China, as today's greatest producer of freshwater pearls. After ten years, several cohorts of keshi and mabe pearls have been produced, representing the first of their kind in Latin America. Although the yield and quality of these pearls has gradually been improved, some aspects of the keshi technique (preparation and seeding of the donor's mantle into the host's mantle) still require further optimisation. To promote social development, one of the goals of the project included the involvement of local communities in the manufacture and selling of handcrafts made from the shell. The other goal was to share the main outcomes derived from the keshi and mabe techniques with academics, producers, and government authorities through a series of training workshops aimed to create awareness in the local communities for the potential of freshwater pearl culture in Tabasco as an aquaculture‐based, environmentally friendly and viable model for socioeconomic development.

Anti-inflammatory and sedative activities of Peperomia galioides : in vivo studies in mice - Isabel Wilches; Priscila Jiménez-Castillo; Nancy Cuzco; M. Victoria Clos; Francesc Jiménez-Altayó; Eugenia Peñaherrera; Lourdes Jerves-Andrade; Vladimiro Tobar; Yvan Vander Heyden; Fabián Leon-Tamariz; Elisabet Vila (Natural Product Research, 2021)

Precipitation of Heavy Metal Ions (Cu, Fe, Zn, and Pb) from Mining Flotation Effluents Using a Laboratory-Scale Upflow Anaerobic Sludge Blanket Reactor - Manuel José Leal-Gutiérrez; Rodrigo Cuéllar-Briseño; Andrei M. Castillo-Garduño; Marisela Bernal-González; Ángel Enrique Chávez-Castellanos; Julio Alberto Solís-Fuentes; María-del-Carmen Durán-Domínguez-de-Bazúa; Enrique Rodolfo Bazúa-Rueda (Water, Air, & Soil Pollution, 2021)

Seed bank dynamics of the annual halophyte Salicornia ramosissima: towards a sustainable exploitation of its wild populations - Alejandro Polo; Alba Fragoso; María D. Infante-Izquierdo; Francisco J. J. Nieva; Adolfo F. Muñoz-Rodríguez; Jesús M. Castillo (Plant Ecology, 2021)

Estimating carbon isotope discrimination and grain yield of bread wheat grown under water-limited and full irrigation conditions by hyperspectral canopy reflectance and multilinear regression analysis - Miguel Garriga; Sebastián Romero-Bravo; Félix Estrada; Ana M. Méndez-Espinoza; Luis González-Martínez; Iván A. Matus; Dalma Castillo; Gustavo A. Lobos; Alejandro Del Pozo (International Journal of Remote Sensing, 2021)

The Impact of Wave Model Source Terms and Coupling Strategies to Rapidly Developing Waves across the North-West European Shelf during Extreme Events - Nieves G. Valiente; Andrew Saulter; John M. Edwards; Huw W. Lewis; Juan M. Castillo Sanchez; Diego Bruciaferri; Christopher Bunney; John Siddorn (Journal of Marine Science and Engineering, 2021)
Prediction of severe natural hazards requires accurate forecasting systems. Recently, there has been a tendency towards more integrated solutions, where different components of the Earth system are coupled to explicitly represent the physical feedbacks between them. This study focuses on rapidly developing waves under extratropical storms to understand the impact of different wave source term parameterisations in the WAVEWATCH III (WWIII) model (ST4 and ST6) and coupling strategies (surface roughness closure versus surface stress closure) on the accuracy of the Met Office regional atmosphere-ocean-wave coupled research system for the north-west (NW) European shelf (UKC4). Results of a study focused on simulations during winter 2013/14 demonstrate that ST6 allows for a faster wave growth than the ST4 parameterisation but might degrade low to mid energy wave states. The difference between ST6 and ST4 in wave growth is larger for higher wind speeds and short fetches. The experiment with ST4 and roughness closure consistently under-predicts the wave growth in those locations where fetch dependence is an important factor (i.e., seas at the East (E) of Ireland and the UK for storms coming from the NW-WNW). The implementation in the wave model of ST6 physics with the stress closure coupling strategy appears to improve growth of young wind-seas, reducing bias in those locations where the storms are underestimated. The slower wave growth when using surface roughness closure seems to be related to an underestimation of the momentum transfer computed by the wave model when coupling the wind speeds. For very young to young wind seas, this can be overcome when the surface stress is computed by the atmospheric model and directly passed to the ocean.

Secundiflorol G isolated from Aeschynomene fascicularis , a Mayan medicinal plant, induces apoptosis in cervical cancer cells - Cristina M. Castillo-Bautista; Luis W. Torres-Tapia; Alfredo Lagunas-Martínez; Carla O. Contreras-Ochoa; Sergio R. Peraza-Sanchez; Rosa Moo-Puc (Natural Product Research, 2021)

Quantifying the Impact on Stormwater Management of an Innovative Ceramic Permeable Pavement Solution - Jesica Tamara Castillo-Rodríguez; I. Andrés-Doménech; M. Martín; I. Escuder-Bueno; S. Perales-Momparler; J. Mira-Peidro (Water Resources Management, 2021)

Variation in sexual reproductive output among exotic taxa of Spartina (Poaceae) - M. Dolores Infante-Izquierdo; Adolfo. F. Muñoz-Rodríguez; F. Javier J. Nieva; Alejandro Polo-Ávila; Enrique Sánchez-Gullón; Jesús J. Soriano; Israel Sanjosé; Brenda J. Grewell; Jesús M. Castillo (Aquatic Ecology, 2021)

A Matter of Scale: Population Genomic Structure and Connectivity of Fisheries At-Risk Common Dolphins (Delphinus delphis) From Australasia - Andrea Barceló; Jonathan Sandoval-Castillo; Karen A. Stockin; Kerstin Bilgmann; Catherine R. M. Attard; Nikki Zanardo; Guido J. Parra; Krista Hupman; Isabella M. Reeves; Emma L. Betty; Gabriela Tezanos-Pinto; Luciano B. Beheregaray; et al. (Frontiers in Marine Science, 2021)
An understanding of population structure and connectivity at multiple spatial scales is required to assist wildlife conservation and management. This is particularly critical for widely distributed and highly mobile marine mammals subject to fisheries by-catch. Here, we present a population genomic assessment of a near-top predator, the common dolphin ( Delphinus delphis ), which is incidentally caught in multiple fisheries across the Australasian region. The study was carried out using 14,799 ddRAD sequenced genome-wide markers genotyped for 478 individuals sampled at multiple spatial scales across Australasia. A complex hierarchical metapopulation structure was identified, with three highly distinct and genetically diverse regional populations at large spatial scales (>1,500 km). The populations inhabit the southern coast of Australia, the eastern coast of Australia, New Zealand, and Tasmania, with the latter also showing a considerable level of admixture to Australia's east coast. Each of these regional populations contained two to four nested local populations (i.e., subpopulations) at finer spatial scales, with most of the gene flow occurring within distances of 50 to 400 km. Estimates of contemporary migration rates between adjacent subpopulations ranged from 6 to 25%. Overall, our findings identified complex common dolphin population structure and connectivity across state and international jurisdictions, including migration and gene flow across the Tasman Sea. The results indicate that inter-jurisdictional collaboration is required to implement conservation management strategies and mitigate fisheries interactions of common dolphins across multiple spatial scales in the Australasian region.

Machine Learning as a Seismic Prior Velocity Model Building Method for Full-Waveform Inversion: A Case Study from Colombia - Ursula Iturrarán-Viveros; Andrés M. Muñoz-García; Octavio Castillo-Reyes; Khemraj Shukla (Pure and Applied Geophysics, 2021)
We use machine learning algorithms (artificial neural networks, ANNs) to estimate petrophysical models at seismic scale combining well-log information, seismic data and seismic attributes. The resulting petrophysical images are the prior inputs in the process of full-waveform inversion (FWI). We calculate seismic attributes from a stacked reflected 2-D seismic section and then train ANNs to approximate the following petrophysical parameters: P-wave velocity ( $$V_\mathrm{{p}}$$ V p ), density ( $$ρ $$ ρ ) and volume of clay ( $$V_\mathrm{{clay}}$$ V clay ). We extend the use of the $$V_\mathrm{{clay}}$$ V clay by constraining it with the well lithology and we establish two classes: sands and shales. Consequently, machine learning allows us to build an initial estimate of the earth property model ( $$V_\mathrm{{p}}$$ V p ), which is iteratively refined to produce a synthetic seismogram that matches the observed seismic data. We apply the 1-D Kennett method as a forward modeling tool to create synthetic data with the images of $$V_\mathrm{{p}}$$ V p , $$ρ $$ ρ and the thickness of layers (sands or shales) obtained with the ANNs. A nonlinear least-squares inversion algorithm minimizes the residual (or misfit) between observed and synthetic full-waveform data, which improves the $$V_\mathrm{{p}}$$ V p resolution. In order to show the advantage of using the ANN velocity model as the initial velocity model for the inversion, we compare the results obtained with the ANNs and two other initial velocity models. One of these alternative initial velocity models is computed via P-wave impedance, and the other is achieved by velocity semblance analysis: root-mean-square velocity (RMS). The results are in good agreement when we use $$ρ $$ ρ and $$V_\mathrm{{p}}$$ V p obtained by ANNs. However, the results are poor and the synthetic data do not match the real acquired data when using the semblance velocity model and the $$ρ $$ ρ from the well log (constant for the entire 2-D section). Nevertheless, the results improve when including $$ρ $$ ρ , the layered structure driven by the $$V_\mathrm{{clay}}$$ V clay (both obtained with ANNs) and the semblance velocity model. When doing inversion starting with the initial $$V_\mathrm{{p}}$$ V p model estimated using the P-wave impedance, there is some gain of the final $$V_\mathrm{{p}}$$ V p with respect to the RMS initial $$V_\mathrm{{p}}$$ V p . To assess the quality of the inversion of $$V_\mathrm{{p}}$$ V p , we use the information for two available wells and compare the final $$V_\mathrm{{p}}$$ V p obtained with ANNs and the final $$V_\mathrm{{p}}$$ V p computed with the P-wave impedance. This shows the benefit of employing ANNs estimations as prior models during the inversion process to obtain a final $$V_\mathrm{{p}}$$ V p that is in agreement with the geology and with the seismic and well-log data. To illustrate the computation of the final velocity model via FWI, we provide an algorithm with the detailed steps and its corresponding GitHub code.

Optimization of theoretical maximal quantity of cells to immobilize on solid supports in the rational design of immobilized derivatives strategy - Freddy Castillo-Alfonso; Marcia M. Rojas; Irina Salgado-Bernal; María E. Carballo; Roberto Olivares-Hernández; Jorge González-Bacerio; José M. Guisán; Alberto del Monte-Martínez (World Journal of Microbiology and Biotechnology, 2021)

Specific tissue proteins 1 and 6 are involved in root biology during normal development and under symbiotic and pathogenic interactions in Medicago truncatula - Lucía Albornos; Virginia Casado-del-Castillo; Ignacio Martín; José M. Díaz-Mínguez; Emilia Labrador; Berta Dopico (Planta, 2021)

Autoregressive process of monthly rainfall amounts in Catalonia ( NE Spain) and improvements on predictability of length and intensity of drought episodes - Xavier Lana; Raül Rodríguez‐Solà; M. Dolors Martínez; M. Carmen Casas‐Castillo; Carina Serra; Ricard Kirchner (International Journal of Climatology, 2021)
Advantages offered by a pluviometric network in Catalonia (NE Spain) have permitted a detailed analysis of the two primary results derived from the autoregressive ARIMA process applied to monthly rainfall amounts. The first was the spatial distribution of the necessary number of previous monthly amounts needed to predict the next amount. The second was the spatial distribution of discrepancies between the real recorded amount and those derived from the autoregressive process. The heterogeneous spatial distribution of both parameters of the ARIMA process is in accordance with the complex spatial distribution of the monthly rainfall regime in Catalonia and fractal/multifractal analyses of several monthly rainfall time series. The statistical distribution of monthly discrepancies also permits a prediction of the probable evolution at monthly scale of drought episodes in terms of length and accumulated rainfall deficit. The results of the ARIMA algorithm are characterized by a few cases of rain gauges with remarkable differences (10–20 mm⋅month –1 ) between real and autoregressive amounts, a predominant number of emplacements lowering 10 mm⋅month –1 and a not negligible number of cases with discrepancies lower than 5 mm⋅month –1 . In terms of percentages with respect to average monthly amounts, most of discrepancies do not exceed 15%, and only in a very few cases they are within the 20–40% range. It is also worth mentioning that the discrepancies between real and predicted drought lengths use to be no longer than 1 month. Results corresponding to monthly series recorded at two Earth Sciences observatories are described with more detail to illustrate the advantages offered by the ARIMA autoregressive process in the prediction of beginning, continuity and end of drought episodes.

Prior cortical activity differences during an action observation plus motor imagery task related to motor adaptation performance of a coordinated multi-limb complex task - J. Ignacio Serrano; Daniel Muñoz-García; Raúl Ferrer-Peña; Victor D’eudeville; Marta Brero; Maxime Boisson; M. Dolores del Castillo (Cognitive Neurodynamics, 2020)

Spatial patterning of soil microbial communities created by fungus‐farming termites - Christopher C. M. Baker; Jessica A. Castillo Vardaro; Daniel F. Doak; Johan Pansu; Jérémy Puissant; Robert M. Pringle; Corina E. Tarnita (Molecular Ecology, 2020)
Spatially overdispersed mounds of fungus‐farming termites (Macrotermitinae) are hotspots of nutrient availability and primary productivity in tropical savannas, creating spatial heterogeneity in communities and ecosystem functions. These termites influence the local availability of nutrients in part by redistributing nutrients across the landscape, but the links between termite ecosystem engineering and the soil microbes that are the metabolic agents of nutrient cycling are little understood. We used DNA metabarcoding of soils from Odontotermes montanus mounds to examine the influence of termites on soil microbial communities in a semi‐arid Kenyan savanna. We found that bacterial and fungal communities were compositionally distinct in termite‐mound topsoils relative to the surrounding savanna, and that bacterial communities were more diverse on mounds. The higher microbial alpha and beta diversity associated with mounds created striking spatial patterning in microbial community composition, and boosted landscape‐scale microbial richness and diversity. Selected enzyme assays revealed consistent differences in potential enzymatic activity, suggesting links between termite‐induced heterogeneity in microbial community composition and the spatial distribution of ecosystem functions. We conducted a large‐scale field experiment in which we attempted to simulate termites’ effects on microbes by fertilizing mound‐sized patches; this altered both bacterial and fungal communities, but in a different way than natural mounds. Elevated levels of inorganic nitrogen, phosphorus and potassium may help to explain the distinctive fungal communities in termite‐mound soils, but cannot account for the distinctive bacterial communities associated with mounds.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Characterization of standardized heavy rainfall profiles for Barcelona city: clustering, rain amounts and intensity peaks - X. Lana; R. Rodríguez-Solà; M. D. Martínez; M. C. Casas-Castillo; C. Serra; A. Burgueño (Theoretical and Applied Climatology, 2020)

Eukaryotic plankton communities across reef environments in Bocas del Toro Archipelago, Panamá - Andrea M. Rodas; Rachel M. Wright; Logan K. Buie; Hannah E. Aichelman; Karl D. Castillo; Sarah W. Davies (Coral Reefs, 2020)

Serum CGRP, VIP, and PACAP usefulness in migraine: a case–control study in chronic migraine patients in real clinical practice - Sara Pérez-Pereda; María Toriello-Suárez; Gonzalo Ocejo-Vinyals; Sandra Guiral-Foz; Jesús Castillo-Obeso; Silvia Montes-Gómez; Rosa M. Martínez-Nieto; Fernando Iglesias; Vicente González-Quintanilla; Agustin Oterino (Molecular Biology Reports, 2020)

Health-promoting properties of oleocanthal and oleacein: Two secoiridoids from extra-virgin olive oil - Julián Lozano-Castellón; Anallely López-Yerena; José Fernando Rinaldi de Alvarenga; Jaume Romero del Castillo-Alba; Anna Vallverdú-Queralt; Elvira Escribano-Ferrer; Rosa M. Lamuela-Raventós (Critical Reviews in Food Science and Nutrition, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Nutritional factors modulating plant and fruit susceptibility to pathogens: BARD workshop, Haifa, Israel, February 25–26, 2018 - Dov Prusky; Leandro José de Assis; Riccardo Baroncelli; Ernesto P. Benito; Virginia Casado del Castillo; Timothy Chaya; Shay Covo; José María Díaz-Mínguez; Nicole M. Donofrio; Eduardo Espeso; Tânia Ribeiro Fernandes; Gustavo H. Goldman; et al. (Phytoparasitica, 2020)

Effectiveness of the Sex Pheromone for Monitoring Stenoma catenifer (Lepidoptera: Elachistidae) in Avocado Orchards - L. Cruz-López; M. A. Vázquez; A. Castillo (Neotropical Entomology, 2020)

Heavy metals (lead, cadmium and zinc) from street dust in Monterrey, Mexico: ecological risk index - D. Castillo-Nava; M. Elias-Santos; U. J. López-Chuken; A. Valdés-González; L. G. de la Riva-Solís; M. P. Vargas-Pérez; L. J. Galán-Wong; H. A. Luna-Olvera (International Journal of Environmental Science and Technology, 2020)

White-Faced Capuchin, Cebus capucinus imitator, Hammerstone and Anvil Tool Use in Riparian Habitats on Coiba Island, Panama - Claudio M. Monteza-Moreno; Tamara Dogandžić; Kevin A. McLean; Pedro L. Castillo-Caballero; Zarluis Mijango-Ramos; Evelyn Del Rosario-Vargas; Margaret C. Crofoot; Brendan J. Barrett (International Journal of Primatology, 2020)

Improving ozonation to remove carbamazepine through ozone-assisted catalysis using different NiO concentrations - Claudia M. Aguilar; Jorge Vazquez-Arenas; Omar O. Castillo-Araiza; Julia L. Rodríguez; Isaac Chairez; Eric Salinas; Tatiana Poznyak (Environmental Science and Pollution Research, 2020)

A morphological, reproductive, and molt phenology database for 379 bird species from the Colombian Tropical Andes - Leydy J. Cardona‐Salazar; Yeny A. Benavides‐Ossa; Ángela M. Vargas‐Daza; Juan F. Betancurt‐Grisales; Mauricio Bohada‐Murillo; Estefani T. Martínez‐Sánchez; Marelid Cardona‐Romero; Ana Busi; William D. Tobón‐Escobar; Mateo Ortíz‐Giraldo; Daniela Gómez Castillo; Johnathan Alvarez‐Londoño; et al. (Ecology, 2020)
The Colombian Tropical Andes are one of the regions with highest bird diversity on Earth. However, information on bird morphology, reproductive phenology, and molt is particularly scarce in this region. Also, this region is heavily impacted by deforestation, and it is vulnerable to climate change. Hence, providing baseline information on life history and morphological traits will be essential to support future research on functional diversity, climate change effects, conservation, evolution, and phenology. To fill this gap, we have compiled information on bird distribution, morphology, molt, and reproductive phenology at 52 localities of the Department of Caldas, covering an elevation range between 148 and 3845 m. This compilation comprises a wide range of habitats, including native forests, forestry plantations, croplands, and paramo. Our database presents information for 3,398 records belonging to 379 bird species (representing 23 orders, 53 families, and 258 genera). From those records, 2,843 correspond to information collected in the field between 2008 and 2019, and the remaining 555 records correspond to specimens deposited in the Natural History Museum of the Caldas University, collected between 1969 and 2014. We measured nine morphological traits from all specimens: total culmen, gape, bill width, bill depth, tarsus, wing length, tail length, total length, and mass. We also have reproductive condition information for 257 species and molt information available for 378 species. The information contained in this data set represents ~20% of the Colombian avifauna and ~11% of the bird species richness in South America. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Fruit Set, Seed Viability and Germination of the European Native Spartina maritima in Southwest Iberian Peninsula - M. Dolores Infante-Izquierdo; Jesús M. Castillo; F. Javier J. Nieva; Ioana D. Rotundu; Francesca T. David; Brenda J. Grewell; Adolfo F. Muñoz-Rodríguez (Wetlands, 2020)

Influence of regional and seasonal rainfall patterns on the ratio between fixed and unrestricted measured intervals of rainfall amounts - Alba Llabrés-Brustenga; Anna Rius; Raúl Rodríguez-Solà; M. Carmen Casas-Castillo (Theoretical and Applied Climatology, 2020)

Mexico ants: incidence and abundance along the Nearctic–Neotropical interface - Wesley Dáttilo; Miguel Vásquez‐Bolaños; Diana A. Ahuatzin; Reuber Antoniazzi; Edgar Chávez‐González; Erick Corro; Pedro Luna; Roger Guevara; Fabricio Villalobos; Ricardo Madrigal‐Chavero; Jéssica C. de Faria Falcão; Adrián Bonilla‐Ramírez; et al. (Ecology, 2020)
Mexico is one of the most biodiverse countries in the world, with an important proportion of endemism mainly because of the convergence of the Nearctic and Neotropical biogeographic regions, which generate great diversity and species turnover at different spatial scales. However, most of our knowledge of the Mexican ant biota is limited to a few well‐studied taxa, and we lack a comprehensive synthesis of ant biodiversity information. For instance, most of the knowledge available in the literature on Mexican ant fauna refers only to species lists by states, or is focused on only a few regions of the country, which prevents the study of several basic and applied aspects of ants, from diversity and distribution to conservation. Our aims in this data paper are therefore (1) to compile all the information available regarding ants across the Mexican territory, and (2) to identify major patterns in the gathered data set and geographic gaps in order to direct future sampling efforts. All records were obtained from raw data, including both unpublished and published information. After exhaustive filtering and updating information and synonyms, we compiled a total of 21,731 records for 887 ant species distributed throughout Mexico from 1894 to 2018. These records were concentrated mainly in the states of Chiapas ( n = 6,902, 32.76%) and Veracruz de Ignacio de la Llave ( n = 4,329, 19.92%), which together comprise half the records. The subfamily with the highest number of records was Myrmicinae ( n = 10,458 records, 48.12%), followed by Formicinae ( n = 3,284, 15.11%) and Ponerinae ( n = 1,914, 8.8%). Most ant records were collected in the Neotropical region of the country ( n = 12,646, 58.19%), followed by the Mexican transition zone ( n = 5,237, 24.09%) and the Nearctic region ( n = 3,848, 17.72%). Native species comprised 95.46% of the records ( n = 20,745). To the best of our knowledge, this is the most complete data set available to date in the literature for the country. We hope that this compilation will encourage researchers to explore different aspects of the population and community research of ants at different spatial scales, and to aid in the establishment of conservation policies and actions. There are no copyright restrictions. Please cite this data paper when using its data for publications or teaching events.

The role of purinergic P2Y12 and P2Y13 receptors in ADPβS-induced inhibition of the cardioaccelerator sympathetic drive in pithed rats - Belinda Villanueva-Castillo; Eduardo Rivera-Mancilla; Kristian Agmund Haanes; Antoinette MaassenVanDenBrink; Carlos M. Villalón (Purinergic Signalling, 2020)

Synthesis, in vitro antigiardial activity, SAR analysis and docking study of substituted chalcones - David Cáceres-Castillo; Rubén M. Carballo; Ramiro Quijano-Quiñones; Gumersindo Mirón-López; Manlio Graniel-Sabido; Rosa E. Moo-Puc; Gonzalo J. Mena-Rejón (Medicinal Chemistry Research, 2020)

Combining Isotopic Techniques to Assess Historical Sediment Delivery in a Forest Catchment in Central Chile - C. Bravo-Linares; P. Schuller; A. Castillo; A. Salinas-Curinao; L. Ovando-Fuentealba; E. Muñoz-Arcos; A. Swales; M. Gibbs; G. Dercon (Journal of Soil Science and Plant Nutrition, 2020)

What are the effects of exercise training in childhood cancer survivors? A systematic review - Javier S. Morales; Pedro L. Valenzuela; Alba M. Herrera-Olivares; Cecilia Rincón-Castanedo; Asunción Martín-Ruiz; Adrián Castillo-García; Carmen Fiuza-Luces; Alejandro Lucia (Cancer and Metastasis Reviews, 2020)

Update of the population size and breeding performance of gentoo penguins (Pygoscelis papua) at Stranger Point/Cabo Funes, South Shetland Islands - Mariana A. Juáres; Ricardo Casaux; Javier Negrete; Ayelen Rios; Martín Castillo; Néstor R. Coria; Mercedes M. Santos (Polar Biology, 2020)

Clinical isolates of Escherichia coli are resistant both to antibiotics and organotin compounds - M. Aguilar-Santelises; J. Castillo-Vera; R. Gonzalez-Molina; A. Garcia del Valle; M. Cruz Millan; L. Aguilar-Santelises (Folia Microbiologica, 2020)

Accumulation of Sulphur in Atriplex nummularia Cultivated in Mine Tailings and Effect of Organic Amendments Addition - Y. Tapia; B. Loch; B. Castillo; E. Acuña; M. Casanova; O. Salazar; P. Cornejo; M. Antilén (Water, Air, & Soil Pollution, 2020)

Utilization of naproxen by Amycolatopsis sp. Poz 14 and detection of the enzymes involved in the degradation metabolic pathway - B. M. Alanis-Sánchez; S. M. Pérez-Tapia; S. Vázquez-Leyva; I. Mejía-Calvo; Z. Macías-Palacios; L. Vallejo-Castillo; C. M. Flores-Ortiz; C. Guerrero-Barajas; J. A. Cruz-Maya; J. Jan-Roblero (World Journal of Microbiology and Biotechnology, 2019)

Field Performance of Two Methods for Detection of Poliovirus in Wastewater Samples, Mexico 2016–2017 - Concepción F. Estívariz; Elda E. Pérez-Sánchez; Anita Bahena; Cara C. Burns; Howard E. Gary; Herlinda García-Lozano; Gloria Rey-Benito; Silvia Peñaranda; Katy V. Castillo-Montufar; Raúl S. Nava-Acosta; John Scott Meschke; M. Steven Oberste; et al. (Food and Environmental Virology, 2019)

Genetically informed captive breeding of hybrids of an extinct species of Galapagos tortoise - Maud C. Quinzin; Jonathan Sandoval‐Castillo; Joshua M. Miller; Luciano B. Beheregaray; Michael A. Russello; Elizabeth A. Hunter; James P. Gibbs; Washington Tapia; Freddy Villalva; Adalgisa Caccone (Conservation Biology, 2019)
Hybridization poses a major challenge for species conservation because it threatens both genetic integrity and adaptive potential. Yet, hybridization can occasionally offer unprecedented opportunity for species recovery if the genome of an extinct taxon is present among living hybrids such that selective breeding could recapture it. We explored the design elements for establishing a captive‐breeding program for Galapagos tortoises ( Chelonoidis spp.) built around individuals with admixed ancestry involving an extinct species. The target individuals were hybrids between the extinct species from Floreana Island, C. niger , and an extant species, C. becki , which were recently found in the endemic range of C. becki , from Wolf Volcano on Isabela Island. We combined genotypic data from 35 tortoises with high ancestry from C. niger with forward‐in‐time simulations to explore captive breeding strategies that maximized overall genetic diversity and ancestry from C. niger while accommodating resource constraints, species biology, and the urgency to return tortoises to Floreana Island for facilitating ecosystem restoration. Overall genetic diversity was maximized when in the simulation tortoises were organized in relatively small breeding groups. Substantial amounts of the C. niger genome were captured despite limited resources available for selectively breeding tortoises in captivity. Genetic diversity was maximized when captive‐bred offspring were released to the wild rather than being used as additional breeders. Our results provide genetic‐based and practical guidance on the inclusion of hybrids with genomic representation from extinct taxa into species restoration programs and informs the ongoing debate on the value of hybrids in biodiversity conservation.

Availability of copper in mine tailings with humic substance addition and uptake by Atriplex halimus - Y. Tapia; M. Casanova; B. Castillo; E. Acuña; J. Covarrubias; M. Antilén; A. Masaguer (Environmental Monitoring and Assessment, 2019)

The effects of commonly used anaesthetics on colour measurements across body regions in the poeciliid fish, Girardinus metallicus - Erin M. Wojan; Nalana C. Carreiro; David A. Clendenen; Heather M. Neldner; Crystal Castillo; Susan M. Bertram; Gita R. Kolluru (Journal of Fish Biology, 2019)
The effects of common anaesthetics on the hue, saturation and brightness measurements of the poeciliid fish Girardinus metallicus were investigated in two experiments. For both experiments the coloration of four body regions was measured from digital images of the same males obtained under three conditions: (1) control (in a water‐filled chamber); (2) anaesthetised with MS‐222; and (3) anaesthetised with eugenol (clove oil). In experiment 1 anaesthetised fish were photographed out of water. In experiment 2 all photographs were taken in a water‐filled chamber. Anaesthetics altered coloration in both experiments. In the more methodologically consistent experiment 2 we found significantly different hue, increased saturation and decreased brightness in anaesthetic v . control conditions, consistent with darkening caused by the anaesthetics. The body regions differed in coloration consistent with countershading but did not differentially change in response to anaesthesia. These findings suggest that photographing fish in a water‐filled chamber without anaesthetic is preferable for obtaining digital images for colour analysis and that multiple body regions of fish should be measured when assessing coloration patterns meaningful in behavioural contexts, to account for the gradients caused by countershading. We are encouraged that some researchers employ such methods already and caution against using anaesthetics except when absolutely necessary for immobilisation.

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Microsatellite markers in Spanish lime (Melicoccus bijugatus Jacq., Sapindaceae), a neglected Neotropical fruit crop - Jaime Martínez-Castillo; Renée S. Arias; Rubén H. Andueza-Noh; Matilde M. Ortiz-García; Brian M. Irish; Brian E. Scheffler (Genetic Resources and Crop Evolution, 2019)

Deep reef fishes in the world’s epicenter of marine biodiversity - Hudson T. Pinheiro; Bart Shepherd; Cristina Castillo; Rene A. Abesamis; Joshua M. Copus; Richard L. Pyle; Brian D. Greene; Richard R. Coleman; Robert K. Whitton; Emma Thillainath; Abner A. Bucol; Matthew Birt; et al. (Coral Reefs, 2019)

A physiologically-motivated model of cystic fibrosis liquid and solute transport dynamics across primary human nasal epithelia - Florencio Serrano Castillo; Carol A. Bertrand; Michael M. Myerburg; Monica E. Shapiro; Timothy E. Corcoran; Robert S. Parker (Journal of Pharmacokinetics and Pharmacodynamics, 2019)

Assessing the viral content of uncultured picoeukaryotes in the global‐ocean by single cell genomics - Yaiza M. Castillo; Jean‐François Mangot; Luiz Felipe Benites; Ramiro Logares; Megumi Kuronishi; Hiroyuki Ogata; Olivier Jaillon; Ramon Massana; Marta Sebastián; Dolors Vaqué (Molecular Ecology, 2019)
Viruses are the most abundant biological entities on Earth and have fundamental ecological roles in controlling microbial communities. Yet, although their diversity is being increasingly explored, little is known about the extent of viral interactions with their protist hosts as most studies are limited to a few cultivated species. Here, we exploit the potential of single‐cell genomics to unveil viral associations in 65 individual cells of 11 essentially uncultured stramenopiles lineages sampled during the Tara Oceans expedition. We identified viral signals in 57% of the cells, covering nearly every lineage and with narrow host specificity signal. Only seven out of the 64 detected viruses displayed homologies to known viral sequences. A search for our viral sequences in global ocean metagenomes showed that they were preferentially found at the DCM and within the 0.2–3 µm size fraction. Some of the viral signals were widely distributed, while others geographically constrained. Among the viral signals we detected an endogenous mavirus virophage potentially integrated within the nuclear genome of two distant uncultured stramenopiles. Virophages have been previously reported as a cell's defence mechanism against other viruses, and may therefore play an important ecological role in regulating protist populations. Our results point to single‐cell genomics as a powerful tool to investigate viral associations in uncultured protists, suggesting a wide distribution of these relationships, and providing new insights into the global viral diversity.

Structure and genetic diversity in wild and cultivated populations of Zapote mamey (Pouteria sapota, Sapotaceae) from southeastern Mexico: its putative domestication center - Jaime Martínez-Castillo; Nassib H. Blancarte-Jasso; Gabriel Chepe-Cruz; Noemí G. Nah-Chan; Matilde M. Ortiz-García; Renee S. Arias (Tree Genetics & Genomes, 2019)

Quality control process of the daily rainfall series available in Catalonia from 1855 to the present - Alba Llabrés-Brustenga; Anna Rius; Raúl Rodríguez-Solà; M. Carmen Casas-Castillo; Angel Redaño (Theoretical and Applied Climatology, 2019)

Intra-inflorescence variation in reproductive traits of Conopholis alpina (Orobanchaceae): effect of flower maturation pattern and resource competition - Itzel L. Castillo-Sánchez; Dulce M. Figueroa-Castro (Plant Ecology, 2019)

Diffuse Hydrothermal Venting: A Hidden Source of Iron to the Oceans - Alastair J. M. Lough; Douglas P. Connelly; William B. Homoky; Jeffrey A. Hawkes; Valerie Chavagnac; Alain Castillo; Majid Kazemian; Ko-ichi Nakamura; Tohru Araki; Burkhard Kaulich; Rachel A. Mills (Frontiers in Marine Science, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Evaluating the impact of atmospheric forcing and air–sea coupling on near-coastal regional ocean prediction - Huw W. Lewis; John Siddorn; Juan Manuel Castillo Sanchez; Jon Petch; John M. Edwards; Tim Smyth (Ocean Science, 2019)
Atmospheric forcing applied as ocean model boundary conditions can have a critical impact on the quality of ocean forecasts. This paper assesses the sensitivity of an eddy-resolving (1.5 km resolution) regional ocean model of the north-west European Shelf (NWS) to the choice of atmospheric forcing and atmosphere–ocean coupling. The analysis is focused on a month-long simulation experiment for July 2014 and evaluation of simulated sea surface temperature (SST) in a shallow near-coastal region to the south-west of the UK (Celtic Sea and western English Channel). Observations of the ocean and atmosphere are used to evaluate model results, with a particular focus on the L4 ocean buoy from the Western Channel Observatory as a rare example of co-located data above and below the sea surface. The impacts of differences in the atmospheric forcing are illustrated by comparing results from an ocean model run in forcing mode using operational global-scale numerical weather prediction (NWP) data with an ocean model run forced by a convective-scale regional atmosphere model. The value of dynamically representing feedbacks between the atmosphere and ocean state is assessed via the use of these model components within a fully coupled ocean–wave–atmosphere system. Simulated SSTs show considerable sensitivity to atmospheric forcing and to the impact of model coupling in near-coastal areas. A warm ocean bias relative to in situ observations in the simulation forced by global-scale NWP (0.7 K in the model domain) is shown to be reduced (to 0.4 K) via the use of the 1.5 km resolution regional atmospheric forcing. When simulated in coupled mode, this bias is further reduced (by 0.2 K). Results demonstrate much greater variability of both the surface heat budget terms and the near-surface winds in the convective-scale atmosphere model data, as might be expected. Assessment of the surface heat budget and wind forcing over the ocean is challenging due to a scarcity of observations. However, it can be demonstrated that the wind speed over the ocean simulated by the convective-scale atmosphere did not agree as well with the limited number of observations as the global-scale NWP data did. Further partially coupled experiments are discussed to better understand why the degraded wind forcing does not detrimentally impact on SST results.

Pattern Recognition Applied to Attenuation of Multiples in Subsalt Imaging - J. C. Ortiz-Alemán; J. Abreu-Torres; M. G. Orozco-del-Castillo; J. J. Hernández-Gómez (Pure and Applied Geophysics, 2019)

Neuroprotective effect of Mayan medicinal plant extracts against glutamate-induced toxicity - Cristina M. Castillo-Bautista; Luis W. Torres-Tapia; Jorge A. Rangel-Méndez; Sergio R. Peraza-Sánchez; Daniel Cortés; Iván Velasco; Rosa E. Moo-Puc (Journal of Natural Medicines, 2019)

The BeWo cell line derived from a human placental choriocarcinoma is permissive for respiratory syncytial virus infection - M. A. Velázquez-Cervantes; M. Martínez-Castillo; L. D. González-García; T. A. Vargas-Pavía; M. G. Martínez-Salazar; I. Mancilla-Herrera; G. León-Reyes; J. García-Cordero; A. C. Helguera-Repetto; M. León-Juárez (Virus Genes, 2019)

Pharmacokinetics of two dosing forms of a recrystallized enrofloxacin as hydrochloride dihydrate in tilapia (Oreochromis niloticus × Oreochromis mossambicus) - E Estrada-San Agustín; L Gutiérrez; M Bernad; H Castillo-Juárez; S Sánchez; H Sumano (Aquaculture International, 2019)

Design, synthesis and in vitro evaluation of a Dopa-organoboron compound that acts as a bladder relaxant through non-catecholamine receptors - Ana L. Ocampo-Néstor; Ruth M. López-Mayorga; Enrique F. Castillo-Henkel; Itzia I. Padilla-Martínez; José G. Trujillo-Ferrara; Marvin A. Soriano-Ursúa (Molecular Diversity, 2019)

Description of Ornithodoros montensis n. sp. (Acari, Ixodida: Argasidae), a parasite of the toad Rhinella arenarum (Amphibia, Anura: Bufonidae) in the Monte Desert of Argentina - José M. Venzal; Gabriel N. Castillo; Cynthia J. Gonzalez-Rivas; Atilio J. Mangold; Santiago Nava (Experimental and Applied Acarology, 2019)

Return period curves for extreme 5-min rainfall amounts at the Barcelona urban network - X. Lana; M. C. Casas-Castillo; C. Serra; R. Rodríguez-Solà; A. Redaño; A. Burgueño; M. D. Martínez (Theoretical and Applied Climatology, 2019)

Una Mano Amiga: Pilot Test of a Patient Navigator Program for Southwest New Mexico - Hugo Vilchis; Lynn E. Onstad; Rachel Benavidez; Rebecca Castillo; Nigel Bush; Janet Sanchez; Mary O’Connell; Beti Thompson; Carol M. Moinpour (Journal of Cancer Education, 2019)

UCYN‐A3, a newly characterized open ocean sublineage of the symbiotic N 2 ‐fixing cyanobacterium Candidatus Atelocyanobacterium thalassa - Francisco M. Cornejo‐Castillo; Maria del Carmen Muñoz‐Marín; Kendra A. Turk‐Kubo; Marta Royo‐Llonch; Hanna Farnelid; Silvia G. Acinas; Jonathan P. Zehr (Environmental Microbiology, 2019)
Summary The symbiotic unicellular cyanobacterium Candidatus Atelocyanobacterium thalassa (UCYN‐A) is one of the most abundant and widespread nitrogen (N 2 )‐fixing cyanobacteria in the ocean. Although it remains uncultivated, multiple sublineages have been detected based on partial nitrogenase ( nifH ) gene sequences, including the four most commonly detected sublineages UCYN‐A1, UCYN‐A2, UCYN‐A3 and UCYN‐A4. However, very little is known about UCYN‐A3 beyond the nifH sequences from nifH gene diversity surveys. In this study, single cell sorting, DNA sequencing, qPCR and CARD‐FISH assays revealed discrepancies involving the identification of sublineages, which led to new information on the diversity of the UCYN‐A symbiosis. 16S rRNA and nifH gene sequencing on single sorted cells allowed us to identify the 16S rRNA gene of the uncharacterized UCYN‐A3 sublineage. We designed new CARD‐FISH probes that allowed us to distinguish and observe UCYN‐A2 in a coastal location (SIO Pier; San Diego) and UCYN‐A3 in an open ocean location (Station ALOHA; Hawaii). Moreover, we reconstructed about 13% of the UCYN‐A3 genome from Tara Oceans metagenomic data. Finally, our findings unveil the UCYN‐A3 symbiosis in open ocean waters suggesting that the different UCYN‐A sublineages are distributed along different size fractions of the plankton defined by the cell‐size ranges of their prymnesiophyte hosts.

Ecological guidelines for designing networks of marine reserves in the unique biophysical environment of the Gulf of California - Adrian Munguia-Vega; Alison L. Green; Alvin N. Suarez-Castillo; Maria Jose Espinosa-Romero; Octavio Aburto-Oropeza; Andrés M. Cisneros-Montemayor; Gabriela Cruz-Piñón; Gustavo Danemann; Alfredo Giron-Nava; Ollin Gonzalez-Cuellar; Cristina Lasch; Maria del Mar Mancha-Cisneros; et al. (Reviews in Fish Biology and Fisheries, 2018)

Surface impurities on giant gypsum crystals from “la Cueva de las Espadas” (Cave of Swords), Naica, Mexico - Isaí Castillo-Sandoval; Luis E. Fuentes-Cobas; Bernardo E. Pérez-Cazares; Hilda E. Esparza-Ponce; María E. Fuentes-Montero; Hiram Castillo-Michel; Diane Eichert; Ignacio Reyes-Cortes; Iván J. Carreño-Márquez; José M. Napoles-Duarte; María E. Montero-Cabrera (Mineralogy and Petrology, 2018)

Characterization by next-generation sequencing of 24 new microsatellite loci for the barred sand-bass, Paralabrax nebulifer (Girard, 1854), from the Baja California Peninsula, Mexico - José F. Domínguez-Contreras; Adrian Munguia-Vega; Alejandro Castillo-Lopez; José Alberto Gracia-Olea; Cecilia M. Blasco; S. Hoyt Peckham (Marine Biodiversity, 2018)

Realized niche and spatial pattern of native and exotic halophyte hybrids - B. Gallego-Tévar; G. Curado; B. J. Grewell; M. E. Figueroa; J. M. Castillo (Oecologia, 2018)

Carriage of antibiotic-resistant bacteria in urban versus rural wild boars - Nora Navarro-Gonzalez; Raquel Castillo-Contreras; Encarna Casas-Díaz; Nicolas Morellet; M. Concepción Porrero; Guillem Molina-Vacas; Rita T. Torres; Carlos Fonseca; Gregorio Mentaberre; Lucas Domínguez; Santiago Lavín; Emmanuel Serrano (European Journal of Wildlife Research, 2018)

Logging Pattern and Landscape Change in Southern Mexico: Identifying Potential Weaknesses and Strengthening Conservation in Community-Based Management Programs through Landscape Analysis - J A Ascanio-Lárraga; J L León-Cortés; M A Castillo-Santiago; E Ramírez-Segura (Journal of Forestry, 2018)

Rainfall intensity patterns derived from the urban network of Barcelona (NE Spain) - Xavier Lana; C. Serra; M. C. Casas-Castillo; R. Rodríguez-Solà; A. Redaño; A. Burgueño (Theoretical and Applied Climatology, 2018)

Using unmanned aerial vehicle (UAV) surveys and image analysis in the study of large surface‐associated marine species: a case study on reef sharks Carcharhinus melanopterus shoaling behaviour - Guillaume Rieucau; Jeremy J. Kiszka; Jose Carlos Castillo; Johann Mourier; Kevin M. Boswell; Michael R. Heithaus (Journal of Fish Biology, 2018)
A novel image analysis‐based technique applied to unmanned aerial vehicle (UAV) survey data is described to detect and locate individual free‐ranging sharks within aggregations. The method allows rapid collection of data and quantification of fine‐scale swimming and collective patterns of sharks. We demonstrate the usefulness of this technique in a small‐scale case study exploring the shoaling tendencies of blacktip reef sharks Carcharhinus melanopterus in a large lagoon within Moorea, French Polynesia. Using our approach, we found that C. melanopterus displayed increased alignment with shoal companions when distributed over a sandflat where they are regularly fed for ecotourism purposes as compared with when they shoaled in a deeper adjacent channel. Our case study highlights the potential of a relatively low‐cost method that combines UAV survey data and image analysis to detect differences in shoaling patterns of free‐ranging sharks in shallow habitats. This approach offers an alternative to current techniques commonly used in controlled settings that require time‐consuming post‐processing effort.

Pharmacological dissection of the cellular mechanisms associated to the spontaneous and the mechanically stimulated ATP release by mesentery endothelial cells: roles of thrombin and TRPV - M. Verónica Donoso; Felipe Hernández; Tania Villalón; Claudio Acuña-Castillo; J. Pablo Huidobro-Toro (Purinergic Signalling, 2018)

Introduction to the special issue on “hydro-meteorological time series analysis and their relation to climate change” - Javier Estévez; Amanda García Marín; Julián Báez Benitez; M. Carmen Casas Castillo; Luciano Telesca (Acta Geophysica, 2018)

Analysis of synoptic patterns in relationship with severe rainfall events in the Ebre Observatory (Catalonia) - Núria Pérez-Zanón; M. Carmen Casas-Castillo; Juan Carlos Peña; Montserrat Aran; Raúl Rodríguez-Solà; Angel Redaño; German Solé (Acta Geophysica, 2018)

A single scaling parameter as a first approximation to describe the rainfall pattern of a place: application on Catalonia - M. Carmen Casas-Castillo; Alba Llabrés-Brustenga; Anna Rius; Raúl Rodríguez-Solà; Xavier Navarro (Acta Geophysica, 2018)

Lower tier toxicity risk assessment of agriculture pesticides detected on the Río Madre de Dios watershed, Costa Rica - M Arias-Andrés; R Rämö; F Mena Torres; R Ugalde; L Grandas; C Ruepert; L E Castillo; P J Van den Brink; J S Gunnarsson (Environmental Science and Pollution Research, 2018)

Forest resilience to drought varies across biomes - Antonio Gazol; Jesus Julio Camarero; Sergio M. Vicente‐Serrano; Raúl Sánchez‐Salguero; Emilia Gutiérrez; Martin de Luis; Gabriel Sangüesa‐Barreda; Klemen Novak; Vicente Rozas; Pedro A. Tíscar; Juan C. Linares; Natalia Martín‐Hernández; et al. (Global Change Biology, 2018)
Forecasted increase drought frequency and severity may drive worldwide declines in forest productivity. Species‐level responses to a drier world are likely to be influenced by their functional traits. Here, we analyse forest resilience to drought using an extensive network of tree‐ring width data and satellite imagery. We compiled proxies of forest growth and productivity ( TRW i, absolutely dated ring‐width indices; NDVI , Normalized Difference Vegetation Index) for 11 tree species and 502 forests in Spain corresponding to Mediterranean, temperate, and continental biomes. Four different components of forest resilience to drought were calculated based on TRW i and NDVI data before, during, and after four major droughts (1986, 1994–1995, 1999, and 2005), and pointed out that TRW i data were more sensitive metrics of forest resilience to drought than NDVI data. Resilience was related to both drought severity and forest composition. Evergreen gymnosperms dominating semi‐arid Mediterranean forests showed the lowest resistance to drought, but higher recovery than deciduous angiosperms dominating humid temperate forests. Moreover, semi‐arid gymnosperm forests presented a negative temporal trend in the resistance to drought, but this pattern was absent in continental and temperate forests. Although gymnosperms in dry Mediterranean forests showed a faster recovery after drought, their recovery potential could be constrained if droughts become more frequent. Conversely, angiosperms and gymnosperms inhabiting temperate and continental sites might have problems to recover after more intense droughts since they resist drought but are less able to recover afterwards.

Single-cell PCR amplification of thecate dinoflagellates: a case study of Tripos (Dinophyceae) - A. Hernández-Rosas; M. E. Meave del Castillo; J. Díaz-Larrea; F. Rodríguez (Journal of Applied Phycology, 2018)

The spectrum of genetic variants in hereditary pancreatic cancer includes Fanconi anemia genes - Thomas P. Slavin; Susan L. Neuhausen; Bita Nehoray; Mariana Niell-Swiller; Ilana Solomon; Christina Rybak; Kathleen Blazer; Aaron Adamson; Kai Yang; Sharon Sand; Nancy Guerrero-Llamas; Danielle Castillo; et al. (Familial Cancer, 2018)

Seascape genomics reveals adaptive divergence in a connected and commercially important mollusc, the greenlip abalone ( Haliotis laevigata ), along a longitudinal environmental gradient - Jonathan Sandoval‐Castillo; Nick A. Robinson; Anthony M. Hart; Lachlan W. S. Strain; Luciano B. Beheregaray (Molecular Ecology, 2018)
Populations of broadcast spawning marine organisms often have large sizes and are exposed to reduced genetic drift. Under such scenarios, strong selection associated with spatial environmental heterogeneity is expected to drive localized adaptive divergence, even in the face of connectivity. We tested this hypothesis using a seascape genomics approach in the commercially important greenlip abalone ( Haliotis laevigata ). We assessed how its population structure has been influenced by environmental heterogeneity along a zonal coastal boundary in southern Australia linked by strong oceanographic connectivity. Our data sets include 9,109 filtered SNP s for 371 abalones from 13 localities and environmental mapping across ~800 km. Genotype–environment association analyses and outlier tests defined 8,786 putatively neutral and 323 candidate adaptive loci. From a neutral perspective, the species is better represented by a metapopulation with very low differentiation (global F ST = 0.0081) and weak isolation by distance following a stepping‐stone model. For the candidate adaptive loci, however, model‐based and model‐free approaches indicated five divergent population clusters. After controlling for spatial distance, the distribution of putatively adaptive variation was strongly correlated to selection linked to minimum sea surface temperature and oxygen concentration. Around 80 candidates were annotated to genes with functions related to high temperature and/or low oxygen tolerance, including genes that influence the resilience of abalone species found in other biogeographic regions. Our study includes a documented example about the uptake of genomic information in fisheries management and supports the hypothesis of adaptive divergence due to coastal environmental heterogeneity in a connected metapopulation of a broadcast spawner.

Atom based linear index descriptors in QSAR-machine learning classifiers for the prediction of ubiquitin-proteasome pathway activity - Gerardo M. Casañola-Martin; Hai Pham-The; Juan A. Castillo-Garit; Huong Le-Thi-Thu (Medicinal Chemistry Research, 2018)

Assessing conservation practices in Amalacaxco Gorge (Izta-Popo National Park, Central Mexico) using fallout 137CS and Optically Stimulated Luminescence (OSL) - E Muñoz-Salinas; M Castillo (Journal of Mountain Science, 2018)

Exploring the effects of salinization on trophic diversity in freshwater ecosystems: a quantitative review - Anakena M. Castillo; Diana M. T. Sharpe; Cameron K. Ghalambor; Luis F. De León (Hydrobiologia, 2018)

Ocean–atmosphere conditions related to severe and persistent droughts in the Mexican Altiplano - José Pablo Vega‐Camarena; Luis Brito‐Castillo; Luis M. Farfán; David J. Gochis; Luis F. Pineda‐Martínez; Sara C. Díaz (International Journal of Climatology, 2018)
Ocean and atmospheric patterns associated with the most severe and most persistent droughts in the Mexican Altiplano region are explored. The standardized precipitation index on a time scale of 12 months was used and compared with time series of other atmospheric conditions to identify major dry episodes from 1970 to 2012. The time series were derived from the second mode of a varimax‐rotated empirical orthogonal functional analysis from the mean summer rainfall series observed at weather stations located in the Mexican Altiplano from 1970 through 2000. The results showed that the longest and most persistent episode occurred from 1998 through 2001, while the most severe dry episode occurred in 2011–2012, when the Pacific Decadal Oscillation was in a negative phase and the Atlantic Multidecadal Oscillation in a positive phase, both in combination with a La Niña event. A large upper‐level anticyclone over the north‐central United States is related to droughts in the Altiplano. Under these conditions, the droughts were linked to a large anticyclone positioned over the central‐north of the United States, with consequent negative anomalies of specific humidity over central‐northern Mexico. Concurrent with droughts in the interior of Mexico, are positive rainfall anomalies along the central Pacific coast of Mexico near the study area. Under different atmospheric conditions, opposite anomalous behaviour between the coast and interior can exist. The mechanism driving this see‐saw behaviour between the west coast of Mexico and the Altiplano is explored.

Designing connected marine reserves in the face of global warming - Jorge G. Álvarez‐Romero; Adrián Munguía‐Vega; Maria Beger; Maria del Mar Mancha‐Cisneros; Alvin N. Suárez‐Castillo; Georgina G. Gurney; Robert L. Pressey; Leah R. Gerber; Hem Nalini Morzaria‐Luna; Héctor Reyes‐Bonilla; Vanessa M. Adams; Melanie Kolb; et al. (Global Change Biology, 2018)
Marine reserves are widely used to protect species important for conservation and fisheries and to help maintain ecological processes that sustain their populations, including recruitment and dispersal. Achieving these goals requires well‐connected networks of marine reserves that maximize larval connectivity, thus allowing exchanges between populations and recolonization after local disturbances. However, global warming can disrupt connectivity by shortening potential dispersal pathways through changes in larval physiology. These changes can compromise the performance of marine reserve networks, thus requiring adjusting their design to account for ocean warming. To date, empirical approaches to marine prioritization have not considered larval connectivity as affected by global warming. Here, we develop a framework for designing marine reserve networks that integrates graph theory and changes in larval connectivity due to potential reductions in planktonic larval duration ( PLD ) associated with ocean warming, given current socioeconomic constraints. Using the Gulf of California as case study, we assess the benefits and costs of adjusting networks to account for connectivity, with and without ocean warming. We compare reserve networks designed to achieve representation of species and ecosystems with networks designed to also maximize connectivity under current and future ocean‐warming scenarios. Our results indicate that current larval connectivity could be reduced significantly under ocean warming because of shortened PLD s. Given the potential changes in connectivity, we show that our graph‐theoretical approach based on centrality (eigenvector and distance‐weighted fragmentation) of habitat patches can help design better‐connected marine reserve networks for the future with equivalent costs. We found that maintaining dispersal connectivity incidentally through representation‐only reserve design is unlikely, particularly in regions with strong asymmetric patterns of dispersal connectivity. Our results support previous studies suggesting that, given potential reductions in PLD due to ocean warming, future marine reserve networks would require more and/or larger reserves in closer proximity to maintain larval connectivity.

On the consideration of scaling properties of extreme rainfall in Madrid (Spain) for developing a generalized intensity-duration-frequency equation and assessing probable maximum precipitation estimates - M. Carmen Casas-Castillo; Raúl Rodríguez-Solà; Xavier Navarro; Beniamino Russo; Antonio Lastra; Paula González; Angel Redaño (Theoretical and Applied Climatology, 2018)

Genetic structure of Lima bean (Phaseolus lunatus L.) landraces grown in the Mayan area - Luciana Camacho-Pérez; Jaime Martínez-Castillo; Javier O. Mijangos-Cortés; Miriam M. Ferrer-Ortega; Jean Pierre Baudoin; Rubén H. Andueza-Noh (Genetic Resources and Crop Evolution, 2018)

Ecological disturbance influences adaptive divergence despite high gene flow in golden perch ( Macquaria ambigua ): Implications for management and resilience to climate change - Catherine R. M. Attard; Chris J. Brauer; Jonathan Sandoval‐Castillo; Leanne K. Faulks; Peter J. Unmack; Dean M. Gilligan; Luciano B. Beheregaray (Molecular Ecology, 2018)
Populations that are adaptively divergent but maintain high gene flow may have greater resilience to environmental change as gene flow allows the spread of alleles that have already been tested elsewhere. In addition, populations naturally subjected to ecological disturbance may already hold resilience to future environmental change. Confirming this necessitates ecological genomic studies of high dispersal, generalist species. Here we perform one such study on golden perch ( Macquaria ambigua ) in the Murray‐Darling Basin ( MDB ), Australia, using a genome‐wide SNP data set. The MDB spans across arid to wet and temperate to subtropical environments, with low to high ecological disturbance in the form of low to high hydrological variability. We found high gene flow across the basin and three populations with low neutral differentiation. Genotype–environment association analyses detected adaptive divergence predominantly linked to an arid region with highly variable riverine flow, and candidate loci included functions related to fat storage, stress and molecular or tissue repair. The high connectivity of golden perch in the MDB will likely allow locally adaptive traits in its most arid and hydrologically variable environment to spread and be selected in localities that are predicted to become arid and hydrologically variable in future climates. High connectivity in golden perch is likely due to their generalist life history and efforts of fisheries management. Our study adds to growing evidence of adaptation in the face of gene flow and highlights the importance of considering ecological disturbance and adaptive divergence in biodiversity management.

Feeding ecology of Mediterranean common dolphins: The importance of mesopelagic fish in the diet of an endangered subpopulation - Joan Giménez; Ana Marçalo; Manuel García‐Polo; Isabel García‐Barón; Juan José Castillo; Carolina Fernández‐Maldonado; Camilo Saavedra; M. Begoña Santos; Renaud de Stephanis (Marine Mammal Science, 2018)
The Mediterranean subpopulation of common dolphin ( Delphinus delphis ) is classified as endangered by the IUCN . Still, information about their diet in the Mediterranean is scarce. Stomach contents of 37 common dolphins stranded in the Alboran Sea and Strait of Gibraltar were analyzed. A total of 13,634 individual prey of 28 different taxa were identified. For fish, Myctophidae was the most important family as indicated by the highest index of relative importance ( IRI = 8,470), followed by the family Sparidae ( IRI = 609). The most important Myctophidae species was Madeira lantern fish ( Ceratoscopelus maderensis ) and for Sparids, the bogue ( Boops boops ). Cephalopods, instead, were found in low quantities only with 31 prey from the Loliginidae, Ommastrephidae, and Sepiolidae families. Overall, our results indicate that common dolphins are mainly piscivorous (99.77% N , 94.59% O , 99.73% W ), feeding mostly on mesopelagic prey. Although common dolphins inhabit mainly coastal waters in the study area, the narrow continental shelf seems to facilitate the availability of Myctophids and other members of the mesopelagic assemblage to dolphins when the assemblage migrates to the surface at night. Our results represent the first attempt at quantifying the diet of this predator in the Alboran Sea and Strait of Gibraltar.

Induced Degradation of Anthraquinone-Based Dye by Laccase Produced from Pycnoporus sanguineus (CS43) - Michelle Salazar-López; Magdalena de J. Rostro-Alanis; Carlos Castillo-Zacarías; Ana L. Parra-Guardado; Carlos Hernández-Luna; Hafiz M. N. Iqbal; Roberto Parra-Saldivar (Water, Air, & Soil Pollution, 2017)

Prognostic accuracy of SIRS criteria, qSOFA score and GYM score for 30-day-mortality in older non-severely dependent infected patients attended in the emergency department - J. González del Castillo; A. Julian-Jiménez; F. González-Martínez; J. Álvarez-Manzanares; P. Piñera; C. Navarro-Bustos; M. Martinez-Ortiz de Zarate; F. Llopis-Roca; M. Debán Fernández; J. Gamazo-Del Rio; E. J. García-Lamberechts; F. J. Martín-Sánchez (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Effects of transgenic expression of Brevibacterium linens methionine gamma lyase (MGL) on accumulation of Tylenchulus semipenetrans and key aminoacid contents in Carrizo citrange - Elenor Castillo; Federico Martinelli; Florence Zakharov-Negre; Susan E. Ebeler; Tom R. Buzo; Michael V. McKenry; Abhaya M. Dandekar (Plant Molecular Biology, 2017)

Impact of severe hematological abnormalities in the outcome of hospitalized patients with influenza virus infection - A. Lalueza; H. Trujillo; J. Laureiro; B. Ayuso; P. Hernández-Jiménez; C. Castillo; M. Torres; D. Folgueira; O. Madrid; C. Díaz-Pedroche; E. Arrieta; C. Arévalo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Prevalence, geographic distribution and phenotypic differences of Piscirickettsia salmonis EM ‐90‐like isolates - J Saavedra; N Hernandez; A Osses; A Castillo; A Cancino; H Grothusen; E Navas; P Henriquez; H Bohle; F Bustamante; P Bustos; M Mancilla (Journal of Fish Diseases, 2017)
Early reports accounted for two main genotypes of Piscirickettsia salmonis , a fish pathogen and causative agent of piscirickettsiosis, placing the single isolate EM ‐90 apart from the prototypic LF ‐89 and related isolates. In this study, we provide evidence that, contrary to what has been supposed, the EM ‐90‐like isolates are highly prevalent and disseminated across Chilean marine farms. Molecular analysis of 507 P. salmonis field isolates derived from main rearing areas, diverse hosts and collected over 6 years, revealed that nearly 50% of the entire collection were indeed typed as EM ‐90‐like. Interestingly, these isolates showed a marked host preference, being recovered exclusively from Atlantic salmon ( Salmo salar ) samples. Although both strains produce undistinguishable pathological outcomes, differences regarding growth kinetics and susceptibility to the antibiotics and bactericidal action of serum could be identified. In sum, our results allow to conclude that the EM ‐90‐like isolates represent an epidemiologically relevant group in the current situation of piscirickettsiosis. Based on the consistency between genotype and phenotype exhibited by this strain, we point out the need for genotypic studies that may be as important for the Chilean salmon industry as the continuous surveillance of antimicrobial susceptibility patterns.

Expression Changes in Metal-Resistance Genes in Microbacterium liquefaciens Under Nickel and Vanadium Exposure - Grisel Fierros-Romero; José A. Wrosek-Cabrera; Marlenne Gómez-Ramírez; Reynaldo C. Pless; A. M. Rivas-Castillo; Norma G. Rojas-Avelizapa (Current Microbiology, 2017)

Expression of typical osteoclast markers by PBMCs after PEG-induced fusion as a model for studying osteoclast differentiation - Luz M. Castillo; Carlos A. Guerrero; Orlando Acosta (Journal of Molecular Histology, 2017)

Canine distemper virus in the Serengeti ecosystem: molecular adaptation to different carnivore species - Veljko M. Nikolin; Ximena A. Olarte‐Castillo; Nikolaus Osterrieder; Heribert Hofer; Edward Dubovi; Camila J. Mazzoni; Edgar Brunner; Katja V. Goller; Robert D. Fyumagwa; Patricia D. Moehlman; Dagmar Thierer; Marion L. East (Molecular Ecology, 2017)
Was the 1993/1994 fatal canine distemper virus ( CDV ) epidemic in lions and spotted hyaenas in the Serengeti ecosystem caused by the recent spillover of a virulent domestic dog strain or one well adapted to these noncanids? We examine this question using sequence data from 13 ‘Serengeti’ strains including five complete genomes obtained between 1993 and 2011. Phylogenetic and haplotype network analyses reveal that strains from noncanids during the epidemic were more closely related to each other than to those from domestic or wild canids. All noncanid ‘Serengeti’ strains during the epidemic encoded: (1) one novel substitution G134S in the CDV ‐V protein; and (2) the rare amino acid combination 519I/549H at two sites under positive selection in the region of the CDV ‐H protein that binds to SLAM ( CD 150) host cell receptors. Worldwide, only a few noncanid strains in the America II lineage encode CDV ‐H 519I/549H. All canid ‘Serengeti’ strains during the epidemic coded CDV ‐V 134G, and CDV ‐H 519R/549Y, or 519R/549H. A functional assay of cell entry revealed the highest performance by CDV ‐H proteins encoding 519I/549H in cells expressing lion SLAM receptors, and the highest performance by proteins encoding 519R/549Y, typical of dog strains worldwide, in cells expressing dog SLAM receptors. Our findings are consistent with an epidemic in lions and hyaenas caused by CDV variants better adapted to noncanids than canids, but not with the recent spillover of a dog strain. Our study reveals a greater complexity of CDV molecular epidemiology in multihost environments than previously thought.

Erratum to: Physiological differences and changes in global DNA methylation levels in Agave angustifolia Haw. albino variant somaclones during the micropropagation process - Fátima Duarte-Aké; Eduardo Castillo-Castro; Felipe Barredo Pool; Francisco Espadas; Jorge M. Santamaría; Manuel L. Robert; Clelia De-la-Peña (Plant Cell Reports, 2017)

Tannins and mimosine in Leucaena genotypes and their relations to Leucaena resistance against Leucaena Psyllid and Onion thrips - Ahmed M. M. Ahmed; Francisco J. Solorio Sánchez; Luis Ramírez y Avilés; Rasha Ezzat Elsaid Mahdy; J. B. Castillo Camaal (Agroforestry Systems, 2017)

A study of the scaling properties of rainfall in spain and its appropriateness to generate intensity‐duration‐frequency curves from daily records - Raúl Rodríguez‐Solà; M. Carmen Casas‐Castillo; Xavier Navarro; Ángel Redaño (International Journal of Climatology, 2017)
A methodology based on the fractal properties of rainfall has been applied to obtain the intensity‐duration‐frequency, IDF , curves for 100 pluviometric Spanish stations over the Iberian Peninsula and the Balearic Islands from their daily precipitation series. The scaling behaviour of maximum rainfall intensities has been investigated and simple scaling has resulted suitable. This methodology has been verified in three emblematic observatories with available sub‐daily registers and current known generalized IDF relationships: the Fabra Observatory of Barcelona, the Ebre Observatory near Tortosa (Tarragona) and the Retiro Observatory of Madrid. Despite some general concordance with the mean annual rainfall distribution over Spain, the spatial distribution of the scaling parameter found for the 100 stations shows some discrepancies in diverse areas probably due to the influence of other features, as the inter‐annual rainfall variability and the contribution of convective rainfall to total precipitation, on the characteristic rainfall pattern in these areas.

Variability among strains of Aspergillus section Nigri with capacity to degrade tannic acid isolated from extreme environments - F. Lara-Victoriano; F. Veana; F. D. Hernández-Castillo; C. N. Aguilar; M. H. Reyes-Valdés; R. Rodríguez-Herrera (Archives of Microbiology, 2017)

Physiological differences and changes in global DNA methylation levels in Agave angustifolia Haw. albino variant somaclones during the micropropagation process - Fátima Duarte-Aké; Eduardo Castillo-Castro; Felipe Barredo Pool; Francisco Espadas; Jorge M. Santamaría; Manuel L. Robert; Clelia De-la-Peña (Plant Cell Reports, 2016)

Assessment of a fisheries legal framework for potential development of an ecosystem approach to fisheries management in large rivers - T. I. Castillo; C. R. M. Baigún; P. G. Minotti (Fisheries Management and Ecology, 2016)
Most small‐scale fisheries of large floodplain rivers are still managed under conventional top‐down regulations that limit the application of an ecosystem approach to fisheries ( EAF ) due to inappropriate legal frameworks. Using the Parana–Paraguay River fisheries (Argentina) as an example, this study examines the extent to which existing provincial legislations can be prepared for the adoption of an EAF . An Ecosystem Fishing Legal Approach ( EFLA ) framework is proposed based on different criteria across an environmental–ecological, fishing, social, economic and institutional template. Policy Component Scores ( PCS ) and an Integrated Policy Legal Index ( IPLI ) were applied to assess the degree of compliance by current provincial legislations to EAF implementation. Cluster analysis was used to recognise the potential for articulating a legal framework at a basin scale. The EFLA framework, which provided an accurate picture of how provinces were poorly prepared to adopt an EAF for the Paraguay–Parana fisheries, and represents a suitable tool that can be adapted and extended to other basins around the world.

Extreme 15N Depletion in Seagrasses - M. E. M. Walton; I. Al-Maslamani; N. Haddaway; H. Kennedy; A. Castillo; E. S. Al-Ansari; I. Al-Shaikh; M. Abdel-Moati; M. A. A. Al-Yafei; L. Le Vay (Estuaries and Coasts, 2016)

Identification of Focal Epileptogenic Networks in Generalized Epilepsy Using Brain Functional Connectivity Analysis of Bilateral Intracranial EEG Signals - Po-Ching Chen; Eduardo M. Castillo; James Baumgartner; Joo Hee Seo; Milena Korostenskaja; Ki Hyeong Lee (Brain Topography, 2016)

Carboxyl terminus-truncated α1D-adrenoceptors inhibit the ERK pathway - Marco A. Alfonzo-Méndez; Jean A. Castillo-Badillo; M. Teresa Romero-Ávila; Richard Rivera; Jerold Chun; J. Adolfo García-Sáinz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Spartina versicolor Fabre: Another case of Spartina trans-Atlantic introduction? - A. Baumel; M. Rousseau-Gueutin; C. Sapienza-Bianchi; A. Gareil; N. Duong; H. Rousseau; O. Coriton; R. Amirouche; S. Sciandrello; B. Duarte; I. Caçador; J. M. Castillo; et al. (Biological Invasions, 2016)

Variation in tussock architecture of the invasive cordgrass Spartina densiflora along the Pacific Coast of North America - Jesús M. Castillo; Brenda J. Grewell; Andrea J. Pickart; Enrique Figueroa; Mark Sytsma (Biological Invasions, 2016)

Phenotypic plasticity and population differentiation in response to salinity in the invasive cordgrass Spartina densiflora - Brenda J. Grewell; Jesús M. Castillo; Meghan J. Skaer Thomason; Rebecca E. Drenovsky (Biological Invasions, 2016)

Testing for functional convergence of temperate rainforest tree assemblages in Chile and New Zealand - CH Lusk; M Jimenez‐Castillo; R Aragón; TA Easdale; L Poorter; LF Hinojosa; NWH Mason (New Zealand Journal of Botany, 2016)
An important tenet of biogeography and comparative ecology is that disjunct assemblages in similar physical environments are functionally more similar to each other than to assemblages from other environments. Temperate rainforests in South America, New Zealand and Australia share certain physiognomic similarities, but we are not aware of any statistical evidence that these disjunct plant assemblages share a distinctive suite of functional traits, or trait combinations. We compiled height, leaf, wood and reproductive traits from the 25 commonest arborescent species at Chilean and New Zealand sites matched for summer rainfall, summer maximum temperatures, and winter minimum temperatures. We then used multivariate tests of trait convergence. Tropical and subtropical assemblages served as out‐groups. PERMANOVA showed convergence of trait centroids at the two temperate sites, where trees on average had denser wood and smaller leaves than trees at the (sub)tropical sites. Principal components analyses carried out separately on each assemblage showed that the Chilean and New Zealand assemblages were also the most similar pair in terms of trait relationships, although New Zealand also shared strong similarities with subtropical Argentina. The main axis of variation in both temperate assemblages ranged from small, short‐lived understorey trees with soft leaves, to emergents with sclerophyllous leaves and fairly dense wood. However, the New Zealand assemblage was much richer in small trees with soft leaves than its Chilean counterpart; possible historical influences on this difference include conditions favouring radiation of small trees during the late Neogene in New Zealand, competition from Chusquea bamboos in Chile and the historical absence of browsing mammals from New Zealand. Environmental filtering has produced similar values of individual traits in Chile and New Zealand, but only partial convergence of functional trait combinations. As far as we know, this is the first study to statistically test whether disjunct tree assemblages on climatically matched sites are more functionally similar to each other than to assemblages from other environments.

Analysis of extreme rainfall in the Ebre Observatory (Spain) - Núria Pérez-Zanón; M. Carmen Casas-Castillo; Raúl Rodríguez-Solà; Juan Carlos Peña; Anna Rius; J. Germán Solé; Ángel Redaño (Theoretical and Applied Climatology, 2016)

Drivers of fluorescent dissolved organic matter in the global epipelagic ocean - T. S. Catalá; X. A. Álvarez‐Salgado; J. Otero; F. Iuculano; B. Companys; B. Horstkotte; C. Romera‐Castillo; M. Nieto‐Cid; M. Latasa; X. A. G. Morán; J. M. Gasol; C. Marrasé; et al. (Limnology and Oceanography, 2016)
Fluorescent dissolved organic matter (FDOM) in open surface waters ( 70%) than for the amino acid‐like components ( a . Positive non‐linear relationships between both predictor variables and the two humic‐like PARAFAC components suggest that their distribution are biologically controlled. Compared with the dark ocean (> 200 m), the relationships of C1 and C2 with AOU indicate a higher C1/AOU and C2/AOU ratios of the humic‐like substances in the dark ocean than in the surface ocean where a net effect of photobleaching is also detected. C3 (tryptophan‐like) and C4 (tyrosine‐like) variability was mostly dictated by salinity ( S ), by means of positive non‐linear relationships, suggesting a primary physical control of their distributions at the global surface ocean scale that could be related to the changing evaporation‐precipitation regime. Remarkably, bacterial biomass (BB) only contributed to explain a minor part of the variability of C1 and C4.

Species‐specific diversity of novel bacterial lineages and differential abundance of predicted pathways for toxic compound degradation in scorpion gut microbiota - Luis M. Bolaños; Mónica Rosenblueth; Santiago Castillo‐Ramírez; Gilles Figuier‐Huttin; Esperanza Martínez‐Romero (Environmental Microbiology, 2016)
Summary Scorpions are considered ‘living fossils’ that have conserved ancestral anatomical features and have adapted to numerous habitats. However, their gut microbiota diversity has not been studied. Here, we characterized the gut microbiota of two scorpion species, V aejovis smithi and C entruroides limpidus . Our results indicate that scorpion gut microbiota is species‐specific and that food deprivation reduces bacterial diversity. 16S r RNA gene phylogenetic analysis revealed novel bacterial lineages showing a low level of sequence identity to any known bacteria. Furthermore, these novel bacterial lineages were each restricted to a different scorpion species. Additionally, our results of the predicted metagenomic profiles revealed a core set of pathways that were highly abundant in both species, and mostly related to amino acid, carbohydrate, vitamin and cofactor metabolism. Notably, the food‐deprived V . smithi shotgun metagenome matched almost completely the metabolic features of the prediction. Finally, comparisons among predicted metagenomic profiles showed that toxic compound degradation pathways were more abundant in recently captured C . limpidus scorpions. This study gives a first insight into the scorpion gut microbiota and provides a reference for future studies on the gut microbiota from other arachnid species.

Application of a multi-criteria decision model to select of design choices for WWTPs - M. Garrido-Baserba; R. Reif; M. Molinos-Senante; L. Larrea; A. Castillo; M. Verdaguer; M. Poch (Clean Technologies and Environmental Policy, 2016)

Implementation of an experimental nutrient film technique-type aquaponic system - D. Castillo-Castellanos; I. Zavala-Leal; J. M. J. Ruiz-Velazco; A. Radilla-García; J. T. Nieto-Navarro; C. A. Romero-Bañuelos; J. González-Hernández (Aquaculture International, 2016)

Physical, chemical, and management-related drivers of submerged macrophyte occurrence in Mediterranean farm ponds - Irene Gallego; Carmen Pérez-Martínez; Pedro M. Sánchez-Castillo; Francisca Fuentes-Rodríguez; Melchor Juan; J. Jesús Casas (Hydrobiologia, 2015)

Closing the gaps on the viral photosystem‐ I psa DCAB gene organization - Sheila Roitman; José Flores‐Uribe; Alon Philosof; Ben Knowles; Forest Rohwer; J. Cesar Ignacio‐Espinoza; Matthew B. Sullivan; Francisco M. Cornejo‐Castillo; Pablo Sánchez; Silvia G. Acinas; Chris L. Dupont; Oded Béjà (Environmental Microbiology, 2015)
Summary Marine photosynthesis is largely driven by cyanobacteria, namely S ynechococcus and P rochlorococcus . Genes encoding for photosystem ( PS ) I and II reaction centre proteins are found in cyanophages and are believed to increase their fitness. Two viral PSI gene arrangements are known, psaJF→ C →A→ B → K → E → D and psaD→ C →A→ B . The shared genes between these gene cassettes and their encoded proteins are distinguished by %G + C and protein sequence respectively. The data on the psaD→ C →A→ B gene organization were reported from only two partial gene cassettes coming from Global Ocean Sampling stations in the P acific and I ndian oceans. Now we have extended our search to 370 marine stations from six metagenomic projects. Genes corresponding to both PSI gene arrangements were detected in the P acific, I ndian and A tlantic oceans, confined to a strip along the equator (30°N and 30°S). In addition, we found that the predicted structure of the viral PsaA protein from the psaD→ C → A → B organization contains a lumenal loop conserved in PsaA proteins from S ynechococcus , but is completely absent in viral PsaA proteins from the psaJF→ C → A → B → K → E → D gene organization and most P rochlorococcus strains. This may indicate a co‐evolutionary scenario where cyanophages containing either of these gene organizations infect cyanobacterial ecotypes biogeographically restricted to the 30°N and 30°S equatorial strip.

Predictive classification of self-paced upper-limb analytical movements with EEG - Jaime Ibáñez; J. I. Serrano; M. D. del Castillo; J. Minguez; J. L. Pons (Medical & Biological Engineering & Computing, 2015)

Particle‐association lifestyle is a phylogenetically conserved trait in bathypelagic prokaryotes - Guillem Salazar; Francisco M. Cornejo‐Castillo; Encarna Borrull; Cristina Díez‐Vives; Elena Lara; Dolors Vaqué; Jesús M. Arrieta; Carlos M. Duarte; Josep M. Gasol; Silvia G. Acinas (Molecular Ecology, 2015)
The free‐living ( FL ) and particle‐attached ( PA ) marine microbial communities have repeatedly been proved to differ in their diversity and composition in the photic ocean and also recently in the bathypelagic ocean at a global scale. However, although high taxonomic ranks exhibit preferences for a PA or FL mode of life, it remains poorly understood whether two clear lifestyles do exist and how these are distributed across the prokaryotic phylogeny. We studied the FL ( PA (0.8–20 μm) prokaryotes at 30 stations distributed worldwide within the bathypelagic oceanic realm (2150–4000 m depth) using high‐throughput sequencing of the small subunit ribosomal RNA gene (16S rRNA ). A high proportion of the bathypelagic prokaryotes were mostly found either attached to particles or freely in the surrounding water but rarely in both types of environments. In particular, this trait was deeply conserved through their phylogeny, suggesting that the deep‐ocean particles and the surrounding water constitute two highly distinct niches and that transitions from one to the other have been rare at an evolutionary timescale. As a consequence, PA and FL communities had clear alpha‐ and beta‐diversity differences that exceeded the global‐scale geographical variation. Our study organizes the bathypelagic prokaryotic diversity into a reasonable number of ecologically coherent taxa regarding their association with particles, a first step for understanding which are the microbes responsible for the processing of the dissolved and particulate pools of organic matter that have a very different biogeochemical role in the deep ocean.

Genetic diversity and silencing suppression activity of the p22 protein of Tomato chlorosis virus isolates from tomato and sweet pepper - Yazmín M. Landeo-Ríos; Jesús Navas-Castillo; Enrique Moriones; M. Carmen Cañizares (Virus Genes, 2015)

Validation of a new catalysed reporter deposition–fluorescence in situ hybridization probe for the accurate quantification of marine B acteroidetes populations - Silvia G. Acinas; Isabel Ferrera; Hugo Sarmento; Cristina Díez‐Vives; Irene Forn; Clara Ruiz‐González; Francisco M. Cornejo‐Castillo; Guillem Salazar; Josep M. Gasol (Environmental Microbiology, 2015)
Summary Catalysed reporter deposition–fluorescence in situ hybridization ( CARD‐FISH ) is a powerful approach to quantify bacterial taxa. I n this study, we compare the performance of the widely used B acteroidetes CF 319 a probe with the new CF 968 probe. In silico analyses and tests with isolates demonstrate that CF 319 a hybridizes with non‐ B acteroidetes sequences from the R hodobacteraceae and A lteromonadaceae families. We test the probes’ accuracy in 37 globally distributed marine samples and over two consecutive years at the B lanes B ay M icrobial O bservatory ( NW M editerranean). We also compared the CARD‐FISH data with the B acteroidetes 16 S rRNA gene sequences retrieved from 27 marine metagenomes from the TARA Oceans expedition. We find no significant differences in abundances between both approaches, although CF 319 a targeted some unspecific sequences and both probes displayed different abundances of specific B acteroidetes phylotypes. Our results demonstrate that quantitative estimations by using both probes are significantly different in certain oceanographic regions ( M editerranean Sea, R ed Sea and A rabian Sea) and that CF 968 shows seasonality within marine B acteroidetes , notably large differences between summer and winter that is overlooked by CF 319 a . We propose CF 968 as an alternative to CF 319 a for targeting the whole B acteroidetes phylum since it has better coverage, greater specificity and overall better quantifies marine B acteroidetes .

Chemical modification of Byrsonima crassifolia with citric acid for the competitive sorption of heavy metals from water - J. Monroy-Figueroa; D. I. Mendoza-Castillo; A. Bonilla-Petriciolet; M. A. Pérez-Cruz (International Journal of Environmental Science and Technology, 2015)

Effects of cytomegalovirus infection in human neural precursor cells depend on their differentiation state - H. M. González-Sánchez; A. Monsiváis-Urenda; C. A. Salazar-Aldrete; A. Hernández-Salinas; D. E. Noyola; M. E. Jiménez-Capdeville; A. Martínez-Serrano; C. G. Castillo (Journal of NeuroVirology, 2015)

Vibrio mexicanus sp. nov., isolated from a cultured oyster Crassostrea corteziensis - Adrián González-Castillo; Julissa Enciso-Ibarrra; M. Carmen Bolán-Mejia; Sabela Balboa; Aide Lasa; Jesús L. Romalde; Hector Cabanillas-Beltrán; Bruno Gomez-Gil (Antonie van Leeuwenhoek, 2015)

Management of Perennial Warm-Season Bioenergy Grasses. II. Seasonal Differences in Elephantgrass and Energycane Morphological Characteristics Affect Responses to Harvest Frequency and Timing - Chae-In Na; Lynn E. Sollenberger; John E. Erickson; Kenneth R. Woodard; Miguel S. Castillo; M. Kimberly Mullenix; João M. B. Vendramini; Maria L. Silveira (BioEnergy Research, 2015)

Spinal cord toxoplasmosis in human immunodeficiency virus infection/acquired immunodeficiency syndrome - Concepción García-García; Federico Castillo-Álvarez; José M. Azcona-Gutiérrez; María J. Herraiz; Valvanera Ibarra; José A. Oteo (Infectious Diseases, 2015)

Removal of heavy metals and arsenic from aqueous solution using textile wastes from denim industry - D. I. Mendoza-Castillo; C. K. Rojas-Mayorga; I. P. García-Martínez; M. A. Pérez-Cruz; V. Hernández-Montoya; A. Bonilla-Petriciolet; M. A. Montes-Morán (International Journal of Environmental Science and Technology, 2015)

World Squid Fisheries - Alexander I. Arkhipkin; Paul G. K. Rodhouse; Graham J. Pierce; Warwick Sauer; Mitsuo Sakai; Louise Allcock; Juan Arguelles; John R. Bower; Gladis Castillo; Luca Ceriola; Chih-Shin Chen; Xinjun Chen; et al. (Reviews in Fisheries Science & Aquaculture, 2015)

Biochemical, Physical, Chemical, and Microbiological Assessment of Blue Shrimp ( Litopenaeus stylirostris ) Stored in Ice - Dalila F. Canizales-Rodríguez; Víctor M. Ocaño-Higuera; Enrique Marquez-Rios; Abril Z. Graciano-Verdugo; Jose L. Cárdenas-López; María S. Yepiz-Gómez; Francisco J. Castillo-Yáñez (Journal of Aquatic Food Product Technology, 2015)

Foraging ecology of silky sharks, Carcharhinus falciformis, captured by the tuna purse-seine fishery in the eastern Pacific Ocean - Leanne M. Duffy; Robert J. Olson; Cleridy E. Lennert-Cody; Felipe Galván-Magaña; Noemi Bocanegra-Castillo; Petra M. Kuhnert (Marine Biology, 2015)

Invasive Populations of Elephantgrass Differ in Morphological and Growth Characteristics from Clones Selected for Biomass Production - Lynn E. Sollenberger; Kenneth R. Woodard; João M. B. Vendramini; John E. Erickson; Kenneth A. Langeland; M. Kimberly Mullenix; Chaein Na; Miguel S. Castillo; Maria Gallo; Christine D. Chase; Yolanda López (BioEnergy Research, 2014)

Aerobiological study in the Mexico City subway system - O. Hernández-Castillo; V. Mugica-Álvarez; M. T. Castañeda-Briones; J. M. Murcia; F. García-Franco; Y. Falcón Briseño (Aerobiologia, 2014)

Integrative diagnosis and molecular phylogeny of dagger and needle nematodes of olives and grapevines in the island of Crete, Greece, with description of Xiphinema cretense n. sp. (Nematoda, Longidoridae) - Emmanuel A. Tzortzakakis; Antonio Archidona-Yuste; Carolina Cantalapiedra-Navarrete; Eleni Nasiou; Maria S. Lazanaki; Emmanouil M. Kabourakis; Juan E. Palomares-Rius; Pablo Castillo (European Journal of Plant Pathology, 2014)

Development of plaque assay for Chilean Infectious Salmon Anaemia Virus, application for virus purification and titration in salmon ASK cells - M T Castillo‐Cerda; L Cottet; D Toro‐Ascuy; E Spencer; M Cortez‐San Martín (Journal of Fish Diseases, 2014)

Community metabolism in a deep (stratified) tropical reservoir during a period of high water-level fluctuations - Patricia M. Valdespino-Castillo; Martín Merino-Ibarra; Jorge Jiménez-Contreras; Fermín S. Castillo-Sandoval; Jorge A. Ramírez-Zierold (Environmental Monitoring and Assessment, 2014)

Improving Environmental and Social Targeting through Adaptive Management in Mexico's Payments for Hydrological Services Program - KATHARINE R. E. SIMS; JENNIFER M. ALIX‐GARCIA; ELIZABETH SHAPIRO‐GARZA; LEAH R. FINE; VOLKER C. RADELOFF; GLEN ARONSON; SELENE CASTILLO; CARLOS RAMIREZ‐REYES; PATRICIA YAÑEZ‐PAGANS (Conservation Biology, 2014)
Natural resource managers are often expected to achieve both environmental protection and economic development even when there are fundamental trade‐offs between these goals. Adaptive management provides a theoretical structure for program administrators to balance social priorities in the presence of trade‐offs and to improve conservation targeting. We used the case of Mexico's federal Payments for Hydrological Services program (PSAH) to illustrate the importance of adaptive management for improving program targeting. We documented adaptive elements of PSAH and corresponding changes in program eligibility and selection criteria. To evaluate whether these changes resulted in enrollment of lands of high environmental and social priority, we compared the environmental and social characteristics of the areas enrolled in the program with the characteristics of all forested areas in Mexico, all areas eligible for the program, and all areas submitted for application to the program. The program successfully enrolled areas of both high ecological and social priority, and over time, adaptive changes in the program's criteria for eligibility and selection led to increased enrollment of land scoring high on both dimensions. Three factors facilitated adaptive management in Mexico and are likely to be generally important for conservation managers: a supportive political environment, including financial backing and encouragement to experiment from the federal government; availability of relatively good social and environmental data; and active participation in the review process by stakeholders and outside evaluators. Mejorando los Objetivos Ambiental y Social Mediante el Manejo Adaptativo en el Programa de Pagos por Servicios Hidrológicos en México

Effectiveness of the Aquatic Halophyte Sarcocornia perennis spp. perennis as a Biotool for Ecological Restoration of Salt Marshes - Guillermo Curado; Brenda J. Grewell; Enrique Figueroa; Jesús M. Castillo (Water, Air, & Soil Pollution, 2014)

Metal ion remediation by polyamidoamine dendrimers: a comparison of metal ion, oxidation state, and titania immobilization - V. A. Castillo; M. A. Barakat; M. H. Ramadan; H. L. Woodcock; J. N. Kuhn (International Journal of Environmental Science and Technology, 2014)

The climate in Zafra from 1750 to 1840: history and description of weather observations - M. I. Fernández-Fernández; M. C. Gallego; F. Domínguez-Castro; R. M. Trigo; J. A. García; J. M. Vaquero; J. M. Moreno González; J. Castillo Durán (Climatic Change, 2014)

Metagenomic 16S rDNA I llumina tags are a powerful alternative to amplicon sequencing to explore diversity and structure of microbial communities - Ramiro Logares; Shinichi Sunagawa; Guillem Salazar; Francisco M. Cornejo‐Castillo; Isabel Ferrera; Hugo Sarmento; Pascal Hingamp; Hiroyuki Ogata; Colomban de Vargas; Gipsi Lima‐Mendez; Jeroen Raes; Julie Poulain; et al. (Environmental Microbiology, 2014)
Summary Sequencing of 16S rDNA polymerase chain reaction ( PCR ) amplicons is the most common approach for investigating environmental prokaryotic diversity, despite the known biases introduced during PCR . Here we show that 16S rDNA fragments derived from Illumina‐sequenced environmental metagenomes ( mi tag s) are a powerful alternative to 16S rDNA amplicons for investigating the taxonomic diversity and structure of prokaryotic communities. As part of the T ara O ceans global expedition, marine plankton was sampled in three locations, resulting in 29 subsamples for which metagenomes were produced by shotgun Illumina sequencing (ca. 700 Gb). For comparative analyses, a subset of samples was also selected for R oche‐454 sequencing using both shotgun ( m454 tag s; 13 metagenomes, ca. 2.4 Gb) and 16S rDNA amplicon ( 454 tag s; ca. 0.075 Gb) approaches. Our results indicate that by overcoming PCR biases related to amplification and primer mismatch, mi tag s may provide more realistic estimates of community richness and evenness than amplicon 454 tag s. In addition, mi tag s can capture expected beta diversity patterns. Using mi tag s is now economically feasible given the dramatic reduction in high‐throughput sequencing costs, having the advantage of retrieving simultaneously both taxonomic ( B acteria, A rchaea and E ukarya) and functional information from the same microbial community.

Begomovirus diversity in tomato crops and weeds in Ecuador and the detection of a recombinant isolate of rhynchosia golden mosaic Yucatan virus infecting tomato - Lenin C. Paz-Carrasco; Gloria P. Castillo-Urquiza; Alison T. M. Lima; Cesar A. D. Xavier; Leticia M. Vivas-Vivas; Eduardo S. G. Mizubuti; F. Murilo Zerbini (Archives of Virology, 2014)

Effects of n-butanol on barley microspore embryogenesis - A. M. Castillo; N. H. Nielsen; A. Jensen; M. P. Vallés (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Partial characterisation of digestive proteases of the Mayan cichlid Cichlasoma urophthalmus - C. A. Cuenca-Soria; C. A. Álvarez-González; J. L. Ortiz-Galindo; H. Nolasco-Soria; D. Tovar-Ramírez; R. Guerrero-Zárate; A. Castillo-Domínguez; M. A. Perera-García; R. Hernández-Gómez; E. Gisbert (Fish Physiology and Biochemistry, 2014)

Do Spartina maritima Plantations Enhance the Macroinvertebrate Community in European Salt Marshes? - Guillermo Curado; Juan E. Sánchez-Moyano; Enrique Figueroa; Jesús M. Castillo (Estuaries and Coasts, 2014)

Prospecting metal-resistant plant-growth promoting rhizobacteria for rhizoremediation of metal contaminated estuaries using Spartina densiflora - L. Andrades-Moreno; I. del Castillo; R. Parra; B. Doukkali; S. Redondo-Gómez; P. Pérez-Palacios; M. A. Caviedes; E. Pajuelo; I. D. Rodríguez-Llorente (Environmental Science and Pollution Research, 2014)

Microbial diversity in Los Azufres geothermal field (Michoacán, Mexico) and isolation of representative sulfate and sulfur reducers - Elcia M. S. Brito; Norberto Villegas-Negrete; Irene A. Sotelo-González; César A. Caretta; Marisol Goñi-Urriza; Claire Gassie; Florence Hakil; Yannick Colin; Robert Duran; Felix Gutiérrez-Corona; Hilda A. Piñón-Castillo; Germán Cuevas-Rodríguez; et al. (Extremophiles, 2014)

Changes in gene expression patterns associated with microspore embryogenesis in hexaploid triticale (×Triticosecale Wittm.) - I. Żur; E. Dubas; M. Krzewska; R. A. Sánchez-Díaz; A. M. Castillo; M. P. Vallés (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Low dispersive modeling of Rayleigh waves on partly staggered grids - O. Rojas; B. Otero; J. E. Castillo; S. M. Day (Computational Geosciences, 2014)

Enhancing Antibacterial Activity Against Escherichia coli K-12 of Peptide Ib-AMP4 with Synthetic Analogues - J. M. Flórez-Castillo; Mercedes Perullini; Matias Jobbágy; Herminsul de Jesús Cano Calle (International Journal of Peptide Research and Therapeutics, 2014)

Inter-specific competition and management modify the morphology, nutrient content and resorption in Scots pine needles - Irantzu Primicia; J. Bosco Imbert; M. Carmen Traver; Federico J. Castillo (European Journal of Forest Research, 2014)

Stomach contents of cetaceans in the Alboran Sea and Gulf of Cadiz. - Garcia-Polo M.; Gimenez Joan; Mons J. Luis; Castillo Juan Jos; De Stephanis R; Santos M.B.; Fernndez Maldonado Carolina (Frontiers in Marine Science, 2014)

Biogeochemical responses to nutrient inputs in a Cuban coastal lagoon: runoff, anthropogenic, and groundwater sources - R. González-De Zayas; M. Merino-Ibarra; M. F. Soto-Jiménez; F. S. Castillo-Sandoval (Environmental Monitoring and Assessment, 2013)

Omeprazole and PGC-Formulated Heparin Binding Epidermal Growth Factor Normalizes Fasting Blood Glucose and Suppresses Insulitis in Multiple Low Dose Streptozotocin Diabetes Model - Gerardo M. Castillo; Akiko Nishimoto-Ashfield; Aryamitra A. Banerjee; Jennifer A. Landolfi; Alexander V. Lyubimov; Elijah M. Bolotin (Pharmaceutical Research, 2013)

Native plant restoration combats environmental change: development of carbon and nitrogen sequestration capacity using small cordgrass in European salt marshes - Guillermo Curado; Alfredo E. Rubio-Casal; Enrique Figueroa; Brenda J. Grewell; Jesús M. Castillo (Environmental Monitoring and Assessment, 2013)

Regional signatures of plant response to drought and elevated temperature across a desert ecosystem - Seth M. Munson; Esteban H. Muldavin; Jayne Belnap; Debra P. C. Peters; John P. Anderson; M. Hildegard Reiser; Kirsten Gallo; Alicia Melgoza-Castillo; Jeffrey E. Herrick; Tim A. Christiansen (Ecology, 2013)
The performance of many desert plant species in North America may decline with the warmer and drier conditions predicted by climate change models, thereby accelerating land degradation and reducing ecosystem productivity. We paired repeat measurements of plant canopy cover with climate at multiple sites across the Chihuahuan Desert over the last century to determine which plant species and functional types may be the most sensitive to climate change. We found that the dominant perennial grass, Bouteloua eriopoda , and species richness had nonlinear responses to summer precipitation, decreasing more in dry summers than increasing with wet summers. Dominant shrub species responded differently to the seasonality of precipitation and drought, but winter precipitation best explained changes in the cover of woody vegetation in upland grasslands and may contribute to woody‐plant encroachment that is widespread throughout the southwestern United States and northern Mexico. Temperature explained additional variability of changes in cover of dominant and subdominant plant species. Using a novel empirically based approach we identified “climate pivot points” that were indicative of shifts from increasing to decreasing plant cover over a range of climatic conditions. Reductions in cover of annual and several perennial plant species, in addition to declines in species richness below the long‐term summer precipitation mean across plant communities, indicate a decrease in the productivity for all but the most drought‐tolerant perennial grasses and shrubs in the Chihuahuan Desert. Overall, our regional synthesis of long‐term data provides a robust foundation for forecasting future shifts in the composition and structure of plant assemblages in the largest North American warm desert.

Erratum to: Protected Graft Copolymer Excipient Leads to a Higher Acute Maximum Tolerated Dose and Extends Residence Time of Vasoactive Intestinal Peptide Significantly Better than Sterically Stabilized Micelles - Sandra Reichstetter; Gerardo M. Castillo; Israel Rubinstein; Akiko Nishimoto-Ashfield; ManShun Lai; Cynthia C. Jones; Aryamitra Banerjee; Alex Lyubimov; Duane C. Bloedow; Alexei Bogdanov; Elijah M. Bolotin (Pharmaceutical Research, 2013)

The Missing Skill Set in Community Management of Tropical Forests - MIGUEL N. ALEXIADES; CHARLES M. PETERS; SARAH A. LAIRD; CITLALLI LÓPEZ BINNQÜIST; PATRICIA NEGREROS CASTILLO (Conservation Biology, 2013)

Huddling up in a dry environment: the physiological benefits of aggregation in an intertidal gastropod - José M. Rojas; Simón B. Castillo; Joan B. Escobar; Jennifer L. Shinen; Francisco Bozinovic (Marine Biology, 2013)

Phytoplankton species‐specific release of dissolved free amino acids and their selective consumption by bacteria - Hugo Sarmento; Cristina Romera-Castillo; Markus Lindh; Jarone Pinhassi; M. Montserrat Sala; Josep M. Gasol; Cèlia Marrase; Gordon T. Taylor (Limnology and Oceanography, 2013)
Despite representing only a small fraction of the ocean's dissolved organic matter pool, dissolved free amino acids (DFAA) have high turnover rates and are major nitrogen and carbon sources for bacterioplankton. Both phytoplankton and bacterioplankton assimilate and release DFAA, but their consumption and production are difficult to quantify in nature due to their short residence times (min) as dissolved monomers. We segregated DFAA production by phytoplankton and bacterial consumption by measuring individual DFAA concentrations in four axenic phytoplankton cultures during the exponential growth phase, and also after 4 d incubations in the presence of a natural bacterioplankton community. The amounts and composition of the DFAA pool varied widely among phytoplankton species. The proportion of dissolved organic carbon attributed to DFAA varied among cultures. The picoeukaryotic prasinophyte, Micromonas pusilla, released higher amounts of DFAA than the other species tested (diatoms and dinoflagellate), especially alanine, which has been reported as the dominant individual DFAA in some oligotrophic environments. Community structure of heterotrophic prokaryotes responded to differences in the quality of organic matter released among microalgal species, with Roseobacter ‐related bacteria responding strongly to exudate composition. Our results demonstrate the specificity of DFAA extracellular release among several algal species and their preferential uptake by members of bacterial communities.

Protected Graft Copolymer Excipient Leads to a Higher Acute Maximum Tolerated Dose and Extends Residence Time of Vasoactive Intestinal Peptide Significantly Better than Sterically Stabilized Micelles - Sandra Reichstetter; Gerardo M. Castillo; Israel Rubinstein; Akiko Nishimoto-Ashfield; ManShun Lai; Cynthia C. Jones; Aryamitra Banjeree; Alex Lyubimov; Duane C. Bloedow; Alexei Bogdanov; Elijah M. Bolotin (Pharmaceutical Research, 2013)

Multiple domestications of the Mesoamerican gene pool of lima bean (Phaseolus lunatus L.): evidence from chloroplast DNA sequences - R. H. Andueza-Noh; M. L. Serrano-Serrano; M. I. Chacón Sánchez; I. Sanchéz del Pino; L. Camacho-Pérez; J. Coello-Coello; J. Mijangos Cortes; D. G. Debouck; J. Martínez-Castillo (Genetic Resources and Crop Evolution, 2013)

Spectral irradiance dependence of sunlight effects on plankton dimethylsulfide production - Martí Gali; Clara Ruiz-Gonzàlez; Thomas Lefort; Josep M. Gasol; Clara Cardelús; Cristina Romera-Castillo; Rafel Simó (Limnology and Oceanography, 2013)
We investigated the short‐term effects of variable solar irradiance and spectrum on the gross biological production of dimethylsulfide (DMS), a trace gas with potential climatic effects, in eight experiments performed at different times of the year in a northwest Mediterranean coastal site. Experimentally determined net community DMS production, DMS photolysis, and dark microbial DMS consumption rates were used to calculate gross community DMS production by budgeting. In addition, the composition of the bacterioplankton and phytoplankton communities in the initial samples, and the photoinhibition of bulk bacterial heterotrophic activity and phytoplankton photosynthetic efficiency were monitored. Our results show that: (1) gross DMS production is irradiance dependent, with a maximum short‐term stimulation factor of 2‐ to 6‐fold compared to dark incubations; (2) its spectral shape is variable but generally similar to that of phytoplankton photoinhibition or photodamage, with more effective stimulation at shorter ultraviolet wavelengths; and (3) stronger stimulation occurs when samples are overexposed with respect to their prior exposure. Remarkably, the photoresponse of gross DMS production was in most cases strong enough to (at least) compensate the photochemical DMS loss at the water subsurface. Such response would prevent DMS depletion in stratified and highly irradiated waters. Since the initial microbial communities were representative of meso‐ to oligotrophic conditions, our observations should apply to a wide variety of oceanic regimes.

Draft whole genome sequence of the cyanide‐degrading bacterium P seudomonas pseudoalcaligenes CECT 5344 - Víctor M. Luque‐Almagro; Felipe Acera; Ma Isabel Igeño; Daniel Wibberg; Ma Dolores Roldán; Lara P. Sáez; Magdalena Hennig; Alberto Quesada; Ma José Huertas; Jochen Blom; Faustino Merchán; Ma Paz Escribano; et al. (Environmental Microbiology, 2013)
Summary P seudomonas pseudoalcaligenes CECT 5344 is a Gram‐negative bacterium able to tolerate cyanide and to use it as the sole nitrogen source. We report here the first draft of the whole genome sequence of a P . pseudoalcaligenes strain that assimilates cyanide. Three aspects are specially emphasized in this manuscript. First, some generalities of the genome are shown and discussed in the context of other P seudomonadaceae genomes, including genome size, G + C content, core genome and singletons among other features. Second, the genome is analysed in the context of cyanide metabolism, describing genes probably involved in cyanide assimilation, like those encoding nitrilases, and genes related to cyanide resistance, like the cio genes encoding the cyanide insensitive oxidases. Finally, the presence of genes probably involved in other processes with a great biotechnological potential like production of bioplastics and biodegradation of pollutants also is discussed.

The Mexican Sugarcane Industry: Overview, Constraints, Current Status and Long-Term Trends - N. Aguilar-Rivera; D. A. Rodríguez L.; V. Enríquez R.; A. Castillo M.; A. Herrera S. (Sugar Tech, 2012)

Time to positivity of blood culture association with clinical presentation, prognosis and ESBL-production in Escherichia coli bacteremia - R. Álvarez; L. Viñas-Castillo; J. A. Lepe-Jiménez; E. García-Cabrera; J. M. Cisneros-Herreros (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Potato, an experimental and natural host of the crinivirus Tomato chlorosis virus - Isabel M. Fortes; Jesús Navas-Castillo (European Journal of Plant Pathology, 2012)

Evaluation of four phenotypic methods to detect plasmid-mediated AmpC β-lactamases in clinical isolates - M. J. Gude; C. Seral; Y. Sáenz; M. González-Domínguez; C. Torres; F. J. Castillo (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Evaluation of an immunochromatographic dip strip test for simultaneous detection of Cryptosporidium spp, Giardia duodenalis, and Entamoeba histolytica antigens in human faecal samples - P. Goñi; B. Martín; M. Villacampa; A. García; C. Seral; F. J. Castillo; A. Clavel (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Sensory changes related to breeding for plant architecture and resistance to viruses and anthracnose in bean market class Fabada (Phaseolus vulgaris L.) - J. J. Ferreira; Romero R. del Castillo; E. Perez-Vega; M. Plans; J. Simó; F. Casañas (Euphytica, 2012)

Palm use and social values in rural communities on the coastal plains of Veracruz, Mexico - R. M. González-Marín; P. Moreno-Casasola; R. Orellana; A. Castillo (Environment, Development and Sustainability, 2012)

Muscular strength and markers of insulin resistance in European adolescents: the HELENA Study - D. Jiménez-Pavón; F. B. Ortega; J. Valtueña; J. Castro-Piñero; S. Gómez-Martínez; M. Zaccaria; F. Gottrand; D. Molnár; M. Sjöström; M. González-Gross; M. J. Castillo; L. A. Moreno; et al. (European Journal of Applied Physiology, 2012)

Diverse population of a new bipartite begomovirus infecting tomato crops in Uruguay - Belén Márquez-Martín; Diego Maeso; Ada Martínez-Ayala; Roberto Bernal; M. Teresa Federici; Paul Vincelli; Jesús Navas-Castillo; Enrique Moriones (Archives of Virology, 2012)

Simultaneous detection of the IPN and ISA viruses in outbreaks of clinical disease and mortality in farmed Atlantic salmon, Salmo salar L., in Chile - M Cortez‐San Martin; A Rivas‐Aravena; S Guajardo; M T Castillo; M Jashes; A M Sandino; E Spencer (Journal of Fish Diseases, 2012)

Potentially pathogenic nontuberculous mycobacteria found in aquatic systems. Analysis from a reclaimed water and water distribution system in Mexico City - A. I. Castillo-Rodal; M. Mazari-Hiriart; L. T. Lloret-Sánchez; B. Sachman-Ruiz; P. Vinuesa; Y. López-Vidal (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Protected Graft Copolymer (PGC) Basal Formulation of Insulin as Potentially Safer Alternative to Lantus® (Insulin-Glargine): A Streptozotocin-Induced, Diabetic Sprague Dawley Rats Study - Sandra Reichstetter; Gerardo M. Castillo; ManShun Lai; Akiko Nishimoto-Ashfield; Aryamitra Banerjee; Alexei Bogdanov; Alexander V. Lyubimov; Elijah M. Bolotin (Pharmaceutical Research, 2012)

Development of wild barley (Hordeum chilense)-derived DArT markers and their use into genetic and physical mapping - C. Rodríguez-Suárez; M. J. Giménez; N. Gutiérrez; C. M. Ávila; A. Machado; E. Huttner; M. C. Ramírez; A. C. Martín; A. Castillo; A. Kilian; A. Martín; S. G. Atienza (Theoretical and Applied Genetics, 2012)

Detection and characterization of a ST6 clone of vanB2-Enterococcus faecalis from three different hospitals in Spain - M. López; A. Rezusta; C. Seral; C. Aspiroz; C. Marne; M. J. Aldea; I. Ferrer; M. J. Revillo; F. J. Castillo; C. Torres (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Cardiac Tissue Injury Resistance During Myocardial Infarction at Adulthood by Developmental Exposure to Cadmium - Ramiro Zepeda; Paula Castillo; Daniel Sáez; Miguel N. Llanos; Ana M. Ronco (Cardiovascular Toxicology, 2012)

Diversity of Flavobacterium psychrophilum and the potential use of its phages for protection against bacterial cold water disease in salmonids - D Castillo; G Higuera; M Villa; M Middelboe; I Dalsgaard; L Madsen; R T Espejo (Journal of Fish Diseases, 2012)
Flavobacterium psychrophilum causes rainbow trout fry syndrome (RTFS) and cold water disease (CWD) in salmonid aquaculture. We report characterization of F. psychrophilum strains and their bacteriophages isolated in Chilean salmonid aquaculture. Results suggest that under laboratory conditions phages can decrease mortality of salmonids from infection by their F. psychrophilum host strain. Twelve F. psychrophilum isolates were characterized, with DNA restriction patterns showing low diversity between strains despite their being obtained from different salmonid production sites and from different tissues. We isolated 15 bacteriophages able to infect some of the F. psychrophilum isolates and characterized six of them in detail. DNA genome sizes were close to 50 Kbp and corresponded to the Siphoviridae and Podoviridae families. One isolate, 6H, probably contains lipids as an essential virion component, based on its chloroform sensitivity and low buoyant density in CsCl. Each phage isolate rarely infected F. psychrophilum strains other than the strain used for its enrichment and isolation. Some bacteriophages could decrease mortality from intraperitoneal injection of its host strain when added together with the bacteria in a ratio of 10 plaque‐forming units per colony‐forming unit. While we recognize the artificial laboratory conditions used for these protection assays, this work is the first to demonstrate that phages might be able protect salmonids from RTFS or CWD.

Assessment of Metal Pollution in Soils From a Former Havana (Cuba) Solid Waste Open Dump - O. Díaz Rizo; M. Hernández Merlo; F. Echeverría Castillo; J. O. Arado López (Bulletin of Environmental Contamination and Toxicology, 2012)

Extending Residence Time and Stability of Peptides by Protected Graft Copolymer (PGC) Excipient: GLP-1 Example - Gerardo M. Castillo; Sandra Reichstetter; Elijah M. Bolotin (Pharmaceutical Research, 2012)

Effect of fitness and physical activity on bone mass in adolescents: the HELENA Study - L. Gracia-Marco; G. Vicente-Rodríguez; J. A. Casajús; D. Molnar; M. J. Castillo; L. A. Moreno (European Journal of Applied Physiology, 2011)

Assessment of Heavy Metal Pollution in Urban Soils of Havana City, Cuba - O. Díaz Rizo; F. Echeverría Castillo; J. O. Arado López; M. Hernández Merlo (Bulletin of Environmental Contamination and Toxicology, 2011)

The Uptake of Copper by Aldama dentata: Ecophysiological Response, Its Modeling, and the Implication for Phytoremediation - N. Dasgupta-Schubert; M. G. Barrera; C. J. Alvarado; O. S. Castillo; E. M. Zaragoza; S. Alexander; S. Landsberger; S. Robinson (Water, Air, & Soil Pollution, 2011)

Algal assemblages and their relationship with water quality in tropical Mexican streams with different land uses - G. Vázquez; J. A. Aké-Castillo; M. E. Favila (Hydrobiologia, 2011)

Ambient ozone and pulmonary innate immunity - Mashael Al-Hegelan; Robert M. Tighe; Christian Castillo; John W. Hollingsworth (Immunologic Research, 2011)

Cerebellum Atrophy and Development of a Peripheral Dysgraphia: A Paediatric Case - Maria Concepción Fournier del Castillo; Maria Jesus Maldonado Belmonte; Maria Luz Ruiz-Falcó Rojas; Miguel Ángel López Pino; Jordi Bernabeu Verdú; Jesús M. Suárez Rodríguez (The Cerebellum, 2010)

Bond-based linear indices of the non-stochastic and stochastic edge-adjacency matrix. 1. Theory and modeling of ChemPhys properties of organic molecules - Yovani Marrero-Ponce; Eugenio R. Martínez-Albelo; Gerardo M. Casañola-Martín; Juan A. Castillo-Garit; Yunaimy Echevería-Díaz; Vicente Romero Zaldivar; Jan Tygat; José E. Rodriguez Borges; Ramón García-Domenech; Francisco Torrens; Facundo Pérez-Giménez (Molecular Diversity, 2010)

Molecular variability among isolates of Mycosphaerella graminicola, the causal agent of septoria tritici blotch, in Argentina - N. Castillo; C. Cordo; M. R. Simón (Phytoparasitica, 2010)

Effect of dietary protein source and time on alkaline proteolytic activity of Nile tilapia (Oreochromis niloticus) - Mayra L. González-Félix; Francisco J. Castillo-Yañez; Víctor M. Ocaño-Higuera; Martin Perez-Velazquez; Venecia Cota-Moreno; José Lozano-Taylor (Fish Physiology and Biochemistry, 2010)

Genetic stability of cryopreserved shoot tips of Rubus germplasm - Nina Rosa F. Castillo; Nahla V. Bassil; Sugae Wada; Barbara M. Reed (In Vitro Cellular & Developmental Biology - Plant, 2010)

Erratum: Production of chromophoric dissolved organic matter by marine phytoplankton - Cristina Romera-Castillo; Hugo Sarmento; Xosé Antón Álvarez-Salgado; Josep M. Gasol; Celia Marrasé (Limnology and Oceanography, 2010)

Role of the Y-Family DNA Polymerases YqjH and YqjW in Protecting Sporulating Bacillus subtilis Cells from DNA Damage - Andrea M. Rivas-Castillo; Ronald E. Yasbin; E. Robleto; Wayne L. Nicholson; Mario Pedraza-Reyes (Current Microbiology, 2010)

Production of chromophoric dissolved organic matter by marine phytoplankton - Cristina Romera Castillo; Hugo Sarmento; Xosé Antón Álvarez-Salgado; Josep M. Gasol; Celia Marraséa (Limnology and Oceanography, 2010)
Incubation experiments with axenic cultures of four common phytoplankton species of the genera Chaetoceros , Skeletonema , Prorocentrum , and Micromonas were performed to test for the production of fluorescent dissolved organic matter (FDOM) by marine phytoplankton. Our results prove that the four species exuded both fluorescent protein‐like and marine humic‐like materials in variable amounts, with more production by the diatoms Chaetoceros sp. and Skeletonema costatum and less by Prorocentrum minimum . Whereas the exudation of protein‐like substances by healthy phytoplankton cells has been recognized, the in situ production of marine humic‐like substances is still a matter of debate. Using axenic cultures, we demonstrate unequivocally that phytoplankton can directly contribute to the autochthonous production of colored humic‐like substances in the ocean. Extrapolation of these findings to the field indicates that about 20% of the marine humic‐like substances produced in the highly productive coastal upwelling system of the Ria de Vigo could originate from growing phytoplankton. Therefore, the exudation of FDOM by marine phytoplankton should be considered in future studies of the dynamics of colored DOM in marine systems.

Shrub encroachment can reverse desertification in semi‐arid Mediterranean grasslands - Fernando T. Maestre; Matthew A. Bowker; María D. Puche; M. Belén Hinojosa; Isabel Martínez; Pablo García‐Palacios; Andrea P. Castillo; Santiago Soliveres; Arántzazu L. Luzuriaga; Ana M. Sánchez; José A. Carreira; Antonio Gallardo; et al. (Ecology Letters, 2009)
The worldwide phenomenon of shrub encroachment in grass‐dominated dryland ecosystems is commonly associated with desertification. Studies of the purported desertification effects associated with shrub encroachment are often restricted to relatively few study areas, and document a narrow range of possible impacts upon biota and ecosystem processes. We conducted a study in degraded Mediterranean grasslands dominated by Stipa tenacissima to simultaneously evaluate the effects of shrub encroachment on the structure and composition of multiple biotic community components, and on various indicators of ecosystem function. Shrub encroachment enhanced vascular plant richness, biomass of fungi, actinomycetes and other bacteria, and was linked with greater soil fertility and N mineralization rates. While shrub encroachment may be a widespread phenomenon in drylands, an interpretation that this is an expression of desertification is not universal. Our results suggest that shrub establishment may be an important step in the reversal of desertification processes in the Mediterranean region.

Microspore embryogenesis: assignment of genes to embryo formation and green vs. albino plant production - M. Muñoz-Amatriaín; J. T. Svensson; A. M. Castillo; T. J. Close; M. P. Vallés (Functional & Integrative Genomics, 2009)

Inhibition of mammary tumor growth and metastases to bone and liver by dietary grape polyphenols - Linette Castillo-Pichardo; Michelle M. Martínez-Montemayor; Joel E. Martínez; Kristin M. Wall; Luis A. Cubano; Suranganie Dharmawardhane (Clinical & Experimental Metastasis, 2009)

The hemiplegic migraine-associated Y1245C mutation in CACNA1A results in a gain of channel function due to its effect on the voltage sensor and G-protein-mediated inhibition - Selma A. Serra; Noèlia Fernàndez-Castillo; Alfons Macaya; Bru Cormand; Miguel A. Valverde; José M. Fernández-Fernández (Pflügers Archiv - European Journal of Physiology, 2009)

Interindividual interactions of Molina’s hog-nosed skunksConepatus chinga in the Pampas grassland of Argentina - Juan I. Reppucci; Diego F. Castillo; Mauro Lucherini; Estela M. Luengos Vidal; Emma B. Casanave (Mammal Research, 2009)

Effects of abiotic factors on the life span of the invasive cordgrass Spartina densiflora and the native Spartina maritima at low salt marshes - Jesús M. Castillo; Enrique Figueroa (Aquatic Ecology, 2009)

Effect of exogenous arginine on sugarcane (Saccharum sp.) somatic embryogenesis, free polyamines and the contents of the soluble proteins and proline - N. Nieves; F. Sagarra; R. González; Y. Lezcano; M. Cid; M. A. Blanco; R. Castillo (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Strontium Levels in Different Causes of Death: Diagnostic Efficacy in Drowning - M. D. Pérez-Cárceles; A. Sibón; M. L. Gil del Castillo; M. A. Vizcaya; E. Osuna; T. Casas; J. L. Romero; A. Luna (Biological Trace Element Research, 2008)

Plant zonation at salt marshes of the endangered cordgrass Spartina maritima invaded by Spartina densiflora - Jesús M. Castillo; Enrique Mateos-Naranjo; Francisco J. Nieva; Enrique Figueroa (Hydrobiologia, 2008)

Potential use of seaweeds in the laying hen ration to improve the quality of n-3 fatty acid enriched eggs - S. Carrillo; E. López; M. M. Casas; E. Avila; R. M. Castillo; M. E. Carranco; C. Calvo; F. Pérez-Gil (Journal of Applied Phycology, 2008)

Six novel begomoviruses infecting tomato and associated weeds in Southeastern Brazil - Gloria P. Castillo-Urquiza; José Evando A. Beserra; Fernanda P. Bruckner; Alison T. M. Lima; Arvind Varsani; Poliane Alfenas-Zerbini; F. Murilo Zerbini (Archives of Virology, 2008)

Immunological changes after a single bout of moderate-intensity exercise in a hot environment - J. Romeo; D. Jiménez-Pavón; M. Cervantes-Borunda; J. Wärnberg; S. Gómez-Martínez; M. J. Castillo; A. Marcos (Journal of Physiology and Biochemistry, 2008)

Zinc sulphate improved microspore embryogenesis in barley - Begoña Echavarri; Mercedes Soriano; Luis Cistué; M. Pilar Vallés; Ana M. Castillo (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Enhanced induction of microspore embryogenesis after n-butanol treatment in wheat (Triticum aestivum L.) anther culture - M. Soriano; L. Cistué; A. M. Castillo (Plant Cell Reports, 2008)

Changes in chromium distribution during the electrodialytic remediation of a Cr (VI)-contaminated soil - Ana M. Nieto Castillo; Juan José Soriano; Rafael A. García-Delgado (Environmental Geochemistry and Health, 2008)

Cholesterol efflux and the effect of combined treatment with niacin and chromium on aorta of hyperlipidemic rat - Songul Suren Castillo; M. Mutluhan Doger; Sehnaz Bolkent; Refiye Yanardag (Molecular and Cellular Biochemistry, 2008)

Effects of colchicine on anther and microspore culture of bread wheat (Triticum aestivum L.) - Mercedes Soriano; Luis Cistué; María P. Vallés; Ana M. Castillo (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Correlation between the presence of symptoms and the Giardia duodenalis genotype - J. Sahagún; A. Clavel; P. Goñi; C. Seral; M. T. Llorente; F. J. Castillo; S. Capilla; A. Arias; R. Gómez-Lus (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Suitability of weed species prevailing in Spanish vineyards as hosts for root-knot nematodes - P. Castillo; H. F. Rapoport; J. E. Palomares Rius; R. M. Jiménez Díaz (European Journal of Plant Pathology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Carbon emissions from land-use change: an analysis of causal factors in Chiapas, Mexico - M. A. Castillo-Santiago; A. Hellier; R. Tipper; B. H. J. de Jong (Mitigation and Adaptation Strategies for Global Change, 2007)

Environmental evaluation of single-use and reusable cups - Nuria Garrido; M. Dolors Alvarez del Castillo (The International Journal of Life Cycle Assessment, 2007)

Environmental evaluation of single-use and reusable cups - Nuria Garrido; M. Dolors Alvarez del Castillo (The International Journal of Life Cycle Assessment, 2007)

Physalis ixocarpa and P. peruviana, new natural hosts of Tomato chlorosis virus - Helena P. Trenado; Isabel M. Fortes; Diamantina Louro; Jesús Navas-Castillo (European Journal of Plant Pathology, 2007)

Contrasting strategies to cope with drought by invasive and endemic species of Lantana in Galapagos - Jesús M. Castillo; Pablo Leira-Doce; Jorge Carrión-Tacuri; Edison Muñoz-Guacho; Aída Arroyo-Solís; Guillermo Curado; David Doblas; Alfredo E. Rubio-Casal; Antonio A. Álvarez-López; Susana Redondo-Gómez; Regina Berjano; Giovanny Guerrero; et al. (Biodiversity and Conservation, 2007)

The cyanotrophic bacterium Pseudomonas pseudoalcaligenes CECT5344 responds to cyanide by defence mechanisms against iron deprivation, oxidative damage and nitrogen stress - Victor M. Luque‐Almagro; María J. Huertas; M. Dolores Roldán; Comrado Moreno‐Vivián; Manuel Martínez‐Luque; Rafael Blasco; Francisco Castillo (Environmental Microbiology, 2007)
Summary Two‐dimensional (2‐D) electrophoresis approach has been used to test protein expression changes in response to cyanide in the alkaliphilic bacterium Pseudomonas pseudoalcaligenes CECT5344. This is a cyanide‐assimilating strain which also grows in media containing cyanide‐enriched effluent from the jewellery industry. The bacterium efficiently uses this residue as the sole nitrogen source for aerobic growth under alkaline pH with negligible nitrogen losses as HCN. Cell‐free extracts isolated from P. pseudoalcaligenes grown with a jewellery residue, free cyanide or ammonium chloride as nitrogen source were subjected to 2‐D electrophoresis and the spot patterns were examined to determine differential protein expression. Electrophoretic plates exhibiting an average of 1000 spots showed significant differences in the expression of about 44 proteins depending on the nitrogen source. Some of these protein spots were analysed by Matrix‐assisted laser desorption/ionization‐time of flight‐mass spectrometry (MALDI‐TOF‐MS). Characterization of five of these proteins reveals that cyanide shock induces proteins related to iron acquisition, regulation of nitrogen assimilation pathways and oxidative stress repairing and protection.

Cinnamtannin B-1 from bay wood exhibits antiapoptotic effects in human platelets - A. Bouaziz; C. Romera-Castillo; S. Salido; P. J. Linares-Palomino; J. Altarejos; A. Bartegi; J. A. Rosado; G. M. Salido (Apoptosis, 2007)

Prevalence of fecal carriage of ESBL-producing Enterobacteriaceae in hospitalized and ambulatory patients during two non-outbreak periods - F. J. Castillo García; C. Seral García; M. P. Gandara; M. I. Millán Lou; C. Pitart Ferré (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

ORIGINAL ARTICLE: Elevational parallels of latitudinal variation in the proportion of lianas in woody floras - M. Jiménez‐Castillo; S. K. Wiser; C. H. Lusk (Journal of Biogeography, 2007)
Aim To determine if elevational variation in the proportion of lianas in woody floras parallels the variation observed on latitudinal gradients. This is to be expected if the poleward decrease in the importance of lianas is related to the vulnerability of their wide vessels to freeze embolism. Location Coastal ranges of south‐central Chile (latitude 37°–40° S) and western South Island of New Zealand (41°–43° S). Methods The presence of all woody species was recorded in plots of 2500 m 2 (Chile) or 100–400 m 2 (New Zealand) on four elevational gradients in temperate rain forest. Each species was classified as a tree, shrub or liana. Original data were obtained from 22 plots at two sites in Chile. In New Zealand, two surveys comprising a total of 296 plots were extracted from the National Vegetation Survey data base. Results Liana species richness declined more or less monotonically on all four gradients, whereas richness of trees and shrubs showed more varied elevational patterns. The proportion of woody species contributed by the liana life‐form was negatively correlated with elevation on all four gradients, falling from 15 to 35% of the woody flora at c . 200 m a.s.l. to nil well below the tree line. The elevational and latitudinal limits of liana species were marginally significantly correlated in Chile, but not in New Zealand. Main conclusions The elevational parallel of the well‐documented decline in liana representation with increasing latitude is consistent with the hypothesis that cold intolerance is a strong control on the global distribution of the liana life‐form.

Influence of Grain Processing on Acid–Base Balance in Feedlot Steers - C. Castillo; J. Hernández; J. Méndez; J. Llena; V. Pereira; M. López-Alonso; J. L. Benedito (Veterinary Research Communications, 2006)

Expression and characterization of the assimilatory NADH-nitrite reductase from the phototrophic bacterium Rhodobacter capsulatus E1F1 - M. Francisca Olmo-Mira; Purificación Cabello; Carmen Pino; Manuel Martínez-Luque; David J. Richardson; Francisco Castillo; M. Dolores Roldán; Conrado Moreno-Vivián (Archives of Microbiology, 2006)

In vitro propagation of the neotropical giant bamboo, Guadua angustifolia Kunth, through axillary shoot proliferation - Víctor M. Jiménez; Jhamna Castillo; Elena Tavares; Eric Guevara; Mayra Montiel (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Influence of Fe concentration in the medium on multicellular pollen grains and haploid plants induced by mannitol pretreatment in barley (Hordeum vulgare L.) - A. Pulido; F. Bakos; A. Castillo; M. P. Vallés; B. Barnabás; A. Olmedilla (Protoplasma, 2006)

Interactions Between Nitrate Assimilation and 2,4-Dinitrophenol Cometabolism in Rhodobacter capsulatus E1F1 - V.M. Luque-Almagro; R. Blasco; L. Paloma Sáez; M. D. Roldán; C. Moreno-Vivián; F. Castillo; M. Martínez-Luque (Current Microbiology, 2006)

Production of doubled haploids in durum wheat (Triticum turgidum L.) through isolated microspore culture - L. Cistué; M. Soriano; A. M. Castillo; M. P. Vallés; J. M. Sanz; B. Echávarri (Plant Cell Reports, 2006)

Climatic cycles inferred from the aminostratigraphy and aminochronology of Quaternary dunes and palaeosols from the eastern islands of the Canary Archipelago - J. E. Ortiz; T. Torres; Y. Yanes; C. Castillo; J. De La Nuez; M. Ibáñez; M. R. Alonso (Journal of Quaternary Science, 2006)
Aminochronological and aminostratigraphical methods have been used to study the Quaternary aeolian deposits from the islands located east of the Canary Archipelago (Fuerteventura and Lanzarote islands and La Graciosa, Montaña Clara and Alegranza islets). The extent of racemisation/epimerisation of four amino acids (isoleucine, aspartic acid, phenylalanine and glutamic acid) was measured in land snail shells of the genus Theba . The age calculation algorithms of these amino acids have been determined to permit the numerical dating of these deposits. Eight Aminozones, each defining dune/palaeosol‐formation episodes, have been distinguished and dated at 48.6 ± 6.4, 42.5 ± 6.0, 37.8 ± 4.6, 29.4 ± 4.8, 22.4 ± 4.5, 14.9 ± 3.6, 11.0 ± 4.0 and 5.4 ± 1.1 ka BP, the first five of them defining cycles of 5–7 ka. The alternation of palaeosols and aeolian deposits, which are related to abrupt transitions from humid to arid conditions, are the reflection of globally induced changes in North Africa palaeoenvironmental conditions linked to the effect of African palaeomonsoons on the trade winds and the Saharan Air Layer. Probably these aeolian cycles, with a recurrence period of 5–7 ka, are the expression of multiples of the ∼2.4 ka solar‐cycle. Copyright © 2005 John Wiley & Sons, Ltd.

Kinetic Study of the Release of Lead in a Mine-Impacted Tropical River - F. Arcega-Cabrera; S. E. Castillo-Blum; M. A. Armienta (Bulletin of Environmental Contamination and Toxicology, 2005)

Application of the ‘Climafor’ Approach to Estimate Baseline Carbon Emissions of a Forest Conservation Project in the Selva Lacandona, Chiapas, Mexico - B. H. J. De Jong; A. Hellier; M. A. Castillo-Santiago; R. Tipper (Mitigation and Adaptation Strategies for Global Change, 2005)

Clonal growth and tiller demography of the invader cordgrass Spartina densiflora brongn. At two contrasting habitats in SW European salt marshes - F. Javier J. Nieva; Eloy M. Castellanos; Jesús M. Castillo; M. Enrique Figueroa (Wetlands, 2005)

Short-term responses to salinity of an invasive cordgrass - Jesús M. Castillo; Alfredo E. Rubio-Casal; Susana Redondo; Antonio A. Álvarez-López; Teresa Luque; Carlos Luque; Francisco J. Nieva; Eloy M. Castellanos; Manuel E. Figueroa (Biological Invasions, 2005)

Effects of ovariectomy and growth hormone administration on body composition and vascular function and structure in old female rats - C. Castillo; M. Cruzado C. Ariznavarreta; V. Lahera; V. Cachofeiro; P. Gil-Loyzaga; Jess A. F. Tresguerres (Biogerontology, 2005)

Growing more rice with less water: Research findings from a study in China - Randoph Barker; To Phuc Tuong; Yuanhua Li; E. G. Castillo; B. A. M. Bouman (Paddy and Water Environment, 2004)

Effect of irrigation method and N-fertilizer management on rice yield, water productivity and nutrient-use efficiencies in typical lowland rice conditions in China - Romeo J. Cabangon; To Phuc Tuong; Ernesto G. Castillo; Lang Xing Bao; Guoan Lu; Guangho Wang; Yuanlai Cui; Bas A. M. Bouman; Yuanhua Li; Chongde Chen; Jianzhang Wang (Paddy and Water Environment, 2004)

Identifying and structurally characterizing CD1b in Aotus nancymaae owl monkeys - Fabio Castillo; Carlos Guerrero; Esperanza Trujillo; Gabriela Delgado; Pilar Martinez; Luz M. Salazar; Paola Barato; Manuel E. Patarroyo; Carlos Parra-Lpez (Immunogenetics, 2004)

A comparison of Passalidae (Coleoptera, Lamellicornia) diversity and community structure between primary and secondary tropical forest in Los Tuxtlas, Veracruz, Mexico - MarÍa Luisa Castillo; Jorge M. Lobo (Biodiversity and Conservation, 2004)

Ten-Year Viability Study on Natural Populations of Drosophila Sibling Species from Laguna Verde, Veracruz, México - E. Pimentel; M. P. Cruces; V. M. Salceda; M. E. de la Rosa; L. Levine; J. A. Castillo (Archives of Environmental Contamination and Toxicology, 2004)

Changes with ageing in several leukocyte functions of male and female rats - Mnica De La Fuente; Isabel Baeza; Noelia Guayerbas; Marta Puerto; Carmen Castillo; Veronica Salazar; Carmen Ariznavarreta; Jesus A. F-tresguerres (Biogerontology, 2004)

Biological and molecular characterization of P101 isolate, a tobamoviral pepper strain from Bulgaria - M. Ruz del Pino; A. Moreno; M. Garca de Lacoba; S. Castillo-Lluva; P. Gilardi; M. T. Serra; I. Garca-Luque (Archives of Virology, 2003)

Natural Disturbances and Mining of Panamanian Coral Reefs by Indigenous People - Héctor M. Guzmán; Carlos Guevara; Arcadio Castillo (Conservation Biology, 2003)
Before the 1980s, coral reefs were considered relatively stable and healthy in Kuna‐Yala, Caribbean Panama. During the 1980s, however, several natural disturbances changed the reef's community structure. We evaluated historical changes in coral cover and for the first time provide quantitative evidence of a large‐scale process of reef degradation. This process started long before the onset of these disturbances as a result of demographic growth and the traditional practices of the Kuna people. Living coral cover declined 79% in 30 years ( 1970–2001 ) while the indigenous population increased 62%. We measured 20 km of seawall built with mined reef corals ( 16,000 m 3 ) and an increase in island surface area of 6.23 ha caused by coral land filling. Consequently, coastal erosion has increased as a result of the lack of a protective natural barrier and a 2.0 cm/year local increase in sea level. Coral‐mining and land‐filling practices to accommodate population expansion and mismanagement of resources have significantly modified the reef ecosystem and will have serious long‐term consequences. We propose eight priority conservation areas within the Indian reserve, based on reef conservation status. The Kuna people and their leaders are considering a cultural change, which may include a gradual and organized migration to the mainland, and have optimistically accepted our results.

Bottom‐up controls on bacterial production in tropical lowland rivers - María M. Castillo; George W. Kling; J. David Allan (Limnology and Oceanography, 2003)
The importance of organic carbon and inorganic nutrients in controlling bacterial production was investigated in two tropical lowland rivers draining undisturbed forested catchments. Glucose (C), ammonium (N), phosphate (P), leaf leachate, and algal leachate were added alone or combined to water collected from one clear‐water (Cataniapo) and one black‐water (Autana) river of the Middle Orinoco basin, and bacterial production (BP) was measured at 0, 8, 24, and 36 h of incubation. The rivers have low pH (3.8–5.9) and conductivity (6.3–9.1 µS cm −1 ) and abundant nitrogen (total N, 273–314 µg L −1 ) compared to phosphorus (total P, 3.6–5.5 µg L −1 ). BP was significantly stimulated by additions of P, CP, NP, and CNP in both river waters. N or C alone or combined did not stimulate BP, suggesting that P rather than carbon is the primary limiting nutrient in these rivers. Higher responses to CNP and CP amendments (3–7 times over controls), compared to P and NP (1.3–4 times over controls), indicate that carbon is an important secondary constraint to bacterial production. Responses to NP and P were more frequent in the Autana than in the Cataniapo, suggesting that bacteria in the clear‐water river were less resource limited than those in the black‐water river. Responses to added leaf leachate, which had high concentrations of P and dissolved organic carbon (DOC), were generally greater than responses to added algal leachate. Seasonal patterns in response to nutrient addition suggest that the size of the labile fraction of DOC may increase during periods of low and rising water.

Mexico's Community‐Managed Forests as a Global Model for Sustainable Landscapes - David Barton Bray; Leticia Merino‐Pérez; Patricia Negreros‐Castillo; Gerardo Segura‐Warnholtz; Juan Manuel Torres‐Rojo; Henricus F. M. Vester (Conservation Biology, 2003)
Researchers concerned with sustainable management of forests in the tropics have argued that the road to improved stewardship of forest resources is the transfer of responsibility to the local communities who get their livelihoods from them. On the other hand, conservationists have declared that the only way to stem the tide of deforestation is to place as many tracts as possible under strict protection. In this context, Mexico presents a national laboratory for studying the social and ecological benefits of delivering forests to local people. As a little‐noticed result of the Mexican Revolution in the second decade of the twentieth century, well over half of the forests of Mexico were placed in community‐held lands. In historic struggles that passed through several phases, most of these communities have now gained substantial control over the use of their forests. Because of the substantial degree of social capital in rural forms of organization in Mexico, this control of forest resources has led to an estimated 290–479 community forest enterprises ( CFEs ), through which communities are producing timber on their own lands. New studies are beginning to suggest that important gains in both social and economic justice, good forest management, and biodiversity protection are resulting from the actions of these CFEs. As more forests globally are being devolved to local communities, it is important to carry out more research on the Mexican model of community forest management for timber production.

Insights into Insulin and Glucagon Responses in Fish - I. Navarro; P. Rojas; E. Capilla; A. Albalat; J. Castillo; N. Montserrat; M. Codina; J. Gutiérrez (Fish Physiology and Biochemistry, 2002)

Effects of dietary fish oil on the fatty acid composition of the main lipid classes of chick plasma lipoproteins - M. Castillo; F. Amalik; E. García-Fuentes; E. García-Peregrín (Journal of Physiology and Biochemistry, 2002)

Evaluation of an Immunochromatographic Dip-Strip Test for the Detection of Cryptosporidium Oocysts in Stool Specimens - M. Llorente; A. Clavel; M. Varea; S. Olivera; F. Castillo; J. Sahagún; M. Rubio; R. Gómez-Lus (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Cattle as Biomonitors of Soil Arsenic, Copper, and Zinc Concentrations in Galicia (NW Spain) - M. López Alonso; J. L. Benedito; M. Miranda; C. Castillo; J. Hernández; R. F. Shore (Archives of Environmental Contamination and Toxicology, 2002)

Effect of Testosterone Suppression on the Pharmacokinetics of a Potent GnRH Receptor Antagonist - Eugenia A. Iatsimirskaia; Margaret L. Gregory; Kenna L. Anderes; Rosemary Castillo; K. Eric Milgram; David R. Luthin; Ved P. Pathak; Lance C. Christie; Haresh Vazir; Mark B. Anderson; John M. May (Pharmaceutical Research, 2002)

Parasitoid diversity and impact on populations of the diamondback moth Plutella xylostella (L.) on Brassica crops in central México - M. Martínez-Castillo; J.L. Leyva; J. Cibrián-Tovar; R. Bujanos-Muñiz (BioControl, 2002)

Structure of a pond community in Central Mexico - E. Escobar-Briones; A.M. Cortez-Aguilar; M. García-Ramos; L.M. Mejía-Ortíz; A.Y. Simms-Del Castillo (Hydrobiologia, 2002)

Genetic loci associated with field resistance to late blight in offspring of Solanum phureja and S.tuberosum grown under short-day conditions - M. Ghislain; B. Trognitz; Ma. del R. Herrera; J. Solis; G. Casallo; C. Vásquez; O. Hurtado; R. Castillo; L. Portal; M. Orrillo (Theoretical and Applied Genetics, 2001)

Effect of abscisic acid and jasmonic acid on partial desiccation of encapsulated somatic embryos of sugarcane - Nadina Nieves; M. E. Martínez; R. Castillo; María A. Blanco; J. L. González-Olmedo (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Some properties of semicarbazide-sensitive amine oxidase (SSAO) from human cerebrovascular tissues - C. Smeraldi; V. Castillo; J. M. Lizcano; M. Unzeta (Inflammation Research, 2001)

Efficient production of androgenic doubled-haploid mutants in barley by the application of sodium azide to anther and microspore cultures - A. M. Castillo; L. Cistué; M. P. Vallés; J. M. Sanz; I. Romagosa; J. L. Molina-Cano (Plant Cell Reports, 2001)

Polymorphism of the 5′ terminal region of Citrus tristeza virus (CTV) RNA: Incidence of three sequence types in isolates of different origin and pathogenicity - M. A. Ayllón; C. López; J. Navas-Castillo; S. M. Garnsey; J. Guerri; R. Flores; P. Moreno (Archives of Virology, 2001)

Causes and consequences of salt-marsh erosion in an Atlantic estuary in SW Spain - J. M. Castillo; C. J. Luque; E. M. Castellanos; M. E. Figueroa (Journal of Coastal Conservation, 2000)

Influence of hydrological seasonality on bacterioplankton in two neotropical floodplain lakes - María M. Castillo (Hydrobiologia, 2000)

Astrovirus Infection Among Children with Gastroenteritis in the City of Zaragoza, Spain - L. López; F. J. Castillo; M. A. Fernández; A. Clavel; M. C. Rubio; R. Gómez-Lus; B. Cutillas (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Investigation of Tuberculosis Contacts in a Nonhospital Pneumology Practice - D. del Castillo Otero; M. Peñafiel Colás; F. Álvarez Gutiérrez; J.G. Soto Campos; E. Calderón Osuna; J. Toral Marín; J. Sánchez Gómez (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Surface-sediment and epilithic diatom pH calibration sets for remote European mountain lakes (AL:PE Project) and their comparison with the Surface Waters Acidification Programme (SWAP) calibration set - N. G. Cameron; H. J. B. Birks; V. J. Jones; F. Berges; J. Catalan; R. J. Flower; J. Garcia; B. Kawecka; K. A. Koinig; A. Marchetto; P. Sánchez-Castillo; R. Schmidt; et al. (Journal of Paleolimnology, 1999)

Desiccated doubled-haploid embryos obtained from microspore culture of barley cv. Igri - A. B. Ryan; A. M. Castillo; M. P. Vallés; J. M. Sanz; L. Cistué (Plant Cell Reports, 1999)

Use of a Selective Medium and a Membrane Filter Method for Isolation of Campylobacter Species from Spanish Paediatric Patients - L. López; F. J. Castillo; A. Clavel; M. C. Rubio (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Somatic embryogenesis and plant regeneration from barley cultivars grown in Spain - A. M. Castillo; B. Egaña; J. M. Sanz; L. Cistué (Plant Cell Reports, 1998)

Use of a selective medium and a membrane filter method for isolation ofCampylobacter species from Spanish paediatric patients - L. López; F. J. Castillo; A. Clavel; M. C. Rubio (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Myosin II–actin interaction in MDCK cells: role in cell shape changes in response to Ca2+ variations - Aida M. Castillo; Roberto Lagunes; Mercedes Urbán; Eugenio Frixione; Isaura Meza (Journal of Muscle Research and Cell Motility, 1998)

Plasma membrane redox system activity in tumour cell lines of mammary origins with different proliferation rates - A. E. del Valle; A. del Castillo-Olivares; F. Sánchez-Jiménez; J. Márquez; I. Núñez de Castro; M. A. Medina (Protoplasma, 1998)

Plant regeneration from encapsulated somatic embryos of Carica papaya L. - B. Castillo; M. A. L. Smith; U. L. Yadava (Plant Cell Reports, 1998)

Degradation of p -nitrophenol by the phototrophic bacterium Rhodobacter capsulatus - M. D. Roldán; R. Blasco; F. J. Caballero; F. Castillo (Archives of Microbiology, 1997)

Fusarium and Fumonisins in Corn at Harvest Time: Effect of Fertilization and Planting Area - M. L. Ramirez; A. Torres; M. Rodriguez; C. Castillo; S. Chulze (Cereal Research Communications, 1997)

Direct somatic embryogenesis from Begonia gracilis explants - B. Castillo; M. A. L. Smith (Plant Cell Reports, 1997)

Direct somatic embryogenesis fromBegonia gracilis explants - B. Castillo; M. A. L. Smith (Plant Cell Reports, 1997)

Nitrate reductase activity in spheroplasts from Rhodobacter capsulatus E1F1 requires a periplasmic protein - Maria M. Dobao; Manuel Martnez-Luque; Francisco Castillo (Archives of Microbiology, 1993)

In vivo inhibition of nitrogenase by hydroxylamine in Rhodospirillaceae Role of nitric oxide - F. Javier Caballero; M. Isabel Igeo; Rafael Quiles; Francisco Castillo (Archives of Microbiology, 1992)

Inhibition of aconitase and fumarase by nitrogen compounds in Rhodobacter capsulatus - M. Martinez Luque-Romero; F. Castillo (Archives of Microbiology, 1991)